Optical film, optically active film, easily adhesive film, optical laminate, surface plate, image display device, and polarizing plate
By developing a polyester optical film containing more than 10% biomass components, and controlling the phase difference in the plane by stretching and processing, the problems of rainbow spot phenomenon and environmental burden in the prior art have been solved, and excellent visual recognition and Environmentally friendly optical film.
Patent Information
- Application Number
- CN202380052174.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-31
- Filing Date
- 2023-07-11
- Publication Date
- 2025-02-21
AI Technical Summary
When used in image display devices, existing optical laminates are prone to rainbow spots, which reduces visual recognition, and relies on fossil fuels in material selection, resulting in an increase in environmental burden.
A polyester material for optical films has been developed, containing more than 10% of biomass components, with a total light transmittance of more than 70%, and the phase difference in the control plane is between 3,000 nm and 30,000 nm by stretching processing. To reduce rainbow spot phenomenon and reduce environmental burden.
An optical film with excellent visual recognition is achieved, and the environmental burden is reduced by using biomass polyester materials, and the same optical and mechanical properties as fossil fuel polyester are maintained.
Smart Images

Figure BDA0005229901150000521 
Figure BDA0005229901150000531 
Figure BDA0005229901150000771
Abstract
Description
Technical Field
[0001] The present disclosure relates to an optical film, an optical action film, an easily adhesive film, an optical layered body, a surface plate, an image display device, and a polarizing plate. Background Art
[0002] Image display devices include various optical layered bodies for the purpose of improving image visibility and preventing damage to the device surface. Such optical layered bodies generally include a plastic film as an optical film and a functional layer provided on the film (see, for example, Patent Documents 1 and 2).
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2007-046031
[0006] Patent Document 2: Japanese Patent Application Publication No. 2012-256014 Summary of the invention
[0007] In recent years, the trend toward building a sustainable recycling-oriented society has been growing. From the perspective of carbon neutrality, there is a desire to move away from fossil fuels in the material field as well as in the energy field.
[0008] An object of the present disclosure is to provide an optical film capable of reducing environmental burden.
[0009] The optical film of the first embodiment of the present disclosure is an optical film for laminating a functional layer, comprising polyester, having a biomass degree of 10% or more, a total light transmittance of 70% or more, and an in-plane retardation of 3,000 nm to 30,000 nm.
[0010] The optical film of the second embodiment of the present disclosure is an optical film for laminating a functional layer, comprising polyester, having a biomass degree of 10% or more, a total light transmittance of 70% or more, and an in-plane retardation of 1,500 nm or less.
[0011] The optical film according to the third embodiment of the present disclosure contains polyester, has a biomass degree of 10% or more, a total light transmittance of 70% or more, and a yellowness index (YI) of -1.0 to 2.5.
[0012] The easy-adhesive film of the fourth embodiment of the present disclosure comprises a polyester film and an easy-adhesive layer, the polyester film contains polyester, the biomass degree of the easy-adhesive film is greater than 10%, the total light transmittance of the easy-adhesive film is greater than 70%, and the average value of δq / δa on the surface of the easy-adhesive layer is less than 3.10. The easy-adhesive film is used to set a functional layer on the easy-adhesive layer.
[0013] The optical layered body according to the fifth embodiment of the present disclosure includes a resin substrate and a functional layer provided on the resin substrate, and the complex elastic modulus of the functional layer is set to E r B. Set the composite elastic modulus of the resin substrate to E r In case of A, E r B is 1.0 GPa or more and 10.0 GPa or less, E r B / E r A is 0.50 or more and 2.00 or less, the biomass degree of the optical layered body is 10% or more, and the total light transmittance of the optical layered body is 70% or more.
[0014] According to the present disclosure, an optical film capable of reducing environmental burden is provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 It is a cross-sectional view schematically illustrating one embodiment of the optical film.
[0016] Figure 2 This is a schematic cross-sectional view of a corrosion rate measuring device.
[0017] Figure 3 This is an image diagram of a state in which an optical film is worn by a test liquid containing pure water and spherical silica ejected from an ejection unit.
[0018] Figure 4 It is a cross-sectional view schematically illustrating one embodiment of the optical film.
[0019] Figure 5 This is a cross-sectional view schematically illustrating one embodiment of the optical layered body.
[0020] Figure 6 It is a figure which shows schematically the state of a continuous folding test.
[0021] Figure 7 This is a cross-sectional view schematically illustrating one embodiment of the optical layered body.
[0022] Figure 8 This is a cross-sectional view schematically illustrating one embodiment of the optical layered body. DETAILED DESCRIPTION
[0023] In this specification, when multiple candidates for upper limit values and multiple candidates for lower limit values are listed for a certain parameter, the numerical range of the parameter can also be constructed by combining any one candidate for upper limit value and any one candidate for lower limit value. As an example, the statement "Parameter B can be greater than A1, greater than A2, or greater than A3. Parameter B can be less than A4, less than A5, or less than A6." is explained. In this example, the numerical range of parameter B can be greater than A1 and less than A4, greater than A1 and less than A5, greater than A1 and less than A6, greater than A2 and less than A4, greater than A2 and less than A5, greater than A2 and less than A6, greater than A3 and less than A4, greater than A3 and less than A5, or greater than A3 and less than A6.
[0024] In this specification, the terms "film", "sheet" and "plate" are used only as different names and do not distinguish each other. Therefore, for example, "film" also includes components that can also be called sheets or plates. As a specific example, "optical film" and "optically effective film" also include components that can also be called "optical sheet", "optical plate" and the like.
[0025] In this specification, unless otherwise stated, the atmosphere for measuring various parameters is set to a temperature of 23°C ± 5°C and a relative humidity of 40% to 65%. In addition, unless otherwise stated, the sample is exposed to the above atmosphere for 30 minutes to 60 minutes before each measurement. Examples of various parameters include nx-ny, Re, total light transmittance, and haze.
[0026] First Embodiment
[0027] A first embodiment of the present disclosure relates to an optical film.
[0028] Hereinafter, the first embodiment of the present disclosure will be described. First, the subject to be solved by the first embodiment will be described. For the purpose of improving the visual recognition of the image and suppressing the damage to the surface of the device, etc., the image display device has various optical layered bodies. Such an optical layered body usually has a plastic film as an optical film and a functional layer provided on the film (for example, refer to Japanese Patent Publication No. 2007-046031 and Japanese Patent Publication No. 2012-256014).
[0029] Polyester films such as polyethylene terephthalate films have been proposed as the plastic films, but when polyester films are applied to image display devices that output polarized light, such as liquid crystal display devices and organic EL display devices, rainbow-like interference patterns called rainbow spots may occur, which reduces visibility.
[0030] In recent years, there has been a growing trend toward building a sustainable recycling-oriented society. From the perspective of carbon neutrality, there is a desire to move away from fossil fuels in the material field as well as in the energy field.
[0031] An object of a first embodiment of the present disclosure is to provide an optical film that has excellent visibility and can reduce environmental burden.
[0032] According to the first embodiment of the present disclosure, an optical film having excellent visibility and reduced environmental burden is provided. Also, an optical film having optical and mechanical properties comparable to those of a polyester derived from fossil fuels can be provided even when using polyester derived from biomass materials.
[0033] [Optical film]
[0034] In this specification, an optical film refers to a film that can transmit light.
[0035] like Figure 1 As shown, the optical film 1 of the first embodiment of the present disclosure has a first surface 1a and a second surface 1b facing the first surface 1a. The polyester film described later also has a first surface and a second surface facing the first surface. When the first surface and the second surface are not particularly distinguished, they are sometimes simply referred to as "surfaces". The optical film has a first direction and a second direction orthogonal to the first direction within the plane. The first direction is the longitudinal direction, flow direction or mechanical direction (MD) of the optical film in the first embodiment. The second direction is the transverse direction or width direction (TD) of the optical film in the first embodiment. In the following description of the first embodiment of the present disclosure, unless otherwise specifically distinguished, when it is recorded as "optical film", it refers to the optical film of the first embodiment of the present disclosure.
[0036] In the first embodiment, the optical film includes at least a polyester film.
[0037] The polyester film refers to a film containing polyester.
[0038] In the first embodiment, the optical film is composed of a polyester film.
[0039] In the first embodiment, the optical film includes a polyester film and an easily adhesive layer provided on the polyester film. In the present specification, an optical film including a polyester film and an easily adhesive layer may be particularly referred to as an "easy adhesive film".
[0040] <Polyester>
[0041] The optical film and the polyester film each contain polyester.
[0042] Polyester refers to a copolymer of at least a diol component and a dicarboxylic acid component. The optical film contains at least a polyester derived from a biomass material (hereinafter also referred to as "biomass polyester") as the polyester. In the first embodiment, the polyester film contains at least a biomass polyester as the polyester. By measuring the biomass polyester as a raw material for the optical film and the polyester film and determining it as a film raw material, the biomass degree of the film can be predetermined, and the quality of the film can also be controlled.
[0043] Biomass polyester refers to polyester in which at least a part of raw material monomers are monomers derived from biomass materials such as plants. Examples of such plants include sugar cane and corn. Fossil fuel-derived polyester refers to polyester in which all raw material monomers are monomers derived from fossil fuels such as petroleum.
[0044] Examples of biomass polyesters include polyesters having diol units derived from a diol component and dicarboxylic acid units derived from a dicarboxylic acid component, wherein at least a portion of the diol component and / or at least a portion of the dicarboxylic acid component is derived from a biomass material.
[0045] Biomass polyester is preferably high in biomass degree as described below because it can contribute to reducing environmental burdens. However, the biomass degree does not necessarily need to be 100%, and may contain monomer units derived from fossil fuels.
[0046] As biomass polyester, for example, polyesters having diol units derived from ethylene glycol from biomass materials and dicarboxylic acid units derived from dicarboxylic acid components from fossil fuels, polyesters having diol units derived from ethylene glycol from fossil fuels and dicarboxylic acid units derived from dicarboxylic acid components from biomass materials, and polyesters having diol units derived from ethylene glycol from biomass materials and dicarboxylic acid units derived from dicarboxylic acid components from biomass materials. Due to easy acquisition or manufacture, polyesters having diol units derived from ethylene glycol from biomass materials and dicarboxylic acid units derived from dicarboxylic acid components from fossil fuels are preferred. In addition, polyesters having diol units derived from ethylene glycol from biomass materials, dicarboxylic acid units derived from dicarboxylic acid components from fossil fuels, and dicarboxylic acid units derived from dicarboxylic acid components from biomass materials are also preferred. By determining the biomass degree of polyester at the raw material stage of the film, it is determined as the film raw material, the biomass degree of the film can be determined in advance, and the quality of the film can also be controlled.
[0047] Ethylene glycol derived from biomass materials is obtained from ethanol produced from biomass materials as raw materials (hereinafter also referred to as "biomass ethanol"). For example, ethylene glycol derived from biomass materials can be obtained by a method of generating ethylene glycol from biomass ethanol via ethylene oxide. Commercially available ethylene glycol derived from biomass materials can also be used.
[0048] Examples of the diol component include, in addition to ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, butylene glycol, 2-methyl-1,3-propanediol, pentanediol, hexanediol, neopentyl glycol, cyclohexanedimethanol, cyclohexanediethanol, decahydronaphthalenedimethanol, decahydronaphthalenediethanol, norbornanediethanol, norbornanediethanol, tricyclodecanedimethanol, tricyclodecanediethanol, tetracyclododecanedimethanol, tetracyclododecanediethanol, decahydronaphthalenedimethanol, and decahydronaphthalenediethanol. , 5-hydroxymethyl-5-ethyl-2-(1,1-dimethyl-2-hydroxyethyl)-1,3-dioxane, cyclopentanediol, 3-methyl-1,2-cyclopentanediol, 4-cyclopentene-1,3-diol, cyclohexanediol, dicyclohexane-4,4'-diol, 2,2-bis(4-hydroxycyclohexylpropane), 2,2-bis(4-(2-hydroxyethoxy)cyclohexyl)propane, adamantanediol, p-xylene glycol, bisphenol A, bisphenol S and styrene glycol.
[0049] The diol component may be used alone or in combination of two or more.
[0050] Examples of the dicarboxylic acid component include dicarboxylic acids and their derivatives. Examples of the dicarboxylic acid include aromatic dicarboxylic acids and aliphatic dicarboxylic acids. Examples of the dicarboxylic acid derivative include alkyl esters (monoalkyl esters or dialkyl esters) and acid anhydrides of dicarboxylic acids.
[0051] As aromatic dicarboxylic acids, for example, terephthalic acid, isophthalic acid, phthalic acid, naphthalene dicarboxylic acid (1,4-naphthalene dicarboxylic acid, 1,5-naphthalene dicarboxylic acid, 2,5-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, 1,8-naphthalene dicarboxylic acid, etc.), 4,4'-diphenyl dicarboxylic acid, 4,4'-diphenyl ether dicarboxylic acid, diphenoxyethane dicarboxylic acid, diphenyl sulfone dicarboxylic acid, anthracene dicarboxylic acid, phenanthrene dicarboxylic acid, 9,9'-bis(4-carboxyphenyl)fluorene acid and furandicarboxylic acid can be mentioned. As derivatives of aromatic dicarboxylic acids, for example, alkyl esters of aromatic dicarboxylic acids, specifically methyl esters, ethyl esters, propyl esters and butyl esters can be mentioned. Among these, terephthalic acid, naphthalene dicarboxylic acid and furandicarboxylic acid and their alkyl esters are preferred.
[0052] As aliphatic dicarboxylic acids, for example, chain dicarboxylic acids and alicyclic dicarboxylic acids can be mentioned. As chain dicarboxylic acids, for example, oxalic acid, malonic acid, methylmalonic acid, dimethylmalonic acid, ethylmalonic acid, succinic acid, 3,3-diethylsuccinic acid, glutaric acid, 2,2-dimethylglutaric acid, adipic acid, 2-methyladipic acid, trimethyladipic acid, pimelic acid, suberic acid, sebacic acid, azelaic acid, dodecanedioic acid, eicosanedioic acid and dimer acid can be mentioned. As alicyclic dicarboxylic acids, for example, adamantane dicarboxylic acid, norbornene dicarboxylic acid, cyclopentane dicarboxylic acid, cyclohexane dicarboxylic acid, decahydronaphthalene dicarboxylic acid, hexahydroterephthalic acid and hexahydroisophthalic acid can be mentioned. As derivatives of aliphatic dicarboxylic acids, for example, alkyl esters such as methyl esters, ethyl esters, propyl esters and butyl esters of aliphatic dicarboxylic acids and cyclic acid anhydrides of aliphatic dicarboxylic acids such as succinic anhydride can be mentioned.
[0053] Examples of dicarboxylic acids derived from biomass materials include plant oils such as soybean oil, linseed oil, tung oil, coconut oil, palm oil, and castor oil, and aliphatic dicarboxylic acids obtained from plant raw materials such as recycled oils obtained by recycling waste cooking oils containing these as the main components. Examples of aliphatic dicarboxylic acids derived from biomass materials include succinic acid, glutaric acid, adipic acid, sebacic acid, and dimer acid.
[0054] The dicarboxylic acid component may be used alone or in combination of two or more.
[0055] The polyester may be a copolyester having a copolymerization unit derived from a copolymerization component as a third component in addition to the diol unit and the dicarboxylic acid unit. Examples of the copolymerization component include bifunctional hydroxycarboxylic acids, trifunctional or higher polyols for forming a crosslinked structure, trifunctional or higher polycarboxylic acids, anhydrides of the polycarboxylic acids, and trifunctional or higher hydroxycarboxylic acids.
[0056] As polyester, specifically, polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polytrimethylene terephthalate (PTT), polyethylene naphthalate (PEN), polybutylene naphthalate (PBN) and polyethylene 2,5-furandicarboxylate (PEF) can be cited. Among these, PET is preferred because an optical film with excellent mechanical strength can be obtained. As biomass polyester, specifically, polyesters produced using monomers derived from biomass materials as part or all of the raw material monomers (diol components and dicarboxylic acid components) in these polyesters can be cited.
[0057] The composition of the polyester can be determined by dissolving the polyester in hexafluoroisopropanol (HFIP) and using 1H-NMR and 13C-NMR to quantitatively determine the content ratio of each unit.
[0058] The polyester can be obtained by a conventionally known method of polycondensing at least a diol component and a dicarboxylic acid component. Specifically, the polyester can be produced by a general method of melt polymerization such as directly carrying out a polycondensation reaction of the diol component and the dicarboxylic acid component, or carrying out a polycondensation reaction under reduced pressure after carrying out an esterification reaction and / or an ester exchange reaction of the diol component and the dicarboxylic acid component, or a known solution heating dehydration condensation method using an organic solvent. The amount of the diol component used when producing the polyester can be substantially equimolar relative to 100 moles of the dicarboxylic acid component, but usually due to the presence of distillation during the reaction, it can be an amount of more than 100 moles and less than 120 moles.
[0059] The optical film may contain one or more polyesters.
[0060] The polyester film may contain one or more polyesters.
[0061] In addition to biomass polyester, the optical film may also contain polyester derived from fossil fuels. In addition to biomass polyester, the polyester film may also contain polyester derived from fossil fuels. By making the optical film or polyester film contain at least a portion of biomass polyester, the amount of polyester derived from fossil fuels can be reduced compared to the past, thereby reducing the environmental burden.
[0062] The optical film may contain polyester derived from recycled materials. The polyester contained in the optical film may be polyester derived from recycled materials and biomass polyester. A part of the polyester contained in the optical film may be polyester derived from recycled materials. In this case, the other part of the polyester contained in the optical film that is not polyester derived from recycled materials may be biomass polyester. The polyester derived from recycled materials may be recycled PET. The polyester derived from recycled materials may be a polyester derived from a raw material manufactured by recycling. More specifically, as a raw material for the polyester derived from recycled materials, at least any one of ethylene glycol derived from recycled materials or a dicarboxylic acid component derived from recycled materials may be used.
[0063] The content of the polyester in the optical film may exceed 50% by mass, may be 60% by mass or more, may be 70% by mass or more, may be 80% by mass or more, may be 90% by mass or more, or may be 95% by mass or more.
[0064] The content of the polyester in the polyester film may exceed 50% by mass, may be 60% by mass or more, may be 70% by mass or more, may be 80% by mass or more, may be 90% by mass or more, or may be 95% by mass or more.
[0065] The optical film and the polyester film may contain additives, respectively. Examples of additives include ultraviolet absorbers, light stabilizers, antioxidants, heat stabilizers, antistatic agents, slippery particles, heat-resistant polymer particles, alkali metal compounds, alkaline earth metal compounds, phosphorus compounds, flame retardants, anti-gelling agents, and surfactants. The optical film and the polyester film may contain one or more additives, respectively.
[0066] <Polyester film structure>
[0067] The polyester film may have a single-layer structure or a multi-layer structure. A film having a single-layer structure is easy to control stretching. A film having a multi-layer structure is easy to obtain the effect brought about by changing the composition of each layer.
[0068] In a polyester film having a multilayer structure, the biomass polyester may be contained in at least one layer. For example, a multilayer film having a layer containing a biomass polyester as a main component and a layer containing a polyester derived from a fossil fuel as a main component has excellent stretchability. In this specification, a layer containing a certain polymer as a main component refers to a layer containing the polymer in a proportion exceeding 50% by mass, and the content of the polymer may be 60% by mass or more, 70% by mass or more, 80% by mass or more, or 90% by mass or more.
[0069] Examples of the polyester film having a multilayer structure include:
[0070] (1A) A multilayer film comprising two or three or more layers containing a biomass polyester as a main component;
[0071] (2A) a multilayer film comprising a layer containing a biomass polyester as a main component and a layer containing a polyester derived from a fossil fuel as a main component;
[0072] (3A) a multilayer film comprising, in order, a layer containing a biomass polyester as a main component, a layer containing a polyester derived from a fossil fuel as a main component, and a layer containing a biomass polyester as a main component;
[0073] (4A) a multilayer film comprising, in order, a layer containing a biomass polyester as a main component, a layer containing a biomass polyester as a main component, and a layer containing a polyester derived from a fossil fuel as a main component;
[0074] (5A) A multilayer film comprising, in this order, a layer containing a polyester derived from fossil fuel as a main component, a layer containing a biomass polyester as a main component, and a layer containing a polyester derived from fossil fuel as a main component.
[0075] Examples of the polyester film having a multilayer structure include:
[0076] (1B) A multilayer film having two or three or more layers with a biomass degree of 10% or more;
[0077] (2B) A multilayer film comprising a layer having a biomass degree of 10% or more and a layer having a biomass degree of less than 10%;
[0078] (3B) a multilayer film comprising, in order, a layer having a biomass degree of 10% or more, a layer having a biomass degree of less than 10%, and a layer having a biomass degree of 10% or more;
[0079] (4B) a multilayer film comprising, in order, a layer having a biomass degree of 10% or more, a layer having a biomass degree of 10% or more, and a layer having a biomass degree of less than 10%;
[0080] (5B) A multilayer film having, in order, a layer having a biomass degree of less than 10%, a layer having a biomass degree of 10% or more, and a layer having a biomass degree of less than 10%. In the multilayer films of (1B) to (5B), the biomass degree of the film as a whole is 10% or more.
[0081] The multilayer films of (1A) and (1B) have high environmental contributions. The multilayer films of (2A) to (4A) and (2B) to (4B) have high environmental contributions and excellent stretchability. The multilayer films of (5A) and (5B) have high environmental contributions and excellent stretchability, and can also suppress the influence of impurities that can be precipitated from biomass polyester on the functional layer laminated on the optical film.
[0082] The polyester film having a multilayer structure may be a coextruded resin film. For example, the materials constituting each layer are coextruded to form a film, and then stretched to obtain a polyester film having a multilayer structure.
[0083] The thickness of the optical film may be 10 μm or more, 15 μm or more, 20 μm or more, 25 μm or more, or 30 μm or more. Such an optical film has excellent mechanical strength. The same applies to the thickness of the polyester film.
[0084] The thickness of the optical film may be 200 μm or less, 180 μm or less, 160 μm or less, 140 μm or less, 120 μm or less, or 100 μm or less. Such an optical film has excellent bending resistance. The same applies to the thickness of the polyester film.
[0085] In this specification, the thickness of the optical film and each layer is calculated by selecting 20 arbitrary locations of a cross-sectional photograph of the optical film obtained by a scanning electron microscope (SEM) and calculating the average value of the 20 locations. The 20 locations are selected so that the locations are not biased to one side. The acceleration voltage and magnification of the SEM are preferably set at an acceleration voltage of 1 kV to 10 kV and a magnification of 20 to 7,000 times, depending on the layer to be measured.
[0086] When forming a functional layer on an optical film, the film may be subjected to physical treatment such as corona discharge treatment or oxidation treatment to improve adhesion, or a coating called an anchor agent or a primer may be applied in advance.
[0087] The optical film and the optical layered body described later may be in the form of a single sheet cut into a specified size, or in the form of a roll in which a long strip is rolled up. The size of the single sheet, for example, has a maximum diameter of about 2 inches to about 500 inches. The maximum diameter refers to the maximum length when any two points in the surface of the optical film or optical layered body are connected. For example, when the optical film or optical layered body is a rectangle, the diagonal of the rectangle becomes the maximum diameter. When the optical film or optical layered body is a circle, the diameter of the circle becomes the maximum diameter.
[0088] The width of the roll-shaped form can be, for example, 500 mm to 8,000 mm. The length of the roll-shaped form can be, for example, 100 m to 10,000 m. The optical film and optical layered body in a roll-shaped form can be cut into a single piece for use according to the size of the image display device, etc. When cutting, it is preferred to remove the end of the roll whose physical properties are unstable.
[0089] The shape of the single piece can be, for example, a polygon such as a triangle, a quadrilateral, or a pentagon, or a circle, or a random amorphous shape. More specifically, when the optical film or optical layered body is a quadrilateral, the aspect ratio is not particularly limited as long as it does not cause any problem as a display screen. For example, aspect:vertical = 1:1, 4:3, 16:10, 16:9, 2:1, 5:4, 11:8 can be cited.
[0090] <Physical properties of optical films>
[0091] Hereinafter, physical properties that the optical film preferably has will be described.
[0092] (Biomass degree)
[0093] The biomass degree of the optical film is 10% or more, 12% or more, 15% or more, or 18% or more. Such an optical film can reduce the environmental burden. The higher the biomass degree of the optical film, the more preferred it is, for example, it can be 98% or less, 90% or less, 80% or less, 70% or less, 60% or less, 50% or less, 40% or less, or 30% or less.
[0094] In this specification, "biomass degree" (also referred to as biobased carbon content) refers to the value obtained by correcting the pMC (percent Modern Carbon) measured by Method B according to ASTM D6866-22 with δ13C. Specifically, the sample is burned to produce carbon dioxide (CO2), and the carbon dioxide is refined in a vacuum line. Using iron as a catalyst, the refined carbon dioxide is reduced with hydrogen to generate graphite. Then, by accelerator mass spectrometry (AMS method), the 14C count and carbon isotope ratio (14C / 12C, 13C / 12C) of the obtained graphite are measured. As a measuring device, a 14C-AMS dedicated device (manufactured by NEC Corporation) can be used. As a standard sample, oxalic acid (HOxII) provided by the National Bureau of Standards (NIST) of the United States is used. The determination of the standard sample and the background sample is also implemented simultaneously. According to the obtained carbon isotope ratio, the relative proportion (pMC) of the 14C / 12C of the sample relative to the standard sample is calculated. δ13C is the value of 13C / 12C of carbon in the measured sample, and the deviation from the reference sample is expressed in thousandths.
[0095] Biobased carbon content is the value obtained by multiplying pMC by a correction factor due to the excess 14C in the atmosphere caused by nuclear experiments. Since the excess 14C in the atmosphere is constantly decreasing, the correction factor is based on ASTM D6866-22.
[0096] Fossil fuel-derived materials do not contain radioactive carbon (14C) with a mass number of 14, whereas plant-derived materials contain 14C, so the two can be distinguished by the biomass degree based on the content of 14C. Thus, it is known that the biomass degree of fossil fuel-derived materials is approximately 0%. The biomass degree is an indicator indicating the mixing ratio of fossil fuel-derived materials and plant-derived materials.
[0097] When measuring the biomass of the entire optical film, a sample may be prepared from the optical film. When measuring the biomass of each layer in the optical film, a target layer may be separated from the optical film to prepare a sample.
[0098] (In-plane phase difference (Re))
[0099] The in-plane phase difference (Re) of the optical film is greater than 3,000 nm and less than 30,000 nm. In this specification, the "in-plane phase difference" is calculated by the formula: In-plane phase difference (Re) = (nx-ny) × T [nm]. "In-plane phase difference" is also called delay, and the unit is the unit of length. T in the above formula refers to the thickness of the optical film [nm].
[0100] "nx" is the refractive index in the direction of the slow axis, where the refractive index in the plane of the optical film is the largest. "ny" is the refractive index in the direction of the fast axis, which is a direction orthogonal to the slow axis in the plane of the optical film. The refractive index and in-plane phase difference refer to the refractive index and in-plane phase difference relative to a wavelength of 550nm. The direction of the slow axis and the in-plane phase difference are measured at a measurement angle of 0° using the trade name "RETS-100" manufactured by Otsuka Electronics Co., Ltd. In addition to the measurement results of the in-plane phase difference of "RETS-100", nx-ny can also be calculated from the thickness information of the optical film.
[0101] In this specification, nx-ny and Re are the average values of 16 measured values excluding the minimum and maximum values from 18 measured values. In this specification, the measurement site is selected from any site without defects such as damage and dirt.
[0102] The refractive index difference "nx-ny" (hereinafter also referred to as "Δn") may be 0.040 or more, or 0.050 or more. If Δn is 0.040 or more, the thickness of the optical film required to obtain the desired in-plane phase difference can be reduced. Δn may be 0.250 or less, or 0.200 or less. If Δn is 0.250 or less, there is no need to over-stretch the optical film, and the cracking and tearing of the optical film can be suppressed.
[0103] The refractive index (nx) in the slow axis direction may be 1.660 or more, or 1.680 or more. The refractive index (nx) in the slow axis direction may be 1.780 or less, or 1.730 or less. The refractive index (ny) in the fast axis direction may be 1.550 or more, or 1.570 or more. The refractive index (ny) in the fast axis direction may be 1.650 or less, or 1.620 or less.
[0104] The optical film or polyester film is preferably a stretched film. The stretched film may be a uniaxially stretched film or a biaxially stretched film. The biaxial stretching may be a stepwise biaxial stretching or a simultaneous biaxial stretching.
[0105] As an example, an optical film having an in-plane phase difference of 3,000 nm or more and 30,000 nm or less is obtained by stepwise biaxial stretching as follows: a resin composition containing polyester is melted and extruded into a sheet to obtain a cast film. The cast film is stretched in the flow direction and then stretched in the width direction of the film.
[0106] The stretching in the flow direction can be performed, for example, by utilizing the difference in the peripheral speed of the rollers. The stretching ratio in the flow direction can be 1.1 times or more, or 1.2 times or more. The stretching ratio in the flow direction can be 2.0 times or less, or 1.8 times or less.
[0107] From the perspective of suppressing the deviation of optical characteristics such as in-plane phase difference, the stretching temperature during stretching in the flow direction may be higher than the glass transition temperature of the polyester and lower than the glass transition temperature + 100° C. In the case of PET, the stretching temperature may be higher than 70° C., higher than 80° C., lower than 140° C., or lower than 130° C.
[0108] The stretching in the width direction can be carried out using a tentering method, for example. The stretching ratio in the width direction can be 2.5 times or more, or 3.0 times or more. The stretching ratio in the width direction can be 6.0 times or less, or 5.5 times or less. If the stretching ratio in the width direction is 6.0 times or less, the transparency of the film is excellent. If the stretching ratio in the width direction is 2.5 times or more, the necessary stretching tension is obtained, the birefringence becomes larger, and the desired in-plane phase difference is easily obtained. It is preferred that the stretching ratio in the width direction is higher than the stretching ratio in the flow direction.
[0109] The stretching temperature during the stretching in the width direction may be above the glass transition temperature of the polyester and below the glass transition temperature + 120°C. In the case of PET, the stretching temperature may be above 80°C, above 90°C, below 160°C, or below 150°C. The stretching temperature during the stretching in the width direction preferably increases as it goes from the upstream to the downstream. Specifically, when the stretching section in the width direction is divided into two parts, the difference between the temperature in the upstream and the temperature in the downstream may be above 5°C, above 20°C, or above 30°C. In the case of PET, the stretching temperature in the first stage may be above 80°C, above 90°C, below 120°C, or below 110°C.
[0110] In order to impart dimensional stability to the film subjected to stepwise biaxial stretching, it is preferred to perform heat treatment in a tenter at a temperature above the stretching temperature and below the melting point of the polyester. The temperature during the heat treatment may be 120°C or above, 180°C or above, 260°C or below, or 250°C or below.
[0111] The film which has been gradually biaxially stretched is heat treated and then rolled up after being cooled to room temperature.
[0112] As required, relaxation treatment may be performed during heat treatment and / or cooling. From the perspective of suppressing the deviation of optical properties, the relaxation rate during heat treatment may be 0.5% or more, 0.8% or more, 5% or less, or 3% or less. From the perspective of suppressing the deviation of optical properties, the relaxation rate during cooling may be 0.5% or more, 0.8% or more, 3% or less, or 2% or less. From the perspective of the dimensional stability of the film, the temperature of the relaxation treatment during cooling may be 80°C or more, 90°C or more, 150°C or less, or 130°C or less.
[0113] Polyester has excellent transparency, heat resistance and mechanical properties, and can control the in-plane phase difference in a wide range by stretching. An optical film containing polyester has a large intrinsic birefringence, and can ensure a large in-plane phase difference even with a small thickness.
[0114] As a method for controlling the in-plane phase difference of the optical film to be 3,000 nm or more and 30,000 nm or less, there is a method of appropriately setting the stretching ratio, the stretching temperature, and the thickness of the produced optical film. Specifically, the larger the stretching ratio ratio, the larger the in-plane phase difference. The lower the stretching temperature, the larger the in-plane phase difference. The larger the thickness, the larger the in-plane phase difference. The closer the stretching ratio ratio is to 1, the smaller the in-plane phase difference. The higher the stretching temperature, the smaller the in-plane phase difference. The smaller the thickness, the smaller the in-plane phase difference.
[0115] When polarized light passes through a film having birefringence, rainbow spots can be observed on the film. Rainbow spots are rainbow-colored spots that reduce the visual recognition of the film. Polarized light is, for example, image light emitted from a liquid crystal display element or an organic EL display element including a reflection suppression functional layer based on polarization control. Rainbow spots can also be observed with the naked eye, but can be observed more clearly through a polarizing film such as polarized sunglasses. If rainbow color unevenness occurs on the displayed image, the display quality deteriorates.
[0116] It is speculated that the rainbow spots are caused by the following reasons. Usually, when light passes through a component with an in-plane phase difference, the polarization state changes. Therefore, if the component with an in-plane phase difference is arranged between two polarizers, the visible light transmittance of each wavelength of the transmitted light changes according to the in-plane phase difference of the component. Therefore, the light passing through the film with an in-plane phase difference arranged between the two polarizers is visually recognized as a color corresponding to the in-plane phase difference of the film. Moreover, if there is a deviation in the in-plane phase difference at each position of the film surface of the film, the color of the transmitted light also deviates at each position of the film surface of the film. That is, it is speculated that the reason for the rainbow spots is that the light in the polarization state passes through the film with a deviation in the in-plane phase difference, and then the polarization state changes.
[0117] The greater the in-plane phase difference of the optical film, the greater the change in the visible light transmittance of each wavelength relative to the change in the in-plane phase difference. In addition, the greater the in-plane phase difference, the easier it is for light of multiple wavelengths to pass through, so the light that passes through is mixed and easier to be visually recognized. That is, even if there is a deviation in the in-plane phase difference, the visible light transmittance of each wavelength also changes greatly, so even if the transmittance of a certain wavelength becomes low, the transmittance of other wavelengths also becomes high. Therefore, the change in the mixed color of the transmitted light is difficult to be visually recognized in the visual view. If the in-plane phase difference of the optical film is 3,000nm or more, the change in the visible light transmittance of each wavelength corresponding to the in-plane phase difference becomes larger, and even if the visible light transmittance changes due to the deviation of the in-plane phase difference, it will be mixed and visually recognized, and it is difficult to visually recognize the change in color. That is, the rainbow spot can be effectively made less obvious. From this aspect, the in-plane phase difference of the optical film is 3,000nm or more, 4,000nm or more, or 5,000nm or more. The optical film having such an in-plane phase difference can effectively make rainbow spots less noticeable. In addition, from the perspective of suppressing cracking and tearing during stretching, the in-plane phase difference of the optical film is 30,000 nm or less, 25,000 nm or less, 20,000 nm or less, or 15,000 nm or less.
[0118] (Retardation in the thickness direction (Rth))
[0119] In this specification, "the value obtained by dividing the in-plane phase difference (Re) of the optical film by the phase difference (Rth) in the thickness direction of the optical film" is recorded as "Re / Rth". In this specification, "Rth" is a parameter representing the average delay obtained by multiplying the two birefringences △Nxz (=|nx-nz|) and △Nyz (=|ny-nz|) by the film thickness T when observing from a cross section in the film thickness direction. Specifically, Rth is calculated by the formula: "Rth=(△Nxz×T+△Nyz×T) / 2". "nx" and "ny" are defined as above, and "nz" is the refractive index in the thickness direction of the optical film. The refractive index and Rth refer to the refractive index and Rth relative to a wavelength of 550nm. Rth is measured at a measuring angle of 0° using the trade name "RETS-100" manufactured by Otsuka Electronics Co., Ltd.
[0120] From the perspective of suppressing the generation of rainbow spots caused by the viewing angle, the Re / Rth of the optical film can be greater than 0.2, or greater than 0.5. From the perspective of mechanical strength, the Re / Rth of the optical film can be less than 1.2, or less than 1.0. Rth can be adjusted by controlling the stretch ratio of the optical film.
[0121] In this specification, Rth means the average value of 16 measurement values excluding the minimum and maximum values from the 18 measurement values. In this specification, the measurement site is selected from any site without defects such as damage and dirt.
[0122] (Maximum strain along the principal axis of orientation)
[0123] In the optical film, the maximum strain of the orientation axis measured by a microwave transmission type molecular orientation meter can be 7° or less, 6° or less, 5° or less, or 4° or less. The surface plate for an image display device having such an optical film can suppress the reduction in the visual recognition of the product caused by, for example, light leakage during black display and display color changes caused by phase difference. The maximum strain of the orientation axis is 0° or more, and the lower the better, but there is no particular limitation.
[0124] The maximum strain of the main axis of orientation can be adjusted to be below the upper limit value by adjusting the temperature and stretching ratio in the flow direction stretching, the temperature and stretching ratio in the width direction stretching, and the temperature of the heat treatment during film production.
[0125] The maximum strain of the orientation axis can be measured as follows. When the film shape is in the form of a roll, a rectangular film with a length of 1000 mm in the mechanical direction and a full width in the width direction is cut from the roll optical film. Based on the central portion of the width direction of the film, a plurality of 100 mm square films are cut out at intervals of 300 mm in the width direction. The sides of the square film are parallel to the mechanical direction and the width direction, respectively. When the film shape is in the form of a sheet, a rectangle with the largest area inscribed in the sample shape is drawn, and a 100 mm square film with two sides shared with the vertices of the rectangle is cut out from the four vertices. For the cut sample film, the molecular orientation direction (orientation axis) of each is determined using a microwave transmission type molecular orientation meter. The width direction of the film is set to 0 °, and when the molecular orientation angle is less than 45 ° based on the width direction, the difference with 0 ° is obtained, and when it is greater than 45 °, the difference with 90 ° is obtained. The molecular orientation angle with the largest absolute value is taken as the maximum value, and it is taken as the maximum strain of the orientation axis. As a microwave transmission type molecular orientation meter, a molecular orientation meter (MOA-2001A) manufactured by Kanzaki Paper Industries, Ltd. was used.
[0126] (Total Light Transmittance and Haze)
[0127] The total light transmittance of the optical film may be 70% or more, 75% or more, 80% or more, 85% or more, or 90% or more. The higher the total light transmittance of the optical film, the more preferred it is, and it may be 99% or less, 98% or less, or 95% or less. The total light transmittance is measured in accordance with JIS K7361-1:1997.
[0128] The haze of the optical film may be 3.0% or less, 2.5% or less, 2.0% or less, 1.5% or less, or 1.0% or less. The lower the haze of the optical film, the more preferred it is, and it may be 0.1% or more, 0.2% or more, or 0.3% or more. The haze is measured in accordance with JIS K7136:2000.
[0129] (Martens hardness)
[0130] The Martens hardness of at least one surface of the optical film may be 110 N / mm 2 Above 170N / mm 2 Below. Martens hardness is 110N / mm 2 The above optical films have high hardness, excellent scratch resistance and wear resistance. Martens hardness is 170N / mm 2 The following optical films are excellent in foldability. The Martens hardness can be adjusted by aligning the molecular orientation by stretching the film.
[0131] The Martens hardness of at least one surface of the optical film may be 115 N / mm 2 Above, can be 120N / mm 2 Above, can be 125N / mm 2 Above, can be 130N / mm 2 Above, can be 135N / mm 2 Above, 140N / mm is also possible 2 The Martens hardness of at least one surface of the optical film may be 165 N / mm 2 Below, 160N / mm is also possible 2 the following.
[0132] In the first embodiment, at least one of the first and second surfaces of the optical film preferably has the above-mentioned Martens hardness, and more preferably both the first and second surfaces have the above-mentioned Martens hardness. In the first embodiment, the Martens hardness refers to the average value of 20 measured values after removing the minimum and maximum values from the 22 measured values. In the first embodiment, the measurement site is selected from any site without defects such as damage and dirt.
[0133] The standard deviation 3σ of the Martens hardness of at least one surface of the optical film is preferably 45 N / mm 2 Below. The standard deviation of Martens hardness is 45N / mm 2 The following optical films have excellent foldability. From the perspective of foldability, the standard deviation can be 40 N / mm 2 Below, can be 35N / mm 2 Below, can be 30N / mm2 Below, can be 25N / mm 2 Below, 20N / mm is also possible 2 The smaller the standard deviation, the better, and it can be 1N / mm 2 Above, 5N / mm is also possible 2 The standard deviation can be adjusted by the temperature at the time of forming the optical film.
[0134] In the first embodiment, at least one of the first and second surfaces of the optical film preferably has the standard deviation of the Martens hardness, and more preferably both the first and second surfaces have the standard deviation of the Martens hardness. In the first embodiment, the standard deviation of the Martens hardness refers to the standard deviation of the measured values at 20 locations.
[0135] In this specification, Martens hardness is measured by nanoindentation. First, the indentation depth h (nm) corresponding to the indentation load F (N) is continuously measured to create a load-removal curve. The "load-removal curve" is sometimes also called the "load-displacement curve". The "maximum indentation depth hmax" is analyzed based on the load curve, and then the projected area AC (mm) at hmax is analyzed. 2 The projection area AC refers to the area where the indenter contacts the optical film. The Martens hardness HM can be calculated as the value obtained by dividing the maximum indentation load Pmax (N) by the projection area AC (the following formula (1)).
[0136] HM=Pmax / AC···(1)
[0137] Here, AC is the contact projection area corrected for the curvature of the indenter tip in the apparatus using a standard method.
[0138] The Martens hardness can be measured using an apparatus capable of performing a nanoindentation method. As such an apparatus, a "PICODENTOR HM500" manufactured by Fischer Instruments can be used.
[0139] The Martens hardness is measured under the following conditions.
[0140] <Measurement conditions>
[0141] ·Indenter used: Vickers indenter (diamond-shaped quadrangular hammer, model: VV005, Fischer Instruments)
[0142] · Pressing condition: Maximum load
[0143] Maximum pressing load: 20mN
[0144] Load application time: 10 seconds
[0145] Holding time: 5 seconds at maximum press load
[0146] Load unloading time: 10 seconds
[0147] · Sample setting table: Suction table (the suction table uses SMC model "SP2130-AD")
[0148] (Elastic deformation power)
[0149] The elastic deformation power of at least one surface of the optical film may be 60% or more and 70% or less. An optical film having an elastic deformation power of 60% or more has excellent foldability. An optical film having an elastic deformation power of 70% or less has excellent hardness.
[0150] The elastic deformation power can be calculated by calculating the areas of the indentation work region, elastic work region, and plastic work region from the "load-removal curve" prepared when measuring the Martens hardness, and then using the following formula.
[0151] Elastic deformation power [%] = (area of elastic work region / area of compression work region) × 100
[0152] In this specification, the elastic deformation power refers to the average value of 20 measurement values excluding the minimum and maximum values from the 22 measurement values. In this specification, the measurement site is selected from any site without defects such as damage and dirt.
[0153] The standard deviation 3σ of the elastic deformation power is preferably 10% or less. An optical film having a standard deviation of the elastic deformation power of 10% or less has excellent hardness. The smaller the standard deviation, the more preferred it is, and it can be 1% or more, or 2% or more. The standard deviation can be adjusted by the temperature during film formation of the optical film.
[0154] In the first embodiment, it is preferred that at least one of the first and second surfaces of the optical film has the above-mentioned elastic deformation power, and it is more preferred that both the first and second surfaces have the above-mentioned elastic deformation power. In the first embodiment, it is preferred that at least one of the first and second surfaces of the optical film has the standard deviation of the above-mentioned elastic deformation power, and it is more preferred that both the first and second surfaces have the standard deviation of the above-mentioned elastic deformation power.
[0155] (Heat shrinkage)
[0156] The heat shrinkage ratio 1 in the fast axis direction of the optical film may be 5.0% or less, 3.0% or less, or 2.5% or less. The heat shrinkage ratio 1 may be 0% or more, 0.5% or more, or 1.0% or more.
[0157] The thermal shrinkage ratio 2 in the slow axis direction of the optical film may be 1.0% or less, 0.5% or less, or 0.3% or less. The thermal shrinkage ratio 2 may be 0% or more, 0.1% or more, or 0.2% or more.
[0158] The fast axis direction of the optical film is usually equivalent to the machine direction (MD) of the optical film. The slow axis direction of the optical film is usually equivalent to the width direction (TD) of the optical film. As described above, the slow axis direction and the fast axis direction can be measured using the trade name "RETS-100" manufactured by Otsuka Electronics Co., Ltd. at a measurement angle of 0°.
[0159] The ratio (heat shrinkage 1 / heat shrinkage 2) may be 6.0 or more, 6.1 or more, or 6.2 or more. Such an optical film has good interlayer adhesion when the functional layers are stacked. The ratio (heat shrinkage 1 / heat shrinkage 2) may be 15.0 or less, 13.0 or less, 11.0 or less, or 9.0 or less.
[0160] The heat shrinkage ratio of the optical film, and the tensile strength ratio and elongation ratio described below can be controlled, for example, by the ratio of the stretching ratios in each direction. Specifically, the larger the stretching ratio in one direction is compared to the stretching ratio in another direction, the larger the above ratio is.
[0161] The heat shrinkage is measured at 150°C for 30 minutes, specifically as follows. A film with a length of 250 mm and a width of 10 mm in the direction orthogonal to the axial direction (fast axis direction or slow axis direction) of the film to be measured is accurately cut out in a strip shape. Marks are marked at 25 mm from both ends of the long side of the strip (interval: 200 mm), and the interval A (mm) of the above marks is read under a constant tension of 5 gf / 10 mm. Then, after heat treatment in an oven at 150°C for 30 minutes under no load, the interval B (mm) of the above marks is read under a constant tension of 5 gf / 10 mm. The interval of the above marks is read using a stainless steel ruler with a scale of 0.5 mm, and the average of the three measured values is calculated, and the second decimal place is rounded off. The heat shrinkage of the film in the mechanical direction and the width direction is calculated by the following formula.
[0162] Thermal shrinkage at 150°C (%) = (A-B) / A×100
[0163] (Tensile Strength)
[0164] The tensile strength 1 in the fast axis direction of the optical film may be 95 MPa or less, 90 MPa or less, or 85 MPa or less. The tensile strength 1 may be 55 MPa or more, 60 MPa or more, or 65 MPa or more.
[0165] The tensile strength 2 in the slow axis direction of the optical film may be 450 MPa or less, 400 MPa or less, or 350 MPa or less. The tensile strength 2 may be 200 MPa or more, 250 MPa or more, or 300 MPa or more.
[0166] The ratio (tensile strength 2 / tensile strength 1) may be 2.0 or more, 2.2 or more, or 2.4 or more. Such an optical film has good interlayer adhesion when the functional layers are stacked. The ratio (tensile strength 2 / tensile strength 1) may be 5.0 or less, or 4.5 or less.
[0167] (Elongation)
[0168] The elongation 1 in the fast axis direction of the optical film may be 10.0% or less, 7.0% or less, or 5.0% or less. The elongation 1 may be 3.0% or more, 3.5% or more, or 4.0% or more.
[0169] The elongation 2 in the slow axis direction of the optical film may be 95.0% or less, 85.0% or less, or 80.0% or less. The elongation 2 may be 55.0% or more, 60.0% or more, or 65.0% or more.
[0170] The ratio (elongation 2 / elongation 1) may be 6.5 or more, 6.8 or more, or 7.0 or more. Such an optical film has good interlayer adhesion when the functional layers are stacked. The ratio (elongation 2 / elongation 1) may be 20.0 or less, 15.0 or less, or 10.0 or less.
[0171] The tensile strength and elongation were measured in accordance with JIS K7127:1999 under the conditions of a test speed of 25 mm / min and a temperature of 23°C. The elongation (elongation at break) is expressed by elongation (%) = 100 × (L-Lo) / Lo, where Lo is the length of the test piece before the test and L is the length of the test piece at break.
[0172] In the present specification, the heat shrinkage rate, the tensile strength, and the elongation rate refer to the average values of the measured values of 10 different samples of the optical film.
[0173] (Corrosion rate)
[0174] When the average of the corrosion rates of the optical film to a depth of 20 μm from the surface of the optical film is defined as E0-20, E0-20 may be 0.80 μm / g or more. Such an optical film has a good pencil hardness.
[0175] In this specification, E0-20 is measured under the following measurement conditions.
[0176] <Measurement conditions>
[0177] A test solution prepared by mixing pure water, a dispersant, and spherical silica with an average particle size within ±8% based on 4.2 μm at a mass ratio of (pure water: dispersant: spherical silica) = 968:2:30 is placed in a container. "Average particle size within ±8% based on 4.2 μm" means that the average particle size is 3.864 μm or more and 4.536 μm or less.
[0178] The test liquid in the container is sent to the nozzle. Compressed air is sent to the nozzle to accelerate the test liquid in the nozzle, and a predetermined amount of the test liquid is sprayed perpendicularly to the optical film from the spray hole at the front end of the nozzle, so that the spherical silica in the test liquid collides with the optical film. The cross-sectional shape of the nozzle is a 1mm×1mm square, and the distance between the spray hole and the optical film is 4mm. In addition, the flow rate of the test liquid and compressed air supplied to the nozzle, the pressure of the compressed air, and the pressure of the test liquid in the nozzle are predetermined values adjusted by the calibration described later.
[0179] After a predetermined amount of the test liquid is sprayed, the spraying of the test liquid is temporarily stopped. After the spraying of the test liquid is temporarily stopped, the cross-sectional profile of the portion of the optical film where the spherical silica in the test liquid collides is measured.
[0180] The three steps of ejecting a predetermined amount of the test liquid from the ejection port, temporarily stopping the ejection of the test liquid after ejecting the predetermined amount of the test liquid, and measuring the cross-sectional profile after temporarily stopping the ejection of the test liquid are performed as one cycle until the depth of the cross-sectional profile exceeds 20 μm. Then, the corrosion rate (μm / g) of the optical film is calculated in each cycle until the depth of the cross-sectional profile reaches 20 μm. The corrosion rate of the optical film in each cycle until the depth of the cross-sectional profile reaches 20 μm is averaged to calculate E0-20.
[0181] <Correction>
[0182] Before determining the above corrosion rates, a calibration was performed.
[0183] The test liquid is stored in the container. The test liquid in the container is sent to the nozzle. Compressed air is sent into the nozzle to accelerate the test liquid in the nozzle, and any amount of the test liquid is sprayed vertically from the spray hole at the front end of the nozzle relative to the acrylic plate with a thickness of 2 mm, so that the spherical silica in the test liquid collides with the acrylic plate. The cross-sectional shape of the nozzle is a 1 mm × 1 mm square, and the distance between the spray hole and the acrylic plate is 4 mm.
[0184] After spraying an arbitrary amount of the test liquid, the spraying of the test liquid is temporarily stopped. After the spraying of the test liquid is temporarily stopped, the cross-sectional profile of the acrylic plate is measured at the location where the spherical silica in the test liquid collides. The corrosion rate (μm / g) of the acrylic plate is calculated by dividing the depth (μm) of the cross-sectional profile by the arbitrary amount (g).
[0185] The corrosion rate of the acrylic plate is set to be within the range of ±5% based on 1.88 (μm / g) as the qualified condition, and the flow rate of the test liquid and compressed air, the pressure of the compressed air, and the pressure of the test liquid in the nozzle are adjusted and calibrated so that the corrosion rate of the acrylic plate is within the above range. "Corrosion rate is within ±5% based on 1.88 (μm / g)" means that the corrosion rate is above 1.786 (μm / g) and below 1.974 (μm / g).
[0186] The test liquid used in the calibration is the same as the test liquid used in the measurement conditions to be implemented later. The measurement device used in the calibration is the same as the measurement device used in the measurement conditions to be implemented later. The difference between the calibration and the measurement conditions to be implemented later is that, for example, an acrylic plate with a thickness of 2 mm as a standard sample is used as a sample in the calibration, while an optical film is used as a sample in the measurement conditions.
[0187] The acrylic plate with a thickness of 2 mm as the standard sample is preferably a polymethyl methacrylate plate (PMMA plate). When the average corrosion rate of the acrylic plate with a thickness of 2 mm as the standard sample measured under the following measurement condition A is defined as AcE, AcE is preferably 1.786 μm / g or more and 1.974 μm / g or less. As the spherical silica in the following measurement condition A, the model "MSE-BS-5-3" specified by Palmeso Co., Ltd. can be cited. As the spherical silica that meets the model "MSE-BS-5-3" specified by Palmeso Co., Ltd., the part number "BS5-3" of Potters Ballotini Co., Ltd. can be cited.
[0188] <Measurement Condition A>
[0189] A test liquid consisting of pure water, a dispersant, and spherical silica with an average particle size of 4.2 μm within ±8% is placed in a container at a mass ratio of 968:2:30. The test liquid in the container is sent to the nozzle. Compressed air is sent to the nozzle to accelerate the test liquid in the nozzle, and a specified amount of the test liquid is sprayed vertically from the spray hole at the front end of the nozzle relative to the acrylic plate, so that the spherical silica in the test liquid collides with the acrylic plate. The cross-sectional shape of the nozzle is a 1 mm × 1 mm square, and the distance between the spray hole and the acrylic plate is 4 mm. In addition, regarding the flow rates of the test liquid and compressed air supplied to the nozzle, the pressure of the compressed air, and the pressure of the test liquid in the nozzle, the flow rate of the test liquid is not less than 100 ml / minute and not more than 150 ml / minute, the flow rate of the compressed air is not less than 4.96 L / minute and not more than 7.44 L / minute, the pressure of the compressed air is not less than 0.184 MPa and not more than 0.277 MPa, and the pressure of the test liquid in the nozzle is not less than 0.169 MPa and not more than 0.254 MPa.
[0190] After spraying 4g of the test liquid, the spraying of the test liquid was temporarily stopped. After the spraying of the test liquid was temporarily stopped, the cross-sectional profile of the acrylic plate was measured at the location where the spherical silica in the test liquid collided. The corrosion rate of the acrylic plate, AcE (unit: "μm / g"), was calculated by dividing the depth of the cross-sectional profile (μm) by the spraying amount of the test liquid (4g).
[0191] Below, citing Figure 2 , the measurement conditions of the corrosion rate and the technical significance of the corrosion rate calculated based on the measurement conditions are explained. Figure 2 As such a corrosion rate measuring device, there is an example of an MSE test device of Palmeso Co., Ltd., part number "MSE-A203".
[0192] In the measurement conditions of the corrosion rate disclosed in the present invention, first, a test liquid prepared by mixing pure water, a dispersant, and spherical silica having an average particle size within ±8% based on 4.2 μm in a mass ratio of 968:2:30 is placed in a container (11). In the container (11), the test liquid is preferably stirred. There is no particular limitation on the dispersant as long as it can disperse the spherical silica. As a dispersant, the product name "DEMOL N (Demol N)" of Wako Pure Chemical Industries, Ltd. can be cited.
[0193] In the measurement conditions of the corrosion rate in this specification, the "average particle size of spherical silica" is measured as the volume average value d50 in the particle size distribution measurement by the laser diffraction method (so-called "median particle size").
[0194] Spherical silica is preferably such that, in the result of the particle size distribution measurement, when the frequency of the particle size with the largest frequency display is standardized to 100, the width of the particle size with a frequency display of 50 is within ±10% based on 4.2 μm. The “width of the particle size with a frequency display of 50” is represented by “XY (μm)” when “the particle size with a frequency display of 50 and located in the positive direction of the particle size with a frequency display of 100 is defined as X” and “the particle size with a frequency display of 50 and located in the negative direction of the particle size with a frequency display of 100 is defined as Y”. It should be noted that in this specification, the “width of the particle size with a frequency display of 50” is sometimes referred to as the “full width at half maximum of the particle size distribution”.
[0195] As spherical silica having an average particle size within ±8% of 4.2 μm, there is the model “MSE-BS-5-3” designated by Palmeso Co., Ltd. As spherical silica conforming to the model “MSE-BS-5-3” designated by Palmeso Co., Ltd., there is the part number “BS5-3” of Potters Ballotini.
[0196] The test liquid in the container is fed into the nozzle (51). The test liquid can be fed to the nozzle via the test liquid piping (21). A flow meter (31) for measuring the flow rate of the test liquid is preferably provided between the container (11) and the nozzle (51). The flow rate of the test liquid is a value adjusted by the above-mentioned calibration. Figure 2 In the invention, the nozzle (51) is arranged in a housing (52) constituting the injection portion (50).
[0197] Compressed air is delivered to the nozzle (51). The compressed air is delivered to the nozzle through the compressed air pipe (22). In the nozzle, the position where the compressed air is delivered is preferably more upstream than the position where the test liquid is delivered. The upstream side refers to the side away from the injection hole of the nozzle.
[0198] Before the compressed air reaches the nozzle (51), a flow meter (32) for measuring the flow rate of the compressed air and a pressure gauge (42) for measuring the pressure of the compressed air are preferably arranged. The compressed air can be supplied by an air compressor (not shown) or the like.
[0199] The flow rate and pressure of the compressed air are the values adjusted by the above-mentioned calibration.
[0200] When compressed air is delivered into the nozzle (51), the test liquid is accelerated while being mixed by the compressed air. Then, the accelerated test liquid is ejected from the ejection hole at the front end of the nozzle (51) and collides vertically with the optical film (70). The optical film is mainly abraded by the spherical silica particles in the test liquid.
[0201] A pressure gauge (41) for measuring the pressure of the test liquid in the nozzle is preferably disposed in the nozzle (51). The pressure gauge (41) is preferably located downstream of a position where compressed air is fed and a position where the test liquid is fed.
[0202] The pressure of the test fluid in the nozzle (51) is a value adjusted by the above-mentioned calibration.
[0203] The test liquid sprayed from the spray hole at the front end of the nozzle (51) is mixed with air and sprayed in a mist form. Therefore, the collision pressure of the spherical silica particles on the optical film can be reduced. As a result, the wear amount of the optical film caused by one spherical silica particle can be suppressed to a trace amount.
[0204] Figure 3 This is an image diagram showing a state in which an optical film (70) is worn by a test liquid containing pure water (A1) and spherical silica (A2) ejected from an ejection unit (50). Figure 3 In the figure, symbol A3 represents air, and symbol A4 represents the worn optical film.
[0205] Since the test liquid contains water with excellent cooling effect, it is possible to substantially eliminate the deformation and deterioration of the optical film caused by the heat during collision. In other words, it is possible to substantially eliminate abnormal wear of the optical film. Water also has the function of cleaning the surface of the worn optical film and achieving stable wear. Water has the function of accelerating the spherical silica particles or controlling the fluidity of the test liquid.
[0206] Since a large number of spherical silica particles collide with the optical film, the influence of subtle differences in physical properties of individual spherical silica particles can be eliminated.
[0207] Furthermore, the measurement conditions disclosed in the present invention determine the factors affecting the wear amount of the optical film by setting the flow rate of the test liquid supplied to the nozzle, the flow rate of the compressed air supplied to the nozzle, the pressure of the compressed air supplied to the nozzle, and the pressure of the test liquid in the nozzle to the values adjusted by the above calibration, and at the same time determining the cross-sectional shape of the nozzle to a 1mm×1mm square, and determining the distance between the injection hole and the optical film to 4mm. The above distance is Figure 2 The distance indicated by "d" refers to the vertical distance between the front end of the nozzle, i.e., the injection hole, and the optical film.
[0208] As is apparent from the above, the measurement conditions of the present disclosure can be said to be measurement conditions that can form statistically stable wear marks on the optical film.
[0209] The optical film (70) may be mounted on the sample mounting table (81) of the measuring device (90). The optical film (70) is preferably mounted on the sample mounting table (81) via a support (82) such as a stainless steel plate.
[0210] The test liquid sprayed onto the optical film (70) is preferably recovered by the receiver (12) and returned to the container (11) through the return pipe (23). A return pump (24) is preferably arranged between the receiver (12) and the return pipe (23).
[0211] The measurement conditions disclosed herein require that the spraying of the test liquid is temporarily stopped after a predetermined amount of the test liquid is sprayed, and that the cross-sectional profile of the portion of the optical film where the spherical silica in the test liquid collides is measured after the spraying of the test liquid is temporarily stopped.
[0212] The cross-sectional profile refers to the cross-sectional shape of the optical film worn by the test liquid. The optical film is mainly worn by the spherical silica particles in the test liquid. The cross-sectional profile can be measured by a cross-sectional profile acquisition unit (60) such as a stylus-type surface shape measuring device and a laser interference-type surface shape measuring device. The cross-sectional profile acquisition unit (60) is usually arranged at a position separated from the optical film (70) when the test liquid is sprayed. Therefore, it is preferred that at least one of the optical film (70) and the cross-sectional profile acquisition unit (60) is movable. In the MSE test device of Palmeso Co., Ltd., part number "MSE-A203", the cross-sectional profile measurement unit is a stylus-type.
[0213] In the measurement conditions disclosed herein, three steps of ejecting a specified amount of test liquid from an ejection port, temporarily stopping the ejection of the test liquid after ejecting the specified amount of test liquid, and measuring the cross-sectional profile after temporarily stopping the ejection of the test liquid are performed as a cycle until the depth of the cross-sectional profile exceeds 20 μm.
[0214] By performing the above operation, the corrosion rate of the optical film in each cycle can be measured, and further, the variation in the corrosion rate of the optical film can be calculated.
[0215] The above cycle can be continued even after the depth of the cross-sectional profile exceeds 20 μm, but it is preferably terminated when the depth of the cross-sectional profile exceeds 20 μm. In addition, the reason for measuring "from the surface of the optical film to a depth of 20 μm" is that the physical properties of the optical film are easily changed near the surface, and on the other hand, there is a tendency to be more stable toward the inside.
[0216] In this specification, the corrosion rate of each cycle can be calculated by dividing the depth (μm) of the cross-sectional profile in each cycle by the injection amount (g) of the test liquid in each cycle. The depth (μm) of the cross-sectional profile in each cycle is the depth of the deepest position of the cross-sectional profile in each cycle.
[0217] The amount of test liquid injected in each cycle is "fixed" in principle, but may vary slightly in each cycle. The amount of test liquid injected in each cycle is preferably 0.5 g or more, more preferably 1.0 g or more, and preferably 3.0 g or less, more preferably 2.0 g or less.
[0218] In the measurement conditions disclosed herein, the corrosion rate (μm / g) is calculated in each cycle until the depth of the cross-sectional profile reaches 20 μm. Then, the corrosion rates of each cycle until the depth of the cross-sectional profile reaches 20 μm are averaged to calculate E0-20 (the average corrosion rate from the surface of the optical film to a depth of 20 μm).
[0219] The above cycle was performed until the depth of the cross-sectional profile exceeded 20 μm, and the data of the cycle in which the depth of the cross-sectional profile exceeded 20 μm deviated from the data calculated for E0-20.
[0220] Generally, an optical film is easily damaged when it is soft, and is not easily damaged when it is hard. In addition, there is a tendency for the optical film to increase in strength when stretched. Specifically, there is a tendency for the pencil hardness of a uniaxially stretched optical film to be better than that of an unstretched optical film, and there is a tendency for the pencil hardness of a biaxially stretched optical film to be better than that of a uniaxially stretched optical film. However, even for a biaxially stretched optical film, the pencil hardness is sometimes insufficient.
[0221] The inventors have studied the corrosion rate as an indicator of the pencil hardness of the optical film. As described above, the optical film is easily damaged when it is soft and not easily damaged when it is hard, so it is believed that the pencil hardness can be improved when the corrosion rate is small. However, the inventors have found that, on the contrary, by increasing the corrosion rate (E0-20) to more than 0.80 μm / g, the pencil hardness of the optical film can be improved. In addition, the inventors have found that, for the corrosion rate of the optical film, the biaxially stretched optical film is more likely to show a large value than the uniaxially stretched optical film, and the quality of the pencil hardness in the biaxially stretched optical film can be judged by the corrosion rate.
[0222] The reason why the corrosion rate of the optical film is related to the pencil hardness can be considered as follows. As described above, in the measurement conditions of the present disclosure, the test solution containing water and spherical silica is mixed with air and sprayed in a mist form. Therefore, the collision pressure of the spherical silica particles on the optical film is suppressed to be relatively low. Therefore, it is believed that when the optical film is soft, the stress when the spherical silica collides with the optical film is easily dispersed, so the optical film is not easy to wear and the corrosion rate becomes lower. On the other hand, it is believed that when the optical film is hard, the stress when the spherical silica collides with the optical film is difficult to disperse, so the optical film is easy to wear and the corrosion rate becomes higher.
[0223] In addition, it is believed that the difference in corrosion rate in the biaxially stretched optical film is caused by the difference in the elongation of the molecular chain and the difference in the orientation of the molecules. For example, in principle, the biaxially stretched optical film also has molecules that are elongated in the plane but are not fully elongated locally in the plane. In this way, it is believed that if the proportion of molecules that are not fully elongated locally in the plane increases, the biaxially stretched optical film will become locally soft and the corrosion rate will decrease. In addition, it is believed that even biaxially stretched optical films with the same in-plane phase difference will show different corrosion rates due to the difference in local molecular orientation.
[0224] In order to improve the pencil hardness of the optical film, E0-20 may be 0.80 μm / g or more, 0.85 μm / g or more, 0.90 μm / g or more, 0.95 μm / g or more, or 1.00 μm / g or more. In order to make the optical film less prone to cracking, E0-20 may be 3.00 μm / g or less, 2.50 μm / g or less, or 2.00 μm / g or less.
[0225] In the stretching in the flow direction, there is a tendency that the corrosion rate decreases when the stretching time is shortened, and the corrosion rate increases when the stretching time is prolonged. The reason for this is believed to be that if the stretching time is short, it is difficult for the molecules to be stretched uniformly in the surface of the optical film, while on the other hand, if the stretching time is long, the molecules are easily stretched uniformly in the surface of the optical film.
[0226] (Loss tangent (tanδ))
[0227] The peak temperature of the loss tangent (tan δ) in the optical film may be 90° C. to 160° C. Such an optical film has excellent processability when heated. The peak temperature of tan δ may be 92° C. to 94° C. to 96° C. to 100° C. The peak temperature of tan δ may be 160° C. to 155° C. to 150° C. to 150° C.
[0228] The peak top temperature of tan δ generally corresponds to the glass transition temperature of the polyester contained in the optical film. Therefore, by adjusting the glass transition temperature of the polyester, the peak top temperature of tan δ can be adjusted to the above range.
[0229] Tan δ is measured using a dynamic viscoelasticity measuring device (DMA). The temperature at which tan δ reaches a maximum is defined as the peak temperature of tan δ of the optical film. When two or more maximum values of tan δ are observed, the value on the lowest temperature side is adopted. The measurement conditions are as follows. Measuring device: Rheogel-E4000 (manufactured by UBM Co., Ltd.), measurement sample: width 5mm×length 25mm, frequency: 10Hz, distance between chucks: 10mm, measurement temperature range: 25℃~250℃, heating rate: 2℃ / min.
[0230] (Crystallinity)
[0231] The crystallinity of the optical film may be 85% or less. Such an optical film has good interlayer adhesion when the functional layers are stacked. From the perspective of the mechanical strength of the optical film, the crystallinity of the optical film may be 60% or more, 65% or more, or 70% or more.
[0232] The crystallinity of the optical film is a value measured by an X-ray diffraction method.
[0233] The measurement conditions and calculation method of the crystallinity are as follows.
[0234] (Measurement conditions)
[0235] Determination method: 2θ / θ determination
[0236] Installation: Rigaku Manufacturing Smart Lab 9kW
[0237] X-ray source: Cu-Kα45kV-200mA
[0238] Measuring range: 10~50deg
[0239] Step size: 0.020deg
[0240] Measuring time: 4.0deg / min
[0241] (Calculation method)
[0242] The crystallinity was calculated based on the peak shape fitting method from the formula: crystallinity (%) = peak area of crystalline substance / (peak area of crystalline substance + peak area of amorphous substance) × 100.
[0243] The crystallinity of the optical film can be controlled, for example, by the stretching ratio and the stretching temperature. Specifically, the greater the stretching ratio, the greater the crystallinity. The smaller the stretching ratio, the smaller the crystallinity.
[0244] (Gas barrier properties)
[0245] In the first embodiment, the optical film has excellent gas barrier properties.
[0246] The water vapor transmission rate of the optical film measured in accordance with JIS K7129-2:2019 at a temperature of 40°C and a humidity of 90% RH can be 20 g / (m 2 ·24hr) or less, can be 15g / (m 2 ·24hr) or less, or 10g / (m 2 The lower the water vapor permeability of the optical film, the better, and it can be 2g / (m 2 ·24hr) or more, or 3g / (m 2 The water vapor transmission rate can be measured using a water vapor transmission rate measuring device ("PERMATRAN" manufactured by Modern Controls).
[0247] The oxygen permeability of the optical film measured in accordance with JIS K7126-2:2006 at a temperature of 25°C and a humidity of 50% RH may be 100 cc / (m 2 ·24hr·atm) or less, can be 80cc / (m 2 ·24hr·atm) or less, or 50cc / (m 2 The oxygen permeability of the optical film is preferably as low as possible, and may be 5cc / (m 2 ·24hr·atm) or more, or 7cc / (m 2 The oxygen permeability can be measured using an oxygen permeability measuring device ("OX-TRAN 10 / 50A") manufactured by Modern Controls.
[0248] The optical film of the present disclosure is suitable as a film used in an image display device, specifically, as a base material for various functional films such as a hard coat film, an antiglare film, an antireflection film, an antifouling film, an antistatic film, and a polarizing element protective film.
[0249] <Adhesive layer>
[0250] The optical film of the present disclosure may be an easily adhesive film including a polyester film and an easily adhesive layer provided on the polyester film. The easily adhesive layer may be provided on only one of the first and second surfaces of the polyester film, or may be provided on both the first and second surfaces.
[0251] Figure 4 This is a cross-sectional view showing an embodiment of the easily adhesive film 1 of the present disclosure. Figure 4 The easily adhesive film 1 includes a polyester film 4 and an easily adhesive layer 6 in this order. The easily adhesive layer 6 is provided on the first surface 4a of the polyester film 4.
[0252] By providing the easy-adhesion layer on the polyester film, the adhesion between the layers of the optical layered body including the polyester film, the easy-adhesion layer, and the functional layer in this order can be improved.
[0253] As the resin constituting the easy bonding layer, thermoplastic resins such as polyester, polyurethane and (meth) acrylic resin and thermosetting resins can be enumerated, preferably thermoplastic resins. Among thermoplastic resins, preferably polyester and polyurethane, more preferably resins comprising these two components of polyester component and polyurethane component. These resins easily reduce the refractive index difference between polyester film and easy bonding layer.
[0254] The above-mentioned polyurethane component is easy to make the adhesion good, but it is sometimes difficult to enhance the coating strength. Therefore, the resin constituting the easy-adhesion layer preferably contains two components, a polyester component and a polyurethane component. However, when the polyurethane component is too much relative to the polyester component, phase separation is likely to occur. Therefore, the mass ratio of the resin containing the two components of the polyester component and the polyurethane component (polyester component: polyurethane component) can be 95:5 to 60:40, or 90:10 to 60:40.
[0255] The resin constituting the easy-adhesion layer may be a resin derived from biomass materials, a resin derived from fossil fuels, or a mixed resin of a resin derived from biomass materials and a resin derived from fossil fuels. For example, the thermoplastic resins such as the polyester, polyurethane, and (meth) acrylic resin, and the thermosetting resin may be a resin derived from biomass materials, a resin derived from fossil fuels, or a mixed resin of a resin derived from biomass materials and a resin derived from fossil fuels.
[0256] The easy-adhesive layer containing a resin derived from a biomass material has a high environmental contribution, and has a high affinity with a polyester film containing a biomass polyester and a high ability to follow the shape of the film, so an optical film having such an easy-adhesive layer has excellent processability. An optical film having an easy-adhesive layer containing a resin derived from a fossil fuel has excellent adhesion durability in a high temperature and high humidity environment.
[0257] In the first embodiment, the biomass degree of the easy-adhesion layer may be 10% or more, 12% or more, 15% or more, or 18% or more. In the first embodiment, the biomass degree of the easy-adhesion layer may be 98% or less, 90% or less, 80% or less, 70% or less, 60% or less, or 50% or less. By determining the biomass degree of the resin constituting the easy-adhesion layer and determining it as a raw material, the biomass degree of the easy-adhesion layer can be predetermined, and the quality of the optical film can also be controlled.
[0258] The easily adhesive layer may contain one or more of the above-mentioned resins.
[0259] The content of the resin in the easy-adhesion layer may exceed 50% by mass, may be 60% by mass or more, may be 70% by mass or more, may be 80% by mass or more, may be 90% by mass or more, or may be 95% by mass or more.
[0260] The number average molecular weight of the resin constituting the easy-adhesion layer may be 10,000 or more, or 15,000 or more. The number average molecular weight of the resin may be 100,000 or less, or 60,000 or less. Such a resin can easily suppress the cohesive failure of the easy-adhesion layer. In this specification, the number average molecular weight refers to the polystyrene conversion value measured by gel permeation chromatography according to JIS K7252-1:2016.
[0261] The glass transition temperature of the resin constituting the easy-adhesion layer may be 30° C. or higher, 50° C. or higher, or 70° C. or higher. The glass transition temperature of the resin may be 120° C. or lower, 110° C. or lower, or 90° C. or lower. The glass transition temperature is a midpoint glass transition temperature obtained by differential scanning calorimetry (DSC) in accordance with JIS K7121:2012.
[0262] If the glass transition temperature of the resin constituting the easy-adhesive layer is 30°C or higher, it is easy to suppress the flow of the easy-adhesive layer due to the heat during the process, thereby generating internal stress. As the heat during the process, for example, heat in the drying process of the functional layer coating liquid, heat generated by heating when the optical layered body is attached to the polarizing element, etc. can be cited. If the glass transition temperature of the resin constituting the easy-adhesive layer is 120°C or lower, it is easy to suppress the stress caused by the difference in thermal behavior between the easy-adhesive layer and the polyester film due to the heat during the process, so it is possible to suppress the generation of cracks in the easy-adhesive layer due to stress.
[0263] The easy-adhesive layer may contain additives such as a refractive index modifier, a dye, a pigment, a leveling agent, an ultraviolet absorber, an antioxidant, and a light stabilizer, and a cross-linking agent for adjusting hardness or viscosity. The easy-adhesive layer may contain one or more of these components. As the cross-linking agent, for example, xylylene diisocyanate cross-linking agents, isophorone diisocyanate cross-linking agents, hexamethylene diisocyanate cross-linking agents, and ionizing radiation curing type multifunctional monomers may be cited.
[0264] The easy-adhesive layer can be formed by an online coating method for forming the easy-adhesive layer during the film-forming of the polyester film, or can be formed by an offline coating method for forming the easy-adhesive layer after the film-forming of the polyester film. In the online coating method and the offline coating method, it is preferred to use an easy-adhesive layer coating liquid containing the components constituting the easy-adhesive layer. For example, the easy-adhesive layer coating liquid is applied to the polyester film by a general coating method and dried, thereby forming the easy-adhesive layer.
[0265] The direction of the drying air during the formation of the adhesive layer is preferably opposite to the conveying direction of the polyester film. If the direction of the drying air is opposite to the conveying direction of the polyester film, the drying temperature will not be excessively increased, and the drying time of the adhesive layer coating liquid can be shortened.
[0266] The drying time of the easy-adhesive layer coating solution can be less than 120 seconds, or less than 90 seconds. The drying time can be more than 15 seconds, or more than 20 seconds. The drying time can be adjusted by drying temperature and drying wind speed. If the drying time is less than 120 seconds, the composition constituting the easy-adhesive layer can be suppressed to separate. If the drying time is too short, the coating surface is rough and the optical characteristics are reduced sometimes.
[0267] The drying temperature of the coating liquid for the easy adhesion layer may be 50° C. or more, or 60° C. or more. The drying temperature may be 200° C. or less, or 150° C. or less. By setting the drying temperature to 50° C. or more, the drying time of the coating liquid for the easy adhesion layer can be shortened, thereby suppressing the phase separation of the components constituting the easy adhesion layer. By setting the drying temperature to 200° C. or less, the thermal decomposition of the components constituting the easy adhesion layer can be suppressed.
[0268] In order to dissolve or disperse the components constituting the easy-adhesive layer or adjust the viscosity, the coating liquid for the easy-adhesive layer preferably contains an organic solvent. As the organic solvent, for example, ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone and cyclohexanone, ethers such as dioxane and tetrahydrofuran, aliphatic hydrocarbons such as hexane and heptane, alicyclic hydrocarbons such as cyclohexane, aromatic hydrocarbons such as toluene and xylene, halogenated carbons such as methylene chloride and dichloroethane, esters such as methyl acetate, ethyl acetate, propyl acetate and butyl acetate, alcohols such as isopropyl alcohol, butanol and cyclohexanol, cellosolves such as methyl cellosolve and ethyl cellosolve, glycol ethers such as propylene glycol monomethyl ether acetate, cellosolve acetate, sulfoxides such as dimethyl sulfoxide, and amides such as dimethylformamide and dimethylacetamide can be cited.
[0269] If the drying time of the organic solvent of the coating liquid for easy bonding layer is too long, the components constituting the easy bonding layer are easily separated. Therefore, the organic solvent in the coating liquid for easy bonding layer preferably includes a solvent with a fast evaporation rate. If the drying time of the organic solvent in the coating liquid for easy bonding layer is too short, the coating surface is easily roughened. Therefore, the organic solvent in the coating liquid for easy bonding layer preferably mixes an organic solvent with an extremely fast evaporation rate with an organic solvent with a moderately fast evaporation rate.
[0270] In the present specification, an organic solvent having an extremely high evaporation rate refers to an organic solvent having an evaporation rate of 280 or more when the evaporation rate of butyl acetate is set to 100. In the present specification, an organic solvent having a moderately high evaporation rate refers to an organic solvent having an evaporation rate of 150 or more and less than 280 when the evaporation rate of butyl acetate is set to 100.
[0271] The evaporation rate of the organic solvent with an extremely high evaporation rate may be 320 or more, or 340 or more. The evaporation rate may be 430 or less, or 400 or less. Examples of the organic solvent with an extremely high evaporation rate include methyl ethyl ketone with an evaporation rate of 370 and n-heptane with an evaporation rate of 362.
[0272] The evaporation rate of the organic solvent having a moderately high evaporation rate may be 170 or more, or 180 or more. The evaporation rate may be 250 or less, or 220 or less. Examples of the organic solvent having a moderately high evaporation rate include toluene having an evaporation rate of 200 and propyl acetate having an evaporation rate of 214.
[0273] The mass ratio of the organic solvent contained in the adhesive layer coating liquid (organic solvent with extremely high evaporation rate:organic solvent with moderately high evaporation rate) may be 50:50 to 90:10, or 70:30 to 85:15.
[0274] In order to easily suppress phase separation of the coating liquid for the easily adhesive layer, the solid content concentration of the coating liquid may be 2% by mass or more, or 4% by mass or more, or 30% by mass or less, or 15% by mass or less.
[0275] The thickness of the easy bonding layer may be 10 nm or more, 20 nm or more, or 50 nm or more. The thickness of the easy bonding layer may be 600 nm or less, 300 nm or less, or 200 nm or less. In order to suppress interference fringes, the thickness of the easy bonding layer is preferably small.
[0276] [Optical layered body]
[0277] As application examples of the optical film of the present invention, there can be cited, for example, an optical layered body comprising the optical film of the present invention and a functional layer disposed on the film, and an optical layered body comprising the easily adhesive film of the present invention and a functional layer disposed on the easily adhesive layer of the film. The functional layer can be disposed on one side of the optical film or on both sides.
[0278] In this specification, the optical layered body refers to a layered body that can transmit light.
[0279] Figure 5 It is a cross-sectional view showing an embodiment of the optical layered body 3 of the present disclosure. Figure 3 The optical layered body 3 includes a polyester film 4, an easily adhesive layer 6, and a functional layer 8 in this order. The easily adhesive layer 6 and the functional layer 8 are provided on the first surface 4a of the polyester film 4. The easily adhesive layer 6 may not be provided.
[0280] The total light transmittance of the optical layered body may be 50% or more, 60% or more, 70% or more, 80% or more, 85% or more, or 90% or more. The higher the total light transmittance of the optical layered body, the more preferred it is, and it may be 99% or less, 98% or less, or 95% or less. The total light transmittance is measured in accordance with JIS K7361-1:1997.
[0281] The haze of the optical layered body may be 10.0% or less, 7.0% or less, 5.0% or less, 4.0% or less, or 3.0% or less. The haze of the optical layered body may be 0.1% or more, 0.2% or more, or 0.3% or more. The haze is measured in accordance with JIS K7136:2000.
[0282] In the case of an optical layered body including a polyester film, an optional easy-adhesion layer, and a functional layer in this order, the total light transmittance and the haze were measured with the light incident surface being the polyester film surface.
[0283] <Functional layer>
[0284] The optical layered body of the present disclosure may include one functional layer or two or more functional layers. That is, the two or more functional layers may be laminated on the optical film, and in the first embodiment, may be laminated on the easily adhesive layer of the easily adhesive film.
[0285] In the present specification, the functional layer refers to a layer that imparts functions such as scratch resistance, anti-glare, anti-reflection, retardation, antifouling, antistatic and electrical conductivity to the optical layered body.
[0286] As the functional layer, for example, a hard coating layer, an anti-glare layer, an anti-reflection layer (a low refractive index layer, a high refractive index layer, and their stacked structure, etc.), a phase difference layer, an antifouling layer, an antistatic layer, and a conductive layer can be cited. The functional layer can have multiple functions in one layer. For example, the hard coating layer can further have at least one function selected from anti-glare, anti-reflection, phase difference, antifouling, antistatic, and conductivity.
[0287] Examples of the functional layer include the following (1) to (12).
[0288] (1) Hard coating
[0289] (2) Anti-glare layer
[0290] (3) Antifouling layer
[0291] (4) Multilayer structure having a hard coating layer and an anti-reflection layer in sequence
[0292] (5) A multilayer structure having a hard coat layer and an anti-glare layer in sequence
[0293] (6) A multilayer structure having a hard coating layer and an antifouling layer in sequence
[0294] (7) A multilayer structure having an anti-glare layer and an anti-reflection layer in sequence
[0295] (8) A multilayer structure having an anti-glare layer and an anti-fouling layer in sequence
[0296] (9) A multilayer structure having a hard coat layer, an anti-glare layer and an anti-reflection layer in this order
[0297] (10) Antistatic layer
[0298] (11) Conductive layer
[0299] (12) Phase difference layer
[0300] In the above (4) to (11), the left side indicates a layer located on the optical film side.
[0301] Among the one or more functional layers, the functional layer in contact with the optical film preferably contains a cured product of an ionizing radiation curable component. The functional layer in contact with the optical film is preferably a hard coat layer. By making the functional layer in contact with the optical film contain a cured product of an ionizing radiation curable component, the pencil hardness of the optical layered body can be easily increased.
[0302] The functional layer contains, for example, a binder resin and, if necessary, an additive. The functional layer may contain one or more binder resins. The functional layer may contain one or more additives.
[0303] The functional layer preferably contains a cured product of a curable component as a binder resin. The functional layer can be formed, for example, by a curable composition containing a curable component and an additive as required. The curable composition can further contain an organic solvent. Specific examples of organic solvents are exemplified as above as the coating liquid for the easy-adhesion layer. As the cured product of the curable component, for example, a cured product of a thermosetting component and a cured product of an ionizing radiation curable component can be cited, preferably a cured product of an ionizing radiation curable component.
[0304] The content ratio of the cured product of the curable component to the total binder resin of the functional layer may be 60 mass % or more, 70 mass % or more, 80 mass % or more, 90 mass % or more, or 95 mass % or more.
[0305] As the thermosetting component, for example, a thermosetting resin can be mentioned. As the thermosetting resin, for example, phenolic resin, urea resin, melamine resin, melamine-urea co-condensation resin, diallyl phthalate resin, aminoalkyd resin, epoxy resin, unsaturated (meth) acrylic resin, unsaturated polyurethane resin, unsaturated polyester resin and silicone resin can be mentioned. A curing agent can also be used together with the thermosetting component.
[0306] Examples of the ionizing radiation curable component include compounds having an ionizing radiation curable functional group. In the present specification, a compound having an ionizing radiation curable functional group may be referred to as an ionizing radiation curable compound.
[0307] Ionizing radiation refers to radiation with energy quanta that can polymerize or crosslink molecules among electromagnetic waves or charged particle beams. As ionizing radiation, ultraviolet rays or electron beams are generally used, and electromagnetic waves such as X-rays and gamma rays, and charged particle beams such as alpha rays and ion rays can also be used.
[0308] As the ionizing radiation curable functional group, for example, ethylenically unsaturated groups such as (meth)acryloyl, vinyl and allyl, as well as epoxy and oxetanyl groups can be cited. As the ionizing radiation curable compound, a compound having an ethylenically unsaturated group is preferred, a compound having two or more ethylenically unsaturated groups is more preferred, and a polyfunctional (meth)acrylate having two or more ethylenically unsaturated groups is further preferred.
[0309] In the present specification, (meth)acrylate means acrylate or methacrylate, (meth)acrylic acid means acrylic acid or methacrylic acid, and (meth)acryloyl means acryloyl or methacryloyl.
[0310] As the multifunctional (meth) acrylate, any one of a monomer and an oligomer can be used. As an ionizing radiation curable component, it is preferred to use at least a multifunctional (meth) acrylate oligomer. That is, the functional layer preferably contains a cured product of a multifunctional (meth) acrylate oligomer as a binder resin. The cured product of the multifunctional (meth) acrylate oligomer can make the surface hardness of the optical layered body good, and can suppress excessive curing shrinkage of the functional layer.
[0311] In order to make the surface hardness of the optical layered body and the balance of interlayer adhesion better, it is more preferred to use at least oligomers and monomers of multifunctional (meth) acrylate as ionizing radiation curable components. That is, the functional layer preferably contains a cured product of a multifunctional (meth) acrylate oligomer and a multifunctional (meth) acrylate monomer as a binder resin.
[0312] When an oligomer and a monomer are used as the multifunctional (meth)acrylate, the mass ratio of the oligomer to the monomer (oligomer:monomer) may be 5:95 to 95:5, 50:50 to 85:15, or 60:40 to 80:20.
[0313] Examples of the multifunctional (meth)acrylate oligomer include urethane (meth)acrylate, epoxy (meth)acrylate, polyester (meth)acrylate, and polyether (meth)acrylate. Urethane (meth)acrylate is obtained, for example, by the reaction of a polyol and a polyisocyanate with a hydroxyl-containing (meth)acrylate. The multifunctional (meth)acrylate oligomer may be a (meth)acrylate oligomer having at least two functions and at most twelve functions.
[0314] The weight average molecular weight of the multifunctional (meth)acrylate oligomer may be 250 or more, 300 or more, or 1,000 or more. The weight average molecular weight may be 5,000 or less, or 3,000 or less. If the weight average molecular weight of the oligomer is 250 or more, it is easy to suppress excessive curing shrinkage of the functional layer. If the weight average molecular weight of the oligomer is 5,000 or less, it is easy to suppress the reduction of surface hardness. In this specification, the weight average molecular weight refers to the polystyrene conversion value measured by gel permeation chromatography in accordance with JIS K7252-1:2016.
[0315] Examples of the polyfunctional (meth)acrylate monomer include bifunctional (meth)acrylate monomers and trifunctional or higher-functional (meth)acrylate monomers.
[0316] Examples of the bifunctional (meth)acrylate monomer include ethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polytetramethylene glycol di(meth)acrylate, isocyanuric acid di(meth)acrylate, bisphenol A tetraethoxy di(meth)acrylate, bisphenol A tetrapropoxy di(meth)acrylate, and 1,6-hexanediol di(meth)acrylate.
[0317] Examples of the trifunctional or higher-functional (meth)acrylate monomer include trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, dipentaerythritol tetra(meth)acrylate, and isocyanuric acid-modified tri(meth)acrylate.
[0318] A part of the molecular skeleton of the multifunctional (meth)acrylate monomer may be modified. For example, (meth)acrylate monomers modified with ethylene oxide, propylene oxide, caprolactone, isocyanuric acid, alkyl, cyclic alkyl, aromatic, bisphenol, etc. may be used.
[0319] As the ionizing radiation curable compound, a monofunctional (meth)acrylate can be further used. Thus, for example, the viscosity of the component can be adjusted. As the monofunctional (meth)acrylate, for example, methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate and isobornyl (meth)acrylate can be cited.
[0320] The functional layer may or may not contain a component derived from a biomass material.
[0321] In the first embodiment, the biomass degree of the functional layer is 10% or more, 15% or more, 20% or more, 25% or more, or 30% or more. The optical layered body having such a functional layer can reduce the environmental burden. The higher the biomass degree of the functional layer, the more preferred it is, for example, 98% or less, 90% or less, 80% or less, 70% or less, 60% or less, or 50% or less.
[0322] The functional layer having the above-mentioned biomass degree can be formed, for example, by using at least a (meth)acrylate having a group derived from a biomass material (hereinafter also referred to as "biomass (meth)acrylate"). For example, as the above-mentioned ionizing radiation curable compound, an ionizing radiation curable component containing at least a biomass (meth)acrylate is used. By determining the biomass degree of the raw material forming the functional layer and determining it as the raw material, the biomass degree of the functional layer can be predetermined, and the quality of the optical layered body can also be controlled.
[0323] Examples of the biomass (meth)acrylate include esters of biomass-derived alcohols and (meth)acrylic acid derived from biomass or non-biomass materials, that is, (meth)acrylates having an alkyl group derived from biomass.
[0324] Examples of alcohols derived from biomass materials include alcohols having a carbon number of 1 or more and 36 or less. Examples of alcohols derived from biomass materials include biomass ethanol and alcohols derived from plant raw materials such as palm oil, palm kernel oil, and coconut oil. When the carbon number of the alcohol derived from biomass materials is 3 or more, the alcohol may be linear or branched.
[0325] As alcohols derived from biomass materials, saturated aliphatic alcohols having 6 to 36 carbon atoms, saturated aliphatic alcohols having 12 to 20 carbon atoms, or saturated aliphatic alcohols having 16 to 18 carbon atoms can be used. As saturated aliphatic alcohols, linear aliphatic alcohols such as lauryl alcohol, cetyl alcohol, stearyl alcohol, cetearyl alcohol, and behenyl alcohol can be cited. As natural alcohols, alicyclic alcohols having 10 carbon atoms are also known, and isobornyl alcohol collected from trees can be cited. As natural alcohols, glycerol can also be cited.
[0326] Specific examples of biomass (meth)acrylates include lauryl (meth)acrylate, cetyl (meth)acrylate, stearyl (meth)acrylate, cetearyl (meth)acrylate, behenyl (meth)acrylate, isobornyl (meth)acrylate, and (poly)glycerol (meth)acrylate. In addition, soybean oil-modified epoxy (meth)acrylate and rosin-modified epoxy (meth)acrylate can also be mentioned.
[0327] Examples of the (poly)glycerol (meth)acrylate include glycerol (meth)acrylate, glycerol di(meth)acrylate, glycerol tri(meth)acrylate, diglycerol tri(meth)acrylate, and diglycerol tetra(meth)acrylate, and (poly)alkylene oxide-modified products thereof such as (poly)ethylene oxide-modified products and (poly)propylene oxide-modified products.
[0328] Examples of biomass (meth)acrylates include urethane (meth)acrylates, which are reaction products of polyols, polyisocyanates, and hydroxyl-containing (meth)acrylates, wherein at least one of the polyols, polyisocyanates, and hydroxyl-containing (meth)acrylates contains a component derived from a biomass material.
[0329] Examples of the polyol include polyester polyol, polyether polyol, and polycarbonate polyol. Examples of the polyol derived from biomass include polyols obtained by using a component derived from biomass as at least a part of the raw materials of these polyols.
[0330] Examples of the polyisocyanate include aromatic diisocyanate, aliphatic diisocyanate, and alicyclic diisocyanate. Examples of the aromatic diisocyanate include toluene-2,4-diisocyanate, 4-methoxy-1,3-phenylene diisocyanate, 4-isopropyl-1,3-phenylene diisocyanate, 4-chloro-1,3-phenylene diisocyanate, 4-butoxy-1,3-phenylene diisocyanate, 2,4-diisocyanate diphenyl ether, 4,4'-methylenebis(phenylene isocyanate) (MDI), diisocyanate, toluidine diisocyanate, diphenylmethane diisocyanate, xylylene diisocyanate (XDI), 1,5-naphthalene diisocyanate, benzidine diisocyanate, o-nitrobenzidine diisocyanate, and dibenzyl 4,4'-diisocyanate. Examples of the aliphatic diisocyanate include methylene diisocyanate, 1,4-tetramethylene diisocyanate, 1,6-hexamethylene diisocyanate, and 1,10-decamethylene diisocyanate. Examples of the alicyclic diisocyanate include 1,4-cyclohexyl diisocyanate, 4,4-methylenebis(cyclohexyl isocyanate), 1,5-tetrahydronaphthalene diisocyanate, isophorone diisocyanate, hydrogenated MDI, and hydrogenated XDI.
[0331] As polyisocyanates from biomass materials, for example, polyisocyanates obtained by converting a dicarboxylic acid from a plant into a terminal amino group by amidation and reduction, and then reacting with phosgene to convert the amino group into an isocyanate group can be cited. As diisocyanates from biomass materials, for example, dimer acid diisocyanate (DDI), octamethylene diisocyanate and decamethylene diisocyanate can be cited. Using amino acids from plants as raw materials, converting their amino groups into isocyanate groups can also obtain diisocyanates from plants. For example, lysine diisocyanate (LDI) is obtained by converting the amino group into an isocyanate group after methyl esterification of the carboxyl group of lysine. In addition, 1,5-pentamethylene diisocyanate is obtained by converting the amino group into an isocyanate group after decarboxylation of the carboxyl group of lysine.
[0332] Examples of the hydroxyl group-containing (meth)acrylate include compounds having one (meth)acryloyl group such as hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, and 2-hydroxy-3-phenoxypropyl (meth)acrylate, and compounds having two or more (meth)acryloyl groups such as glycerol di(meth)acrylate, pentaerythritol tri(meth)acrylate, ditrimethylolpropane tri(meth)acrylate, dipentaerythritol penta(meth)acrylate, and sorbitol penta(meth)acrylate.
[0333] In the first embodiment, the biomass degree of the biomass (meth)acrylate is 10% or more, 15% or more, 20% or more, 25% or more, or 30% or more. The higher the biomass degree of the biomass (meth)acrylate, the more preferred it is, for example, 98% or less, 90% or less, 80% or less, 70% or less, 60% or less, or 50% or less.
[0334] The ionizing radiation curable compound may be used alone or in combination of two or more.
[0335] In addition to the curable component, the curable composition may also contain a polymer in order to adjust the viscosity. Examples of the polymer include polymers having a weight average molecular weight of more than 5,000 and less than 200,000. The curable composition may further contain a resin from a plant. Examples of such resins include rosin-modified alkyd resins, rosin-modified maleic acid resins, rosin ester resins, rosin-modified phenolic resins, terpene resins, fatty acid-modified rosin resins, and plant oil-modified alkyd resins.
[0336] When the ionizing radiation curable compound is an ultraviolet curable compound, the curable composition preferably further contains a photopolymerization initiator and / or a photopolymerization accelerator. As the photopolymerization initiator, for example, acetophenones, benzophenones, α-hydroxyalkyl phenones, Michler's ketones, benzoin, benzoin dimethyl ether, benzoylbenzoate, α-acyl oxime esters, anthraquinones, halogenated ketones and thioxanthones can be cited. The photopolymerization accelerator can reduce the polymerization hindrance caused by air during curing and accelerate the curing speed. As the photopolymerization accelerator, for example, isopentyl p-dimethylaminobenzoate and ethyl p-dimethylaminobenzoate can be cited.
[0337] The functional layer may contain additives as necessary.
[0338] The additive can be appropriately selected from general materials according to the function assigned to the functional layer. As additives, for example, particles, refractive index adjustment materials, antifouling agents, antistatic agents, conductive fibers, leveling agents, ultraviolet absorbers, antioxidants and light stabilizers can be cited. In the case of imparting anti-glare properties to the functional layer, the functional layer preferably contains particles as additives. In the case of imparting anti-reflection properties to the functional layer, the functional layer preferably contains refractive index adjustment materials such as high refractive index materials and low refractive index materials as additives. In the case of imparting antifouling properties to the functional layer, the functional layer preferably contains antifouling agents as additives. In the case of imparting antistatic properties to the functional layer, the functional layer preferably contains antistatic agents as additives. In the case of imparting conductivity to the functional layer, the functional layer preferably contains conductive fibers as additives.
[0339] The functional layer may contain nanoparticles as additives.
[0340] The functional layer containing nanoparticles has, for example, a low refractive index and excellent hardness.
[0341] In the present disclosure, "nanoparticles" refer to particles with an average primary particle size of less than 1000 nm. Regarding the average primary particle size, 20 particles are selected from an image of a cross section of a functional layer taken using a scanning electron microscope (SEM) and the primary particle size is measured as the arithmetic mean of the primary particle sizes of the 20 particles. Here, the primary particle size is obtained by averaging the maximum value (long diameter) and the minimum value (short diameter) of the distance between two points on the periphery of the particle.
[0342] The nanoparticles may be inorganic particles, organic particles, or a mixture of these.
[0343] As inorganic particles, for example, silica particles can be cited. When silica particles are used as inorganic particles, the silica particles can be active silica particles. Active silica particles are silica particles that can form a cross-linked structure with an ionizing radiation curable component, and functional layers such as hard coatings can fully improve their hardness by containing active silica particles. The active silica particles preferably have reactive functional groups on the surface of the particles. As reactive functional groups, for example, the above-mentioned ionizing radiation curable functional groups can be cited.
[0344] Examples of organic particles include polymethyl methacrylate particles, polyacrylic acid-styrene copolymer particles, polystyrene particles, cross-linked polystyrene particles, polycarbonate particles, polyester resin particles, polyvinyl chloride particles, melamine resin particles, benzoguanamine-melamine formaldehyde particles, silicone particles, and fluorine resin particles. Inorganic components may be mixed into the organic particles.
[0345] Among the nanoparticles, silica particles are preferred.
[0346] The particles may be, for example, spherical, ellipsoidal, or irregular in shape. In addition, the particles may be hollow particles or non-hollow particles.
[0347] The average primary particle size of the nanoparticles can be selected according to the physical properties of the functional layer to be improved. Nanoparticles having different average primary particle sizes or nanoparticles having different shapes may be mixed and used.
[0348] In the first embodiment, the average primary particle size of the nanoparticles may be 5 nm to 100 nm. If the average primary particle size is 100 nm or less, large irregularities are not formed on the surface of a functional layer such as a hard coat layer, and the hardness of the functional layer can be increased.
[0349] In the first embodiment, the average primary particle size of the nanoparticles may be greater than 100 nm, greater than 100 nm and 600 nm or less, or greater than 100 nm and 350 nm or less. The functional layer containing nanoparticles having an average primary particle size greater than 100 nm has excellent anti-blocking properties.
[0350] The content of nanoparticles in functional layers such as hard coating layers can be 10 parts by mass or more, 15 parts by mass or more, 20 parts by mass or more, 60 parts by mass or less, 50 parts by mass or less, or 40 parts by mass or less relative to 100 parts by mass of the binder resin.
[0351] In the first embodiment, the anti-glare layer contains the above-mentioned binder resin and particles. The particles can be any of organic particles and inorganic particles. As organic particles, for example, particles composed of organic materials such as polymethyl methacrylate, polyacrylic acid-styrene copolymer, melamine resin, polycarbonate, polystyrene, polyvinyl chloride, benzoguanamine-melamine-formaldehyde condensate, silicone, fluorine resin and polyester resin can be cited. As inorganic particles, for example, particles composed of inorganic materials such as silicon dioxide, aluminum oxide, antimony, zirconium oxide and titanium dioxide can be cited. The content of the particles in the anti-glare layer is, for example, more than 1 mass part and less than 100 mass parts relative to 100 mass parts of the binder resin.
[0352] The anti-reflection layer in the functional layer may have a single-layer structure or a multi-layer structure. As the anti-reflection layer with a single layer, a low-refractive index layer may be cited. As the anti-reflection layer with a multi-layer structure, for example, a composition of two layers of a high-refractive index layer and a low-refractive index layer may be cited, and a composition of more than three layers may also be cited.
[0353] The refractive index of the low refractive index layer is, for example, 1.10 or more and 1.48 or less.
[0354] The thickness of the low refractive index layer is, for example, not less than 80 nm and not more than 120 nm.
[0355] In the first embodiment, the low refractive index layer contains the above-mentioned binder resin and hollow particles, and may also contain non-hollow particles. The material of the hollow particles and the non-hollow particles may be, for example, any one of inorganic compounds such as silicon dioxide and magnesium fluoride, and organic compounds, preferably silicon dioxide. Therefore, as hollow particles, hollow silica particles are preferred, and as non-hollow particles, non-hollow silica particles are preferred. The content of the hollow silica particles in the low refractive index layer is, for example, more than 100 mass parts and less than 400 mass parts relative to 100 mass parts of the binder resin. The content of the non-hollow silica particles in the low refractive index layer is, for example, more than 90 mass parts and less than 200 mass parts relative to 100 mass parts of the binder resin.
[0356] The refractive index of the high refractive index layer is, for example, 1.53 or more and 1.85 or less.
[0357] The thickness of the high refractive index layer is, for example, not less than 50 nm and not more than 200 nm.
[0358] In the first embodiment, the high refractive index layer contains the above-mentioned binder resin and high refractive index particles. Examples of the high refractive index particles include antimony pentoxide, zinc oxide, titanium oxide, cerium oxide, tin-doped indium oxide, antimony-doped tin oxide, yttrium oxide, and zirconium oxide. The content of the high refractive index particles in the high refractive index layer is, for example, 10 parts by mass or more and 500 parts by mass or less relative to 100 parts by mass of the binder resin.
[0359] In the first embodiment, the antifouling layer contains the above-mentioned binder resin and an antifouling agent. Examples of the antifouling agent include fluorine-based resins, silicone-based resins, and fluorine-silicone copolymer resins. The content of the antifouling agent in the antifouling layer is, for example, 5% by mass to 30% by mass of the total solid content of the antifouling layer.
[0360] In the first embodiment, the conductive layer contains a translucent resin as the above-mentioned binder resin and a plurality of conductive fibers arranged in the translucent resin. The conductive fiber refers to a substance having conductivity and a shape having a length that is sufficiently large compared to the thickness (e.g., diameter). For example, a substance having conductivity and a length that is approximately 5 times or more of the thickness is contained in the conductive fiber. The conductive layer refers to a layer that contains a translucent resin and a plurality of conductive fibers arranged in the translucent resin and can be conductive from the surface. The fiber diameter of the conductive fiber is, for example, more than 10nm and less than 200nm. The fiber length of the conductive fiber is, for example, more than 30μm, and the upper limit is not particularly limited. As conductive fibers, for example, conductive carbon fibers, metal fibers such as metal nanowires, metal-coated organic fibers, metal-coated inorganic fibers, and carbon nanotubes can be cited.
[0361] Most of the conductive fibers may be present on the side close to the optical film from the position of half the thickness of the conductive layer. In this case, other conductive fibers are deposited on the above-mentioned majority of conductive fibers, and thus also exist on the side close to the surface from the position of half the thickness of the conductive layer, and also exist on the surface of the conductive layer. As a result, the conductive layer can be electrically conductive from its surface, and the conductive fibers are in contact with each other in the thickness direction of the conductive layer.
[0362] The functional layer may include, for example, a phase difference layer, or an orientation layer and a phase difference layer provided on the orientation layer. The orientation layer facilitates the orientation of the liquid crystal compound in the phase difference layer when the phase difference layer-forming composition is applied, dried and cured to form the phase difference layer.
[0363] The phase difference layer contains a liquid crystal compound or has a structural unit derived from the liquid crystal compound.
[0364] As the liquid crystal compound, for example, rod-shaped liquid crystal compounds such as nematic liquid crystal compounds and smectic liquid crystal compounds, cholesteric liquid crystal compounds, and discotic liquid crystal compounds can be cited. In order to be able to be polymerized and fixed, the liquid crystal compound is preferably a polymerizable liquid crystal compound. In other words, the phase difference layer is preferably a cured product of a phase difference layer forming composition containing a polymerizable liquid crystal compound.
[0365] The polymerizable liquid crystal compound is a liquid crystal compound having a polymerizable group, and examples thereof include a monofunctional liquid crystal compound having one polymerizable group and a multifunctional liquid crystal compound having two or more polymerizable groups. Among these, a multifunctional liquid crystal compound is preferred, and a multifunctional liquid crystal compound having a number of polymerizable groups of 2 or more and 3 or less is more preferred, and a multifunctional liquid crystal compound having a number of polymerizable groups of 2 is further preferred. The polymerizable group is a group that can be polymerized by being irradiated with active energy rays such as ultraviolet rays and electron rays, and examples thereof include groups containing ethylenically unsaturated double bonds such as vinyl, acryloyl, and methacryloyl.
[0366] In the phase difference layer, the liquid crystal compound is preferably fixed in any one of a vertical orientation or a vertical alignment orientation, a horizontal orientation or a parallel orientation, a mixed orientation and an inclined orientation. For example, it is preferred that the long axis of the rod-shaped liquid crystal compound is substantially horizontal relative to the surface of the phase difference layer. For example, it is preferred that the disk surface of the disc-shaped liquid crystal compound is substantially vertical relative to the surface of the phase difference layer.
[0367] As the rod-like liquid crystal compound, for example, azomethines, azoxyls, cyanobiphenyls, cyanophenyl esters, benzoates, cyclohexanecarboxylic acid phenyl esters, cyanophenylcyclohexanes, cyano-substituted phenylpyrimidines, alkoxy-substituted phenylpyrimidines, phenyldioxanes, tolans, and alkenylcyclohexylbenzonitriles can be cited. As the rod-like liquid crystal compound, not only these low-molecular liquid crystal compounds but also high-molecular liquid crystal compounds can be used.
[0368] The content ratio of the liquid crystal compound in the phase difference layer forming composition in the total solids in the phase difference layer forming composition may be 60% by mass or more, 65% by mass or more, 99.9% by mass or less, or 98% by mass or less. The content ratio of the structural unit derived from the liquid crystal compound in the phase difference layer may be 60% by mass or more, 65% by mass or more, 99.9% by mass or less, or 98% by mass or less.
[0369] The oriented liquid crystal compound is preferably fixed by maintaining the oriented state through a polymerization reaction. Therefore, the phase difference layer forming composition preferably contains a photopolymerization initiator. As the photopolymerization initiator, for example, acetophenone, benzophenone, α-hydroxyalkyl phenone, Michler's ketone, benzoin, benzoin dimethyl ether, benzoyl benzoate, α-acyl oxime ester and thioxanthone can be cited. The content of the photopolymerization initiator can be 0.01% by mass or more of the total solid content of the phase difference layer forming composition, can be 0.5% by mass or more, can be 20% by mass or less, and can also be 5% by mass or less.
[0370] The phase difference layer forming composition generally contains an organic solvent. The content of the solvent in the phase difference layer forming composition may be 50% by mass or more, 70% by mass or more, 90% by mass or less, or 80% by mass or less.
[0371] The retardation layer is preferably a λ / 2 retardation layer or a λ / 4 retardation layer.
[0372] The phase difference layer may be, for example, a positive A layer or a positive C layer.
[0373] In this specification, a positive A layer refers to a layer that satisfies the relationship Nx>Ny≈Nz when the refractive index in the axial direction, i.e., the X-axis direction, which is the highest refractive index in the plane of the phase difference layer, is defined as Nx, the refractive index in the Y-axis direction orthogonal to the X-axis in the direction in the plane of the phase difference layer is defined as Ny, and the refractive index in the thickness direction of the phase difference layer is defined as Nz. In this specification, a positive C layer refers to a layer that satisfies the relationship Nx≈Ny<Nz.
[0374] As the liquid crystal compound forming the positive A layer, a liquid crystal compound capable of parallel orientation may be used. Parallel orientation refers to the state in which the molecular long axis of the liquid crystal compound (the axis extending in the direction in which the main chain of the liquid crystal compound extends) is oriented in the horizontal direction of the layer. As the liquid crystal compound forming the positive A layer, for example, rod-shaped liquid crystal materials and disc-shaped liquid crystal materials can be cited, preferably rod-shaped liquid crystal materials. In addition, from the aspect of making the phase difference layer show the reverse dispersion described later, the rod-shaped liquid crystal compound may have a side chain structure.
[0375] As the liquid crystal compound forming the positive C layer, a liquid crystal compound capable of vertical alignment can be used. Vertical alignment refers to the state in which the molecular long axis of the liquid crystal compound (the axis extending in the direction in which the main chain of the liquid crystal compound extends) is oriented in the vertical direction of the layer. As the liquid crystal compound forming the positive C layer, a rod-shaped liquid crystal compound is preferred. In addition, from the aspect of making the phase difference layer show the reverse dispersion described later, the rod-shaped liquid crystal compound may have a side chain structure.
[0376] The phase difference layer can show positive dispersion or reverse dispersion. Reverse dispersion refers to the property that the phase difference given to the transmitted light increases as the wavelength of the transmitted light becomes longer. Specifically, it is the property that the relationship between the retardation at a wavelength of 450nm (Re450) and the retardation at a wavelength of 550nm (Re550) is Re450<Re550. Positive dispersion refers to the property of Re450>Re550.
[0377] The thickness of the phase difference layer can be appropriately adjusted in consideration of the phase difference to be provided. The thickness of the phase difference layer may be 0.01 μm or more, 0.1 μm or more, 0.5 μm or more, 10 μm or less, 5 μm or less, or 3 μm or less.
[0378] The phase difference layer can be formed, for example, by applying a phase difference layer forming composition, drying and curing the composition. The phase difference layer forming composition is preferably applied on an alignment film.
[0379] The alignment layer can be formed, for example, by coating an alignment layer-forming composition on a transparent substrate and imparting an alignment regulating force. The alignment layer-forming composition can be appropriately selected from existing known materials such as photodimerization materials. As means for imparting an alignment regulating force to the alignment layer, for example, a photoalignment method, a rubbing method, and a shaping method can be cited. The thickness of the alignment layer can be more than 1 nm, more than 60 nm, more than 100 nm, less than 1000 nm, or less than 300 nm.
[0380] The phase difference layer may be a transfer body that can be peeled off from the above-mentioned orientation layer or transparent substrate. When the optical layered body having the phase difference layer is formed into the above-mentioned single sheet or a roll-shaped form in which a long sheet is rolled into a roll, the optical layered body having a substrate can reduce manufacturing defects and is advantageous.
[0381] The retardation layer may be disposed at any position of the surface plate, polarizing plate, or image display device described below, and may be used together with other functional layers or an optical layered body.
[0382] The functional layer is formed, for example, as follows. A curable composition is applied to the optical film at a desired thickness. When an organic solvent is used, the organic solvent is removed by drying to form a coating (uncured resin layer). The drying conditions are, for example, 40°C to 120°C and 10 seconds to 10 minutes. Next, when the curable composition contains a thermosetting component, the coating is heated at a temperature required for curing to cure it. When the curable composition contains an ionizing radiation curable component, the coating is irradiated with ionizing radiation to cure it. In this way, a functional layer can be formed.
[0383] When ultraviolet rays are used as ionizing radiation, it is preferred that the coating film be irradiated with ultraviolet rays having a wavelength of at least 190 nm and at most 380 nm. Examples of ultraviolet light sources include xenon lamps, low-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, metal halide lamps, carbon arc lamps, and tungsten lamps. The irradiation light intensity is, for example, 10 mJ / cm 2 Above 350mJ / cm 2 the following.
[0384] The thickness of the functional layer can be appropriately selected according to the function to be assigned. The thickness of the functional layer can be 0.05 μm or more, 0.1 μm or more, 0.5 μm or more, 1 μm or more, or 2 μm or more. The thickness of the functional layer can be 100 μm or less, 50 μm or less, 30 μm or less, 20 μm or less, or 10 μm or less. When the functional layer includes two or more layers, the thickness of the functional layer refers to the total thickness of the functional layer.
[0385] [Surface panel for image display device]
[0386] Hereinafter, the optical film (including the above-mentioned easy-adhesive film) and the optical layered body of the first embodiment of the present disclosure are also collectively referred to as "the optical component of the first embodiment of the present disclosure". As an application example of the optical component of the first embodiment of the present disclosure, for example, a surface plate for an image display device having a resin plate or a glass plate and the optical component of the first embodiment of the present disclosure arranged on the plate can be cited. The optical layered body is preferably arranged in such a manner that the surface of the functional layer side of the optical layered body faces the side opposite to the resin plate or the glass plate.
[0387] The surface plate is preferably arranged in the image display device such that the surface of the side to which the optical component of the first embodiment of the present disclosure is bonded faces the surface side. In other words, the surface plate is preferably arranged such that the surface of the side to which the optical component of the first embodiment of the present disclosure is bonded faces the side opposite to the display element.
[0388] As the resin plate and the glass plate, resin plates and glass plates commonly used as surface plates of image display devices can be used. The optical component according to the first embodiment of the present disclosure can be bonded to the resin plate or the glass plate using an adhesive, for example.
[0389] The thickness of the resin plate and the glass plate may be 10 μm or more from the viewpoint of strength, 5,000 μm or less, and 1,000 μm or less, 500 μm or less, or 100 μm or less from the viewpoint of thinning.
[0390] [Image display device]
[0391] As an application example of the optical component of the first embodiment of the present disclosure, an image display device including a display element and the optical component of the first embodiment of the present disclosure can be cited. The optical component of the first embodiment of the present disclosure is, for example, arranged on the display element. The optical component of the first embodiment of the present disclosure can be arranged on the light emitting surface side of the display element, or on the side opposite to the light emitting surface. In the image display device, the optical layered body is preferably arranged so that the surface on the functional layer side faces the side opposite to the display element. The optical component of the first embodiment of the present disclosure can be arranged on the outermost surface of the image display device.
[0392] As display elements, for example, liquid crystal display elements, EL display elements such as organic EL display elements and inorganic EL display elements, and plasma display elements can be cited, and further, LED display elements such as Mini LED display elements and Micro LED display elements, and liquid crystal display elements or LED display elements using quantum dots can be cited. Therefore, as the above-mentioned image display device, for example, a liquid crystal display device, an EL display device, a plasma display device, an LED display device, and a display device using quantum dots can be cited.
[0393] As the display mode of the liquid crystal of the liquid crystal display element, for example, the IPS mode, the VA mode, the multi-domain mode, the OCB mode, the STN mode and the TSTN mode can be cited. In the case where the display element is a liquid crystal display element, a backlight source is required. As the backlight source, for example, a backlight source having quantum dots and a backlight source having white light emitting diodes can be cited.
[0394] The image display device may be a foldable image display device or a rollable image display device. The image display device may also have a touch panel function. As the touch panel, for example, resistive film type, electrostatic capacitance type, electromagnetic induction type, infrared type and ultrasonic type can be cited. The touch panel function may be added to the display element as an embedded touch panel liquid crystal display element, or a touch panel may be placed on the display element.
[0395] The image display device is used, for example, for tablet computers, smartphones, clocks such as smart watches, car navigation, public information displays (PIDs), fish finders, or drone operation screens.
[0396] [Polarizing plate]
[0397] As an application example of the optical component of the first embodiment of the present disclosure, for example, a polarizer can be cited, which includes: a polarizing element; a first transparent protective plate arranged on one surface of the polarizing element; and a second transparent protective plate arranged on the other surface of the polarizing element, wherein at least one of the first transparent protective plate and the second transparent protective plate is the optical component of the first embodiment of the present disclosure. The optical layered body is preferably arranged so that the surface on the functional layer side faces the side opposite to the polarizing element.
[0398] Examples of polarizing elements include: sheet-type polarizing elements (polyvinyl alcohol film, polyvinyl formal film, polyvinyl acetal film, ethylene-vinyl acetate copolymer saponified film, etc.) formed by stretching a film dyed with iodine or the like; wire grid polarizing elements composed of a large number of metal wires arranged in parallel; coating polarizing elements coated with lyotropic liquid crystal or dichroic host-guest material; and multilayer thin film polarizing elements. The polarizing element may be a reflective polarizing element having the function of reflecting a polarized component that is not transmitted.
[0399] A first transparent protective plate is disposed on one surface of the polarizing element, and a second transparent protective plate is disposed on the other surface. At least one of the first transparent protective plate and the second transparent protective plate is the optical component of the first embodiment of the present disclosure.
[0400] As the first transparent protective plate and the second transparent protective plate other than the optical component of the first embodiment of the present disclosure, for example, plastic films and glass plates can be cited. As the plastic film, for example, polyester film, polycarbonate film, triacetyl cellulose film, cycloolefin polymer film and acrylic film can be cited, and in order to improve the mechanical strength, stretched films thereof are preferred. As the glass plate, for example, a glass plate composed of glass such as alkali glass, nitride glass, soda-lime glass, borosilicate glass and lead glass can be cited.
[0401] The polarizing element and the transparent protective plate are preferably bonded together via an adhesive. As the adhesive, a general-purpose adhesive can be used, and for example, a polyvinyl alcohol (PVA)-based adhesive is preferred.
[0402] The first embodiment of the present disclosure relates to, for example, the following [1] to
[14] .
[0403] [1] An optical film for laminating a functional layer, wherein the optical film contains polyester, the biomass degree of the optical film is 10% or more, the total light transmittance of the optical film is 70% or more, and the in-plane phase difference of the optical film is 3,000 nm or more and 30,000 nm or less.
[0404] [2] The optical film according to [1] above, wherein the optical film contains a polyester derived from a biomass material.
[0405] [3] The optical film according to [1] or [2] above, wherein the optical film contains polyester derived from recycled materials.
[0406] [4] The optical film according to any one of [1] to [3] above, wherein the in-plane retardation is 4,000 nm to 15,000 nm.
[0407] [5] The optical film according to any one of [1] to [4] above, wherein the Martens hardness of at least one surface of the optical film is 110 N / mm 2 Above 170N / mm 2 the following.
[0408] [6] The optical film according to any one of [1] to [5] above, wherein the elastic deformation power of at least one surface of the optical film is 60% to 70%.
[0409] [7] The optical film according to any one of [1] to [6] above, which is composed of a polyester film containing the polyester, or comprises a polyester film containing the polyester and an easy-adhesion layer provided on the polyester film.
[0410] [8] The optical film according to [7] above, wherein the resin constituting the easy-adhesion layer is a resin derived from a biomass material.
[0411] [9] The optical film according to [7] above, wherein the resin constituting the easily adhesive layer is a resin derived from fossil fuels.
[0412]
[10] The optical film according to [7] above, wherein the resin constituting the easy-adhesion layer is a mixed resin of a resin derived from a biomass material and a resin derived from a fossil fuel.
[0413]
[11] An optical layered body comprising: the optical film according to any one of [1] to
[10] above; and a functional layer provided on the optical film.
[0414]
[12] A surface plate for an image display device, comprising: a resin plate or a glass plate; and the optical film according to any one of [1] to
[10] or the optical layered body according to
[11] disposed on the plate.
[0415]
[13] An image display device comprising: a display element; and the optical film according to any one of [1] to
[10] or the optical layered body according to
[11] disposed on the display element.
[0416]
[14] A polarizing plate comprising: a polarizing element; a first transparent protective plate arranged on one surface of the polarizing element; and a second transparent protective plate arranged on the other surface of the polarizing element, wherein at least one of the first transparent protective plate and the second transparent protective plate is the optical film described in any one of [1] to
[10] or the optical layered body described in
[11] .
[0417] Second Embodiment
[0418] A second embodiment of the present disclosure relates to an optical film.
[0419] Hereinafter, a second embodiment of the present disclosure will be described. In particular, the second embodiment of the present disclosure will be described centering on the differences from the above-described first embodiment.
[0420] First, the problem to be solved by the second embodiment is described. For the purpose of improving the visual recognition of the image and suppressing the damage of the device surface, the image display device has various optical layered bodies. Such optical layered bodies usually have a plastic film as an optical film and a functional layer provided on the film (for example, refer to Japanese Patent Publication No. 2007-046031, Japanese Patent Publication No. 2012-256014 and Japanese Patent Publication No. 2016-141058).
[0421] Polyester films such as polyethylene terephthalate films have been proposed as the plastic films, but when polyester films are applied to image display devices that output polarized light, such as liquid crystal display devices and organic EL display devices, rainbow-like interference patterns called rainbow spots may occur, which reduces visibility.
[0422] In recent years, there has been a growing trend toward building a sustainable recycling-oriented society. From the perspective of carbon neutrality, there is a desire to move away from fossil fuels in the material field as well as in the energy field.
[0423] An object of a second embodiment of the present disclosure is to provide an optical film that has excellent visibility and can reduce environmental burden.
[0424] According to the second embodiment of the present disclosure, an optical film having excellent visibility and reduced environmental burden is provided. Also, an optical film having optical and mechanical properties comparable to those of a polyester derived from fossil fuels can be provided even when using polyester derived from biomass materials.
[0425] In the following description of the second embodiment of the present disclosure, for the optical film described in the first embodiment, and the optical layered body, the surface plate, the image display device, and the polarizing plate having the optical film, the same symbols as those used in the first embodiment are sometimes used, and the repeated description is sometimes omitted. In the case where it is obvious that the effects obtained in the first embodiment can also be obtained in the second embodiment, the description thereof is sometimes omitted. The description of the optical film, the optical layered body, the surface plate, the image display device, and the polarizing plate as the second embodiment of the present disclosure can be applied to the description of the optical film, the optical layered body, the surface plate, the image display device, and the polarizing plate of the first embodiment of the present disclosure as long as there is no contradiction.
[0426] In the following description of the second embodiment of the present disclosure, unless otherwise specified, when “optical film” is described, it means the optical film of the second embodiment of the present disclosure.
[0427] [Optical film]
[0428] <Physical properties of optical films>
[0429] (In-plane phase difference (Re))
[0430] In the second embodiment of the present disclosure, the in-plane phase difference (Re) of the optical film is less than 1,500nm. In this specification, the "in-plane phase difference" is calculated by the formula: in-plane phase difference (Re) = (nx-ny) × T [nm]. "In-plane phase difference" is also called delay, and the unit is the unit of length. T in the above formula refers to the thickness of the optical film [nm]. If the value of the in-plane phase difference becomes higher, the optical film will produce rainbow spots, and there is a tendency for visual recognition to decrease. An optical film with an in-plane phase difference of less than 1,500nm can suppress such rainbow spots.
[0431] "nx" is the refractive index in the direction of the slow axis, where the refractive index in the plane of the optical film is the largest. "ny" is the refractive index in the direction of the fast axis, which is a direction orthogonal to the slow axis in the plane of the optical film. The refractive index and in-plane phase difference refer to the refractive index and in-plane phase difference relative to a wavelength of 550nm. The direction of the slow axis and the in-plane phase difference are measured at a measurement angle of 0° using the trade name "RETS-100" manufactured by Otsuka Electronics Co., Ltd. In addition to the measurement results of the in-plane phase difference of "RETS-100", nx-ny can also be calculated from the thickness information of the optical film.
[0432] In this specification, nx-ny and Re are the average values of 16 measured values excluding the minimum and maximum values from 18 measured values. In this specification, the measurement site is selected from any site without defects such as damage and dirt.
[0433] The refractive index difference "nx-ny" (hereinafter also referred to as "Δn") can be less than 0.050, or less than 0.040. If Δn is less than 0.050, rainbow spots caused by in-plane phase difference can be easily suppressed. Δn can be greater than 0.005, greater than 0.008, or greater than 0.010. If Δn is greater than 0.005, the so-called black screen can be easily suppressed. Here, the black screen refers to the phenomenon that the display screen becomes darker due to the angle when observing, for example, a liquid crystal display device while wearing polarized sunglasses.
[0434] The refractive index (nx) in the slow axis direction may be 1.580 or more, or 1.630 or more. The refractive index (nx) in the slow axis direction may be 1.780 or less, or 1.730 or less. The refractive index (ny) in the fast axis direction may be 1.560 or more, or 1.610 or more. The refractive index (ny) in the fast axis direction may be 1.760 or less, or 1.710 or less.
[0435] The optical film or polyester film is preferably a stretched film. The stretched film may be a biaxially stretched film. The biaxial stretching may be a stepwise biaxial stretching or a simultaneous biaxial stretching.
[0436] As an example, an optical film having an in-plane phase difference of 1,500 nm or less is obtained by stepwise biaxial stretching as follows: a resin composition containing polyester is melted and extruded into a sheet to obtain an unstretched polyester. The unstretched film is stretched in the flow direction and then stretched in the width direction of the film.
[0437] The stretching in the flow direction can be performed, for example, by utilizing the difference in the peripheral speed of the rollers. The stretching ratio in the flow direction can be 2.5 times or more, or 3.0 times or more. The stretching ratio in the flow direction can be 6.0 times or less, or 5.5 times or less.
[0438] The stretching in the width direction can be performed, for example, by a tentering method. From the perspective of adjusting the in-plane retardation to 1,500 nm or less, the stretching ratio in the width direction may be 80% to 120% or 90% to 110% relative to the stretching ratio in the flow direction.
[0439] The difference in physical properties between the stretching direction and the direction orthogonal to the optical film with a high in-plane phase difference manufactured by uniaxial stretching becomes larger. Therefore, the optical film with a high in-plane phase difference is easily deformed by external factors such as heat. For example, when an optical film with a high in-plane phase difference is used as a substrate for a transparent conductive film, the optical film may be deformed by heat during the crystallization process of the transparent conductive layer and the process of forming a take-out electrode composed of a silver paste or the like on the transparent conductive layer and firing it. In this regard, the optical film with a low in-plane phase difference based on biaxial stretching has excellent thermal stability.
[0440] The substrate may include a resin layer as a matrix containing polyester, and birefringent particles that function in a manner that eliminates the birefringence of the resin layer when stretched. That is, the birefringent particles may have a birefringence that is positively or negatively opposite to the birefringence of the polymer processed product forming the resin layer. The polyester resin layer has positive birefringence. Therefore, the birefringent particles may have negative birefringence.
[0441] Polyester is excellent in transparency, heat resistance, and mechanical properties, and its in-plane phase difference can be controlled within a desired range by stretching.
[0442] As a method for controlling the in-plane phase difference of the optical film to be less than 1,500 nm, there is a method of appropriately setting the stretch ratio ratio during biaxial stretching, the stretching temperature, and the thickness of the produced optical film. Specifically, the closer the stretch ratio ratio is to 1, the smaller the in-plane phase difference is. The higher the stretching temperature, the smaller the in-plane phase difference is. The smaller the thickness, the smaller the in-plane phase difference is. The larger the stretch ratio ratio, the larger the in-plane phase difference is. The lower the stretching temperature, the larger the in-plane phase difference is. The larger the thickness, the larger the in-plane phase difference is.
[0443] The smaller the in-plane phase difference of the optical film, the smaller the change in the visible light transmittance of each wavelength relative to the change in the in-plane phase difference. That is, even if there is a deviation in the in-plane phase difference, the visible light transmittance of each wavelength hardly changes. Therefore, if the deviation in the in-plane phase difference is small enough, rainbow spots that can be visually confirmed will not occur. Therefore, if the in-plane phase difference of the optical film is less than 1,500nm, the change in the visible light transmittance of each wavelength corresponding to the in-plane phase difference becomes sufficiently small, and the rainbow spots caused by the deviation in the in-plane phase difference can be effectively made less noticeable. From this aspect, the in-plane phase difference of the optical film is less than 1,500nm, less than 1,450nm, or less than 1,200nm. According to an optical film having such an in-plane phase difference, rainbow spots can be effectively made less noticeable. In addition, from the perspective of suppressing black screen, the in-plane phase difference of the optical film can be 50 nm or more, 100 nm or more, 150 nm or more, 200 nm or more, 250 nm or more, or 300 nm or more. By making the in-plane phase difference 50 nm or more, it is easy to suppress black screen. This is because the optical film with an in-plane phase difference of 50 nm or more can appropriately disturb linear polarized light.
[0444] (Total Light Transmittance and Haze)
[0445] In the second embodiment of the present disclosure, the total light transmittance of the optical film may be 70% or more, 75% or more, or 80% or more. The higher the total light transmittance of the optical film, the more preferred it is, and it may be 99% or less, 98% or less, or 95% or less. The total light transmittance is measured in accordance with JIS K7361-1:1997.
[0446] (Martens hardness)
[0447] In the second embodiment of the present disclosure, it is preferable that the standard deviation 3σ of the Martens hardness of at least one surface of the optical film is 45 N / mm 2 Below. The standard deviation of Martens hardness is 45N / mm 2 The following optical films have excellent foldability. From the perspective of foldability, the standard deviation can be 40 N / mm 2 Below, can be 35N / mm 2 Below, can be 30N / mm 2 Below, can be 25N / mm 2 Below, can be 20N / mm 2 Below, can be 15N / mm 2 Below, 10N / mm is also possible 2 The smaller the standard deviation, the better, and it can be 1N / mm 2 Above, 3N / mm is also possible 2 The standard deviation can be adjusted by the temperature at the time of forming the optical film.
[0448] (Elastic deformation power)
[0449] In the second embodiment of the present disclosure, the standard deviation 3σ of the elastic deformation power of at least one surface of the optical film is preferably 10% or less. The optical film having a standard deviation of the elastic deformation power of 10% or less has excellent hardness. The smaller the standard deviation, the more preferred it is, and it can be 0.1% or more, 0.5% or more, 1% or more, or 2% or more. The standard deviation can be adjusted by the temperature during film formation of the optical film.
[0450] (Corrosion rate)
[0451] In the second embodiment of the present disclosure, when the average of the corrosion rates from the surface of the optical film to a depth of 20 μm is defined as E0-20, the optical film may have an E0-20 of 1.40 μm / g or more. Such an optical film has a good pencil hardness.
[0452] The inventors have studied the corrosion rate as an indicator of the pencil hardness of the optical film. As described above, the optical film is easily damaged when it is soft and not easily damaged when it is hard, so it is believed that the pencil hardness can be improved when the corrosion rate is small. However, the inventors have found that, on the contrary, by increasing the corrosion rate (E0-20) to 1.40 μm / g or more, the pencil hardness of the optical film can be improved. In addition, the inventors have found that, for the corrosion rate of the optical film, the biaxially stretched optical film is more likely to show a large value than the uniaxially stretched optical film, and the quality of the pencil hardness in the biaxially stretched optical film can be judged by the corrosion rate.
[0453] In order to improve the pencil hardness of the optical film, E0-20 may be 1.40 μm / g or more, 1.45 μm / g or more, 1.50 μm / g or more, 1.60 μm / g or more, or 1.80 μm / g or more. In order to make the optical film less prone to cracking, E0-20 may be 3.00 μm / g or less, 2.80 μm / g or less, or 2.50 μm / g or less.
[0454] (Crystallinity)
[0455] In the second embodiment of the present disclosure, the crystallinity of the optical film may exceed 85%. Such an optical film has a good pencil hardness. From the aspect of the pencil hardness of the optical film, the crystallinity of the optical film may be 88% or more, or 90% or more. The crystallinity of the optical film may be 100% or less, 99% or less, or 98% or less.
[0456] The crystallinity of the optical film can be controlled, for example, by the stretching ratio and the stretching temperature. Specifically, the greater the stretching ratio, the greater the crystallinity. The smaller the stretching ratio, the smaller the crystallinity.
[0457] The second embodiment of the present disclosure relates to, for example, the following [1] to
[14] .
[0458] [1] An optical film for laminating a functional layer, wherein the optical film contains polyester, the biomass degree of the optical film is 10% or more, the total light transmittance of the optical film is 70% or more, and the in-plane phase difference of the optical film is 1,500 nm or less.
[0459] [2] The optical film according to [1] above, wherein the optical film contains a polyester derived from a biomass material.
[0460] [3] The optical film according to [1] or [2] above, wherein the optical film contains polyester derived from recycled materials.
[0461] [4] The optical film according to any one of [1] to [3] above, wherein the in-plane retardation is 300 nm to 1,450 nm.
[0462] [5] The optical film according to any one of [1] to [4] above, wherein the Martens hardness of at least one surface of the optical film is 110 N / mm 2 Above 170N / mm 2 the following.
[0463] [6] The optical film according to any one of [1] to [5] above, wherein the elastic deformation power of at least one surface of the optical film is 60% to 70%.
[0464] [7] The optical film according to any one of [1] to [6] above, which is composed of a polyester film containing the polyester, or comprises a polyester film containing the polyester and an easy-adhesion layer provided on the polyester film.
[0465] [8] The optical film according to [7] above, wherein the resin constituting the easy-adhesion layer is a resin derived from a biomass material.
[0466] [9] The optical film according to [7] above, wherein the resin constituting the easily adhesive layer is a resin derived from fossil fuels.
[0467]
[10] The optical film according to [7] above, wherein the resin constituting the easy-adhesion layer is a mixed resin of a resin derived from a biomass material and a resin derived from a fossil fuel.
[0468]
[11] An optical layered body comprising: the optical film according to any one of [1] to
[10] above; and a functional layer provided on the optical film.
[0469]
[12] A surface plate for an image display device, comprising: a resin plate or a glass plate; and the optical film according to any one of [1] to
[10] or the optical layered body according to
[11] disposed on the plate.
[0470]
[13] An image display device comprising: a display element; and the optical film according to any one of [1] to
[10] or the optical layered body according to
[11] disposed on the display element.
[0471]
[14] A polarizing plate comprising: a polarizing element; a first transparent protective plate arranged on one surface of the polarizing element; and a second transparent protective plate arranged on the other surface of the polarizing element, wherein at least one of the first transparent protective plate and the second transparent protective plate is the optical film described in any one of [1] to
[10] or the optical layered body described in
[11] .
[0472] Third Embodiment
[0473] A third embodiment of the present disclosure relates to an optically effective film.
[0474] Hereinafter, a third embodiment of the present disclosure will be described. In particular, the third embodiment of the present disclosure will be described centering on the differences from the first embodiment described above.
[0475] First, the problem to be solved by the third embodiment is described. For the purpose of improving the visual recognition of the image and suppressing the damage of the device surface, the image display device is equipped with various optical effect films. Such optical effect films usually include a plastic film and a functional layer provided on the film (for example, refer to Japanese Patent Publication No. 2007-046031 and Japanese Patent Publication No. 2012-256014).
[0476] As the above-mentioned plastic film, polyester films such as polyethylene terephthalate films have been proposed. In addition, in recent years, the trend of building a sustainable recycling society has been increasing. From the perspective of carbon neutrality, it is expected to be separated from fossil fuels in the field of materials as well as energy.
[0477] The present inventors have studied the use of polyester derived from biomass materials to produce optical effect films from the viewpoint of carbon neutrality. However, the present inventors have found that optical effect films containing polyester derived from biomass materials tend to exhibit yellow color.
[0478] The third embodiment of the present disclosure aims to provide an optical effect film which has less yellow tint and can reduce environmental burden.
[0479] According to the third embodiment of the present disclosure, an optical film with less yellow tint and reduced environmental burden is provided. In addition, an optical film having optical and mechanical properties comparable to those of a polyester derived from fossil fuels can be provided even when using polyester derived from biomass materials.
[0480] In the following description of the third embodiment of the present disclosure, the same reference numerals as those used in the first embodiment may be used for the optical film, the optical layered body, the surface plate, the image display device, and the polarizing plate having the optical film described in the first embodiment, and the repeated description may be omitted. In the case where it is obvious that the effect obtained in the first embodiment can also be obtained in the second embodiment, the description thereof may be omitted.
[0481] [Optical effect film]
[0482] In the third embodiment of the present disclosure, the optically functional film refers to a film that can transmit light.
[0483] The cross section of the optically functional film according to the third embodiment of the present disclosure is Figure 1 The cross-section of the optical film 1 shown is the same. That is, Figure 1 This is also equivalent to a cross-sectional view showing the optically functional film 2 according to the third embodiment of the present disclosure. Figure 1 As shown, the optically effective film 2 of the third embodiment of the present disclosure has a first surface 2a and a second surface 2b facing the first surface 2a. The polyester film described later also has a first surface and a second surface facing the first surface. In the case where the first surface and the second surface are not particularly distinguished, they are sometimes simply referred to as "surfaces". The optically effective film has a first direction and a second direction orthogonal to the first direction within the surface. In the third embodiment, the first direction is the longitudinal direction, flow direction or mechanical direction (MD) of the optically effective film. In the third embodiment, the second direction is the transverse direction or width direction (TD) of the optically effective film. In the following description of the first embodiment of the present disclosure, unless otherwise specifically distinguished, when it is recorded as "optically effective film", it refers to the optically effective film of the third embodiment of the present disclosure.
[0484] In the third embodiment, the optically effective film includes at least a polyester film.
[0485] The polyester film refers to a film containing polyester.
[0486] In the third embodiment, the optically effective film is composed of a polyester film.
[0487] In the third embodiment, the optical effect film includes a polyester film and an easily adhesive layer provided on the polyester film. In the third embodiment, the optical effect film including the polyester film and the easily adhesive layer can be particularly referred to as an "easy adhesive film".
[0488] In this specification, the polyester film, the easily adhesive film, and the optical function film including the polyester film and the color tone adjusting layer described later in the optical function film may be collectively referred to as "optical function film A".
[0489] In the third embodiment, the optically functional film comprises a polyester film and a functional layer provided on the polyester film. In this specification, the optically functional film comprising a polyester film and a functional layer is sometimes particularly referred to as an "optical layered body." The optical layered body may comprise an easy-adhesion layer between the polyester film and the functional layer.
[0490] <Polyester>
[0491] The optical effect film and the polyester film contain polyester.
[0492] As for the description of the polyester contained in the optical film in the third embodiment of the present disclosure, the description of the polyester contained in the optical film in the first embodiment of the present disclosure can be applied as long as there is no contradiction. As for the description of the polyester contained in the polyester film in the third embodiment of the present disclosure, the description of the polyester contained in the polyester film in the first embodiment of the present disclosure can be applied as long as there is no contradiction.
[0493] <Bluing agent>
[0494] The optical effect film preferably contains a bluing agent as a toner.
[0495] In this specification, a bluing agent refers to a component that absorbs light in a wavelength range such as orange to yellow in the visible light region and adjusts the color tone. The visible light region refers to a region between 380 nm and 780 nm. For example, a bluing agent is a dye or a pigment.
[0496] Biomass polyester sometimes contains low molecular weight components (low molecular weight components). It is speculated that due to the low molecular weight components, the optical film appears yellow or the optical film turns yellow. By making the optical film contain a bluing agent, the yellow tone of the optical film can be well reduced.
[0497] In the optical effect film, the polyester film may contain a bluing agent.
[0498] In the easily adhesive film, at least one selected from the polyester film and the easily adhesive layer may contain a bluing agent.
[0499] In the optical layered body, at least one selected from the polyester film and the functional layer may contain a bluing agent. In the optical layered body, at least one selected from the polyester film, the easy-adhesion layer and the functional layer may contain a bluing agent.
[0500] By means of the above, the yellow tint of the optical effect film can be reduced satisfactorily.
[0501] The bluing agent may have a maximum absorption peak in the wavelength range of 500 nm to 650 nm in the visible light region, or may have a maximum absorption peak in the wavelength range of 550 nm to 600 nm. A bluing agent having a maximum absorption peak in such a wavelength range can effectively reduce the yellow tone of the optical effect film.
[0502] In the present specification, the maximum absorption peak can be measured using an ultraviolet-visible spectrophotometer (spectrophotometer V-670 manufactured by JASCO Corporation). As a solvent for dissolving the bluing agent, acetonitrile can be used.
[0503] Examples of bluing agents include organic dyes or pigments and inorganic dyes or pigments. Examples of organic dyes or pigments include condensed polycyclic bluing agents and phthalocyanine bluing agents. Examples of inorganic dyes or pigments include ultramarine, Prussian blue, and cobalt blue.
[0504] As the bluing agent, from the aspects of heat resistance, light resistance and solubility, a condensed polycyclic bluing agent can be used. As the condensed polycyclic bluing agent, for example, anthraquinone-based bluing agents, indigo-based bluing agents and phthalocyanine-based bluing agents can be mentioned. Among these, anthraquinone-based bluing agents are preferred from the aspects of heat resistance, light resistance and solubility.
[0505] The anthraquinone-based bluing agent is a bluing agent having an anthraquinone ring represented by formula (1). Examples of the anthraquinone-based bluing agent include compounds represented by formula (2), and specifically compounds represented by formulas (3) to (5).
[0506] [Chemistry 1]
[0507]
[0508] In formula (2), X1 represents -OH, -NHR1 or -NR1R2, X2 represents -NHR3 or -NR3R4, and R1, R2, R3 and R4 each independently represent a linear or branched alkyl group having 1 to 6 carbon atoms, or a phenyl group in which at least one hydrogen atom is substituted by a linear or branched alkyl group having 1 to 6 carbon atoms. X1 and X2 in formula (2) may be the same or different.
[0509] The compound represented by formula (2) preferably comprises a phenyl group in which at least one of X1 and X2 has at least one hydrogen atom substituted by a straight-chain or branched-chain alkyl group having 1 to 6 carbon atoms, and more preferably comprises a phenyl group in which at least one of X1 and X2 has at least one hydrogen atom substituted by a straight-chain or branched-chain alkyl group having 1 to 6 carbon atoms.
[0510] [Chemistry 2]
[0511]
[0512] Indigo blueing agents are blueing agents containing indoxyl or thioindoxyl. Phthalocyanine blueing agents are blueing agents having a ring structure in which four phthalimides are cross-linked by nitrogen atoms.
[0513] The optical effect film may contain one or more bluing agents.
[0514] When the optical effect film contains a bluing agent, the content of the bluing agent is preferably small and the number of types of bluing agents used is preferably small from the viewpoint of maintaining the total light transmittance of the optical effect film high.
[0515] The content of the bluing agent may be 5 wtppm or more, 8 wtppm or more, or 10 wtppm or more based on the total weight of the optical effect film. When the content of the bluing agent is above the lower limit, the yellow tone of the optical effect film is reduced.
[0516] The content of the bluing agent can be 100 wtppm or less, 80 wtppm or less, 60 wtppm or less, 50 wtppm or less, 40 wtppm or less, or 30 wtppm or less, based on the total mass of the optical effect film. The optical effect film having a bluing agent content below the upper limit has a good color tone and shows a high total light transmittance and low haze.
[0517] The content of the bluing agent can be measured by a known method.
[0518] The optical effect film may contain additives. Examples of additives include ultraviolet absorbers, light stabilizers, antioxidants, heat stabilizers, antistatic agents, slippery particles, heat-resistant polymer particles, alkali metal compounds, alkaline earth metal compounds, phosphorus compounds, flame retardants, anti-gelling agents, and surfactants. The optical effect film may contain one or more additives.
[0519] <Optical effect film structure>
[0520] The optical effect film may have a single-layer structure or a multi-layer structure. A film having a single-layer structure is easy to control stretching. A film having a multi-layer structure is easy to obtain the effect brought about by changing the composition of each layer.
[0521] The optical effect film may be a polyester film containing polyester and a bluing agent. The optical effect film may include a polyester film and a color tone adjustment layer containing a bluing agent disposed on the polyester film, and the polyester film may further contain a bluing agent. Hereinafter, the color tone adjustment layer is also referred to as a "coloring layer". The coloring layer may be an easy-adhesion layer described later. The coloring layer may be a coating formed by applying a coating liquid containing a bluing agent to a polyester film.
[0522] The preferred thickness of the polyester film will be described later.
[0523] The thickness of the coloring layer may be 10 nm or more, 30 nm or more, or 50 nm or more. The thickness of the coloring layer may be 1,000 nm or less, 800 nm or less, 600 nm or less, 400 nm or less, or 200 nm or less.
[0524] When the polyester film contains a bluing agent, the content of the bluing agent in the polyester film may be 5 wtppm or more, 8 wtppm or more, or 10 wtppm or more based on the total weight of the polyester film. Such a polyester film has a less yellow tint.
[0525] When the polyester film contains a bluing agent, the content of the bluing agent in the polyester film may be 100 wtppm or less, 80 wtppm or less, 60 wtppm or less, 50 wtppm or less, 40 wtppm or less, or 30 wtppm or less based on the total mass of the polyester film. Such a polyester film has a good color tone and shows a high total light transmittance and low haze.
[0526] The content of the bluing agent in the toning layer may be 10 wtppm or more, 50 wtppm or more, 100 wtppm or more, 200 wtppm or more, 300 wtppm or more, 400 wtppm or more, 500 wtppm or more, 1,000 wtppm or more, 2,000 wtppm or more, 3,000 wtppm or more, or 4,000 wtppm or more, based on the mass of the toning layer. The optically functional film having such a toning layer has a reduced yellow tint.
[0527] The content of the bluing agent in the toning layer may be 20,000 wtppm or less, 18,000 wtppm or less, 15,000 wtppm or less, 13,000 wtppm or less, 10,000 wtppm or less, or 8,000 wtppm or less, based on the mass of the toning layer. The optically functional film having such a toning layer has a good color tone, and also exhibits a high total light transmittance and low haze.
[0528] The polyester film may have a single-layer structure or a multi-layer structure. The film having a single-layer structure is easy to control stretching. The film having a multi-layer structure is easy to obtain the effect brought by changing the composition of each layer. In the polyester film having a multi-layer structure, at least one layer may contain a bluing agent.
[0529] In a polyester film having a multilayer structure, the biomass polyester may be contained in at least one layer. For example, a multilayer film having a layer containing a biomass polyester as a main component and a layer containing a polyester derived from a fossil fuel as a main component has excellent stretchability. In this specification, a layer containing a certain polymer as a main component refers to a layer containing the polymer in a proportion exceeding 50% by mass, and the content of the polymer may be 60% by mass or more, 70% by mass or more, 80% by mass or more, or 90% by mass or more.
[0530] Examples of the polyester film having a multilayer structure include:
[0531] (1A) A multilayer film comprising two or three or more layers containing a biomass polyester as a main component;
[0532] (2A) a multilayer film comprising a layer containing a biomass polyester as a main component and a layer containing a polyester derived from a fossil fuel as a main component;
[0533] (3A) a multilayer film comprising, in order, a layer containing a biomass polyester as a main component, a layer containing a polyester derived from a fossil fuel as a main component, and a layer containing a biomass polyester as a main component;
[0534] (4A) a multilayer film comprising, in order, a layer containing a biomass polyester as a main component, a layer containing a biomass polyester as a main component, and a layer containing a polyester derived from a fossil fuel as a main component;
[0535] (5A) A multilayer film comprising, in this order, a layer containing a polyester derived from fossil fuel as a main component, a layer containing a biomass polyester as a main component, and a layer containing a polyester derived from fossil fuel as a main component.
[0536] Examples of the polyester film having a multilayer structure include:
[0537] (1B) A multilayer film having two or three or more layers with a biomass degree of 10% or more;
[0538] (2B) A multilayer film comprising a layer having a biomass degree of 10% or more and a layer having a biomass degree of less than 10%;
[0539] (3B) a multilayer film comprising, in order, a layer having a biomass degree of 10% or more, a layer having a biomass degree of less than 10%, and a layer having a biomass degree of 10% or more;
[0540] (4B) a multilayer film comprising, in order, a layer having a biomass degree of 10% or more, a layer having a biomass degree of 10% or more, and a layer having a biomass degree of less than 10%;
[0541] (5B) A multilayer film having, in order, a layer having a biomass degree of less than 10%, a layer having a biomass degree of 10% or more, and a layer having a biomass degree of less than 10%. In the multilayer films of (1B) to (5B), the biomass degree of the film as a whole is 10% or more.
[0542] The multilayer films of (1A) and (1B) have high environmental contributions. The multilayer films of (2A) to (4A) and (2B) to (4B) have high environmental contributions and excellent stretchability. The multilayer films of (5A) and (5B) have high environmental contributions and excellent stretchability, and can also suppress the influence of impurities that can be precipitated from biomass polyester on the functional layer laminated on the polyester film.
[0543] The polyester film having a multilayer structure may be a coextruded resin film. For example, the materials constituting each layer are coextruded to form a film, and then stretched to obtain a polyester film having a multilayer structure.
[0544] The thickness of the polyester film may be 10 μm or more, 15 μm or more, 20 μm or more, 25 μm or more, or 30 μm or more. Such a polyester film has excellent mechanical strength.
[0545] The thickness of the polyester film may be 200 μm or less, 180 μm or less, 160 μm or less, 140 μm or less, 120 μm or less, or 100 μm or less. Such a polyester film has excellent bending resistance.
[0546] In this specification, the thickness of the optical film, polyester film and each layer is calculated by selecting 20 arbitrary parts of the cross-sectional photographs of the optical film and polyester film obtained by scanning electron microscope (SEM) and calculating the average value of the 20 parts. Among them, the 20 parts are selected so that the parts are not biased to one side. Regarding the acceleration voltage and magnification of SEM, the acceleration voltage is preferably 1 kV to 10 kV, and the magnification is preferably 20 times to 7,000 times, which are set according to the layer to be measured.
[0547] When a functional layer is formed on a polyester film, the film may be subjected to physical treatment such as corona discharge treatment or oxidation treatment to improve adhesion, or a coating called an anchor agent or a primer may be applied in advance.
[0548] The polyester film and the optical film may be in the form of a single sheet cut into a predetermined size, or in the form of a roll formed by rolling a long strip. The size of the single sheet, for example, has a maximum diameter of about 2 inches to about 500 inches. The maximum diameter refers to the maximum length when any two points in the plane of the polyester film and the optical film are connected. For example, when the polyester film and the optical film are rectangular, the diagonal of the rectangle becomes the maximum diameter. When the polyester film and the optical film are circular, the diameter of the circle becomes the maximum diameter.
[0549] The width of the roll-shaped form can be, for example, 500 mm to 8,000 mm. The length of the roll-shaped form can be, for example, 100 m to 10,000 m. The polyester film and optical film in a roll-shaped form can be cut into a single sheet for use according to the size of the image display device, etc. When cutting, it is preferred to remove the end of the roll where the physical properties are unstable.
[0550] The shape of the single sheet can be, for example, a polygon such as a triangle, a quadrilateral, or a pentagon, or a circle, or a random amorphous shape. More specifically, when the polyester film and the optical film are quadrilaterals, the aspect ratio is not particularly limited as long as it does not cause problems as a display screen. For example, aspect:vertical = 1:1, 4:3, 16:10, 16:9, 2:1, 5:4, 11:8 can be cited.
[0551] <Physical properties of optical effect films and polyester films>
[0552] Physical properties that the optical effect film and the polyester film preferably have are described.
[0553] (Biomass degree)
[0554] The biomass degree of the optical effect film is 10% or more, 12% or more, 15% or more, or 18% or more. Such an optical effect film can reduce the environmental burden. The higher the biomass degree of the optical effect film, the more preferred it is, for example, it can be 98% or less, 90% or less, 80% or less, 70% or less, 60% or less, 50% or less, 40% or less, or 30% or less.
[0555] The biomass degree of the polyester film may be 10% or more, 12% or more, 15% or more, or 18% or more. Such a polyester film can reduce the environmental burden. The higher the biomass degree of the polyester film, the more preferred it is, for example, it may be 98% or less, 90% or less, 80% or less, 70% or less, 60% or less, 50% or less, 40% or less, or 30% or less.
[0556] When measuring the biomass of the entire optical film, a sample may be prepared from the optical film. When measuring the biomass of each layer in the optical film, a target layer may be separated from the optical film to prepare a sample.
[0557] (Yellowness YI)
[0558] The yellowness index (YI) of the optical effect film is -1.0 or more and 2.5 or less.
[0559] The yellowness index (YI) of the polyester film may be -1.0 or more and 2.5 or less.
[0560] Yellowness (YI) indicates the degree to which the hue deviates from colorless to yellow. A positive YI value indicates a yellow hue. A negative YI value indicates a blue hue. YI is calculated from tristimulus values (X, Y, and Z) according to JIS K7373:2006 by the following formula. The tristimulus values are measured by measuring the transmittance of light with a wavelength of 300 nm to 800 nm using an ultraviolet-visible spectrophotometer (spectrophotometer V-670 manufactured by JASCO Corporation).
[0561] YI=100×(1.2769X-1.0592Z) / Y
[0562] In the above formula, X, Y and Z respectively represent the tristimulus values of the optically effective film in the XYZ colorimetric system when using the auxiliary light source C. The tristimulus values are expressed in the XYZ colorimetric system (2 degree field of view) using the auxiliary light source C specified in JIS Z8720:2012.
[0563] An optical function film having a YI of more than 2.5 may appear yellow, which is not preferable in terms of the appearance of the optical function film. An optical function film having a YI of less than -1.0 may appear blue, which is not preferable in terms of the appearance of the optical function film.
[0564] The YI may be 2.4 or less, 2.0 or less, 1.8 or less, 1.5 or less, or 1.3 or less. The optical effect film and polyester film having such a YI further suppress the yellow tint. The YI may be -0.8 or more, -0.5 or more, -0.3 or more, 0.0 or more, 0.3 or more, or 0.5 or more.
[0565] (In-plane phase difference (Re))
[0566] The in-plane phase difference (Re) of the optical film A is not particularly limited and can be 30,000 nm or less. In this specification, the "in-plane phase difference" is calculated by the formula: in-plane phase difference (Re) = (nx-ny) × T [nm]. "In-plane phase difference" is also called delay, and the unit is the unit of length. T in the above formula in the description of the third embodiment refers to the thickness of the optical film A [nm].
[0567] In the description of the third embodiment, "nx" is the refractive index in the direction of the maximum refractive index in the plane of the optically effective film A, i.e., the slow axis direction. "ny" is the refractive index in the direction orthogonal to the slow axis direction in the plane of the optically effective film A, i.e., the fast axis direction. The refractive index and the in-plane phase difference refer to the refractive index and the in-plane phase difference relative to a wavelength of 550 nm. The direction of the slow axis and the in-plane phase difference are measured at a measuring angle of 0° using the trade name "RETS-100" manufactured by Otsuka Electronics Co., Ltd. In addition to the measurement results of the in-plane phase difference of "RETS-100", nx-ny can also be calculated from the thickness information of the optically effective film A.
[0568] In this specification, nx-ny and Re are the average values of 16 measured values excluding the minimum and maximum values from 18 measured values. In this specification, the measurement site is selected from any site without defects such as damage and dirt.
[0569] When polarized light passes through a film having birefringence, rainbow spots can be observed on the film. Rainbow spots are rainbow-colored spots that reduce the visual recognition of the film. Polarized light is, for example, image light emitted from a liquid crystal display element or an organic EL display element including a reflection suppression functional layer based on polarization control.
[0570] From the perspective of suppressing rainbow spots of the optical film A and improving visibility, the in-plane retardation of the optical film A may be 3,000 nm or more, 4,000 nm or more, or 5,000 nm or less, or 1,500 nm or less, 1,450 nm or less, or 1,200 nm or less.
[0571] If the in-plane phase difference of the optical effect film A is 3,000nm or more, the rainbow spots can be effectively made less obvious. It is speculated that this is based on the following reasons. It is speculated that the reason for the rainbow spots is that the light in the polarization state passes through the film with a deviation in the in-plane phase difference, and then the polarization state changes. As a result, the greater the in-plane phase difference of the optical effect film A, the greater the change in the visible light transmittance of each wavelength relative to the change in the in-plane phase difference. In addition, the larger the in-plane phase difference, the easier it is for light of multiple wavelengths to pass through, so the light that passes through is mixed and easier to be visually recognized. That is, even if there is a deviation in the in-plane phase difference, the visible light transmittance of each wavelength also changes greatly, so even if the transmittance of a certain wavelength becomes lower, the transmittance of other wavelengths also becomes higher. Therefore, the change in the mixed color of the transmitted light is difficult to be visually recognized in the visual view. If the in-plane phase difference of the optical film A is 3,000 nm or more, the change in the visible light transmittance of each wavelength corresponding to the in-plane phase difference becomes larger, and even if the visible light transmittance changes due to the deviation of the in-plane phase difference, it will be mixed and visually recognized, and it is difficult to visually recognize the color change. That is, the rainbow spot can be effectively made less obvious. In addition, from the perspective of suppressing rupture and tearing during stretching, the in-plane phase difference of the optical film A can be less than 30,000 nm, less than 25,000 nm, less than 20,000 nm, or less than 15,000 nm.
[0572] In addition, if the in-plane phase difference of the optical film A is less than 1,500nm, the rainbow spots can be effectively made inconspicuous. It is speculated that this is based on the following reasons. The smaller the in-plane phase difference of the optical film A, the smaller the change in the visible light transmittance of each wavelength relative to the change in the in-plane phase difference. That is, even if there is a deviation in the in-plane phase difference, the visible light transmittance of each wavelength hardly changes. Therefore, if the deviation of the in-plane phase difference is small enough, rainbow spots that can be visually confirmed will not be generated. Therefore, if the in-plane phase difference of the optical film A is less than 1,500nm, the change in the visible light transmittance of each wavelength corresponding to the in-plane phase difference is sufficiently small, and the rainbow spots caused by the deviation of the in-plane phase difference can be effectively made inconspicuous. In addition, from the perspective of suppressing the so-called black screen, the in-plane phase difference of the optical film A can be more than 50nm, more than 100nm, more than 150nm, more than 200nm, more than 250nm, or more than 300nm. Here, the black screen refers to the phenomenon that when a user wears polarized sunglasses to observe, for example, a liquid crystal display device, the display screen becomes darker depending on the angle.
[0573] In the third embodiment, the refractive index difference "nx-ny" (hereinafter also referred to as "Δn") may be greater than 0.040, or greater than 0.050. If Δn is greater than 0.040, the thickness of the optically effective film A required to obtain the desired in-plane phase difference can be reduced. Δn may be less than 0.250, or less than 0.200. If Δn is less than 0.250, there is no need to over-stretch the film, and the rupture and tearing of the film can be suppressed.
[0574] In the third embodiment, Δn may be less than 0.040. If Δn is less than 0.040, rainbow spots caused by in-plane phase difference can be easily suppressed. Δn may be greater than 0.005, greater than 0.008, or greater than 0.010. If Δn is greater than 0.005, black screens can be easily suppressed.
[0575] The optical film A is preferably a stretched film. The stretched film may be a uniaxially stretched film or a biaxially stretched film. The biaxial stretching may be a stepwise biaxial stretching or a simultaneous biaxial stretching.
[0576] As an example, an optical film A having an in-plane phase difference of 3,000 nm or more and 30,000 nm or less is obtained by stepwise biaxial stretching as follows: a resin composition containing polyester is melted and extruded into a sheet to obtain an unstretched film; the unstretched film is stretched in the flow direction and then stretched in the width direction of the film.
[0577] The stretching in the flow direction can be performed, for example, by utilizing the difference in the peripheral speed of the roller. The stretching ratio in the flow direction can be 1.1 times or more, or 1.2 times or more. The stretching ratio in the flow direction can be 2.5 times or less, or 2.0 times or less, or 1.8 times or less.
[0578] From the perspective of suppressing the deviation of optical characteristics such as in-plane phase difference, the stretching temperature during stretching in the flow direction may be higher than the glass transition temperature of the polyester and lower than the glass transition temperature + 100° C. In the case of PET, the stretching temperature may be higher than 70° C., higher than 80° C., lower than 140° C., or lower than 130° C.
[0579] The stretching in the width direction can be carried out using a tentering method, for example. The stretching ratio in the width direction can be 2.5 times or more, or 3.0 times or more. The stretching ratio in the width direction can be 6.0 times or less, or 5.5 times or less. If the stretching ratio in the width direction is 6.0 times or less, the transparency of the film is excellent. If the stretching ratio in the width direction is 2.5 times or more, the necessary stretching tension is obtained, the birefringence becomes larger, and the desired in-plane phase difference is easily obtained. It is preferred that the stretching ratio in the width direction is higher than the stretching ratio in the flow direction.
[0580] The stretching temperature during the stretching in the width direction may be above the glass transition temperature of the polyester and below the glass transition temperature + 120°C. In the case of PET, the stretching temperature may be above 80°C, above 90°C, below 160°C, or below 150°C. The stretching temperature during the stretching in the width direction preferably increases as it goes from the upstream to the downstream. Specifically, when the stretching section in the width direction is divided into two parts, the difference between the temperature in the upstream and the temperature in the downstream may be above 5°C, above 20°C, or above 30°C. In the case of PET, the stretching temperature in the first stage may be above 80°C, above 90°C, below 120°C, or below 110°C.
[0581] In order to impart dimensional stability to the film subjected to stepwise biaxial stretching, it is preferred to perform heat treatment in a tenter at a temperature above the stretching temperature and below the melting point of the polyester. The temperature during the heat treatment may be 120°C or above, 180°C or above, 260°C or below, or 250°C or below.
[0582] The film which has been gradually biaxially stretched is heat treated and then rolled up after being cooled to room temperature.
[0583] As required, relaxation treatment may be performed during heat treatment and / or cooling. From the perspective of suppressing the deviation of optical properties, the relaxation rate during heat treatment may be 0.5% or more, 0.8% or more, 5% or less, or 3% or less. From the perspective of suppressing the deviation of optical properties, the relaxation rate during cooling may be 0.5% or more, 0.8% or more, 3% or less, or 2% or less. From the perspective of the dimensional stability of the film, the temperature of the relaxation treatment during cooling may be 80°C or more, 90°C or more, 150°C or less, or 130°C or less.
[0584] As an example, an optically effective film A having an in-plane phase difference of less than 1,500 nm is obtained by changing the stretching ratio as follows in the above-mentioned stepwise biaxial stretching. The stretching ratio in the flow direction can be 2.5 times or more, or 3.0 times or more. The stretching ratio in the flow direction can be 6.0 times or less, or 5.5 times or less. From the perspective of adjusting the in-plane phase difference to less than 1,500 nm, the stretching ratio in the width direction can be 80% or more and 120% or less, or 90% or more and 110% or less relative to the stretching ratio in the flow direction.
[0585] Polyester is excellent in transparency, heat resistance, and mechanical properties, and its in-plane phase difference can be controlled within a desired range by stretching.
[0586] As a method for controlling the in-plane phase difference of the optical effect film A to be 3,000 nm or more and 30,000 nm or less, there is a method of appropriately setting the stretching ratio, the stretching temperature, and the thickness of the produced optical effect film A. Specifically, the larger the stretching ratio ratio, the larger the in-plane phase difference. The lower the stretching temperature, the larger the in-plane phase difference. The larger the thickness, the larger the in-plane phase difference. The closer the stretching ratio ratio is to 1, the smaller the in-plane phase difference. The higher the stretching temperature, the smaller the in-plane phase difference. The smaller the thickness, the smaller the in-plane phase difference.
[0587] As a method for controlling the in-plane phase difference of the optical effect film A to be less than 1,500 nm, there is a method of appropriately setting the stretch ratio ratio during biaxial stretching, the stretching temperature, and the thickness of the produced optical effect film A. Specifically, the closer the stretch ratio ratio is to 1, the smaller the in-plane phase difference is. The higher the stretching temperature, the smaller the in-plane phase difference is. The smaller the thickness, the smaller the in-plane phase difference is. The larger the stretch ratio ratio, the larger the in-plane phase difference is. The lower the stretching temperature, the larger the in-plane phase difference is. The larger the thickness, the larger the in-plane phase difference is.
[0588] (Maximum strain along the principal axis of orientation)
[0589] In the optical film A, the maximum strain of the orientation axis measured by a microwave transmission type molecular orientation meter can be 7° or less, 6° or less, 5° or less, or 4° or less. A surface plate for an image display device having such a film can suppress, for example, light leakage during black display and a decrease in the visual recognition of the product caused by a change in display color due to a phase difference. The maximum strain of the orientation axis is 0° or more, and the lower the better, and there is no particular limitation.
[0590] The maximum strain of the main axis of orientation can be adjusted to be below the upper limit value by adjusting the temperature and stretching ratio in the flow direction stretching, the temperature and stretching ratio in the width direction stretching, and the temperature of the heat treatment during film production.
[0591] The maximum strain of the orientation axis can be measured as follows. When the film shape is in the form of a roll, a rectangular film with a length of 1000 mm in the mechanical direction and a full width in the width direction is cut out from the roll-shaped optical film A. Based on the central portion of the width direction of the film, a plurality of 100 mm square films are cut out at intervals of 300 mm in the width direction. The sides of the square film are parallel to the mechanical direction and the width direction, respectively. When the film shape is in the form of a sheet, a rectangle with the largest area inscribed in the sample shape is drawn, and a 100 mm square film with two sides shared with the vertices of the rectangle is cut out from four vertices. For the cut sample film, the molecular orientation direction (orientation axis) of each is determined using a microwave transmission type molecular orientation meter. The width direction of the film is set to 0 °, and when the molecular orientation angle is less than 45 ° based on the width direction, the difference with 0 ° is obtained, and when it is greater than 45 °, the difference with 90 ° is obtained. The molecular orientation angle with the largest absolute value is taken as the maximum value, and it is taken as the maximum strain of the orientation axis. As a microwave transmission type molecular orientation meter, a molecular orientation meter (MOA-2001A) manufactured by Kanzaki Paper Industries, Ltd. was used.
[0592] (Total Light Transmittance and Haze)
[0593] The total light transmittance of the optical effect film A may be 70% or more, 75% or more, 80% or more, 85% or more, or 88% or more. The higher the total light transmittance of the optical effect film A, the more preferred it is, and it may be 99% or less, 98% or less, or 95% or less. The total light transmittance is measured in accordance with JIS K7361-1:1997.
[0594] The haze of the optical effect film A may be 3.0% or less, 2.5% or less, 2.0% or less, 1.5% or less, or 1.0% or less. The lower the haze of the optical effect film A, the more preferred it is, and it may be 0.1% or more, 0.2% or more, or 0.3% or more. The haze is measured in accordance with JIS K7136:2000.
[0595] (Martens hardness)
[0596] The Martens hardness of at least one surface of the optically effective film A may be 110 N / mm 2 Above 170N / mm 2 Below. Martens hardness is 110N / mm 2 The above films have high hardness and excellent scratch resistance and wear resistance. Martens hardness is 170N / mm 2 The following films are excellent in foldability. The Martens hardness can be adjusted by aligning the molecular orientation by stretching the film.
[0597] The Martens hardness of at least one surface of the optically effective film A may be 115 N / mm 2 Above, can be 120N / mm 2 Above, can be 125N / mm 2 Above, can be 130N / mm 2 Above, can be 135N / mm 2 Above, 140N / mm is also possible 2 The Martens hardness of at least one surface of the optical effect film A may be 165 N / mm 2 Below, 160N / mm is also possible 2 the following.
[0598] In the third embodiment, it is preferred that at least one of the first and second surfaces of the optically effective film A has the above-mentioned Martens hardness, and it is more preferred that both the first and second surfaces have the above-mentioned Martens hardness. In this specification, the Martens hardness refers to the average value of 20 measured values after removing the minimum and maximum values from the 22 measured values. In this specification, the measurement site is selected from any site without defects such as damage and dirt.
[0599] The standard deviation 3σ of the Martens hardness of at least one surface of the optically effective film A is preferably 45 N / mm 2 Below. The standard deviation of Martens hardness is 45N / mm 2 The following films have excellent foldability. From the perspective of foldability, the standard deviation can be 40 N / mm 2 Below, can be 35N / mm 2 Below, can be 30N / mm 2 Below, can be 25N / mm 2 Below, 20N / mm is also possible 2 The smaller the standard deviation, the better, and it can be 1N / mm 2 Above, 5N / mm is also possible 2 The standard deviation can be adjusted by the temperature during film formation.
[0600] In the third embodiment, at least one of the first and second surfaces of the optically effective film A preferably has the standard deviation of the Martens hardness, and more preferably both the first and second surfaces have the standard deviation of the Martens hardness. In this specification, the standard deviation of the Martens hardness refers to the standard deviation of 20 measured values.
[0601] In this specification, the Martens hardness is measured by nanoindentation. First, the indentation depth h (nm) corresponding to the indentation load F (N) is continuously measured to make a load-removal curve. The "load-removal curve" is sometimes also referred to as a "load-displacement curve". The "maximum indentation depth hmax" is analyzed according to the load curve, and then the projected area AC (mm2) at hmax is analyzed. The projected area AC refers to the area where the indenter contacts the optical action film A. The Martens hardness HM (the following formula (1)) can be calculated as the value obtained by dividing the maximum indentation load Pmax (N) by the projected area AC.
[0602] HM=Pmax / AC···(1)
[0603] Here, AC is the contact projection area corrected for the curvature of the indenter tip in the apparatus using a standard method.
[0604] The Martens hardness can be measured using an apparatus capable of performing a nanoindentation method. As such an apparatus, a "PICODENTOR HM500" manufactured by Fischer Instruments can be used.
[0605] The Martens hardness is measured under the following conditions.
[0606] <Measurement conditions>
[0607] ·Indenter used: Vickers indenter (diamond-shaped quadrangular hammer, model: VV005, Fischer Instruments)
[0608] · Pressing condition: Maximum load
[0609] Maximum pressing load: 20mN
[0610] Load application time: 10 seconds
[0611] Holding time: 5 seconds at maximum press load
[0612] Load unloading time: 10 seconds
[0613] · Sample setting table: Suction table (the suction table uses SMC model "SP2130-AD")
[0614] (Elastic deformation power)
[0615] The elastic deformation power of at least one surface of the optical effect film A may be 60% or more and 70% or less. A film having an elastic deformation power of 60% or more has excellent foldability. A film having an elastic deformation power of 70% or less has excellent hardness.
[0616] The elastic deformation power can be calculated by calculating the areas of the indentation work region, elastic work region, and plastic work region from the "load-removal curve" prepared when measuring the Martens hardness, and then using the following formula.
[0617] Elastic deformation power [%] = (area of elastic work region / area of compression work region) × 100
[0618] In this specification, the elastic deformation power refers to the average value of 20 measurement values excluding the minimum and maximum values from the 22 measurement values. In this specification, the measurement site is selected from any site without defects such as damage and dirt.
[0619] The standard deviation 3σ of the elastic deformation power is preferably 10% or less. The film having a standard deviation of the elastic deformation power of 10% or less has excellent hardness. The smaller the standard deviation, the more preferred it is, and it can be 1% or more, or 2% or more. The standard deviation can be adjusted by the temperature during film formation.
[0620] In the third embodiment, it is preferred that at least one of the first and second surfaces of the optically effective film A has the above-mentioned elastic deformation power, and it is more preferred that both the first and second surfaces have the above-mentioned elastic deformation power. In the third embodiment, it is preferred that at least one of the first and second surfaces of the optically effective film A has the standard deviation of the above-mentioned elastic deformation power, and it is more preferred that both the first and second surfaces have the standard deviation of the above-mentioned elastic deformation power.
[0621] (Loss tangent (tanδ))
[0622] The peak temperature of the loss tangent (tan δ) in the optical effect film A may be 90° C. or higher and 160° C. or lower. Such a film has excellent processability when heated. The peak temperature of tan δ may be 92° C. or higher, 94° C. or higher, 96° C. or higher, or 100° C. or higher. The peak temperature of tan δ may be 160° C. or lower, 155° C. or lower, or 150° C. or lower.
[0623] The peak top temperature of tan δ usually corresponds to the glass transition temperature of the polyester contained in the optical effect film A. Therefore, by adjusting the glass transition temperature of the polyester, the peak top temperature of tan δ can be adjusted to the above range.
[0624] Tan δ is measured using a dynamic viscoelasticity measuring device (DMA). The temperature at which tan δ reaches a maximum is defined as the peak temperature of tan δ of the optical effect film A. When two or more maximum values of tan δ are observed, the value on the lowest temperature side is adopted. The measurement conditions are as follows. Measuring device: Rheogel-E4000 (manufactured by UBM Co., Ltd.), measurement sample: width 5 mm × length 25 mm, frequency: 10 Hz, distance between chucks: 10 mm, measurement temperature range: 25°C to 250°C, heating rate: 2°C / min.
[0625] (Crystallinity)
[0626] The crystallinity of the optical film A may be 85% or less. Such a film has good interlayer adhesion when the functional layers are stacked. From the perspective of the mechanical strength of the film, the crystallinity of the optical film A may be 60% or more, 65% or more, or 70% or more.
[0627] The crystallinity of the optical effect film A may exceed 85%. Such a film has a good pencil hardness. From the perspective of the pencil hardness of the film, the crystallinity of the optical effect film A may be 88% or more, or 90% or more. The crystallinity of the optical effect film A may be 100% or less, 99% or less, or 98% or less.
[0628] The crystallinity of the optical effect film A is a value measured by an X-ray diffraction method.
[0629] The measurement conditions and calculation method of the crystallinity are as follows.
[0630] (Measurement conditions)
[0631] Determination method: 2θ / θ determination
[0632] Installation: Rigaku Manufacturing Smart Lab 9kW
[0633] X-ray source: Cu-Kα45kV-200mA
[0634] Measuring range: 10~50deg
[0635] Step size: 0.020deg
[0636] Measuring time: 4.0deg / min
[0637] (Calculation method)
[0638] The crystallinity was calculated based on the peak shape fitting method from the formula: crystallinity (%) = peak area of crystalline substance / (peak area of crystalline substance + peak area of amorphous substance) × 100.
[0639] The crystallinity of the optical effect film A can be controlled, for example, by the stretching ratio and the stretching temperature. Specifically, the greater the stretching ratio, the greater the crystallinity. The smaller the stretching ratio, the smaller the crystallinity.
[0640] (Gas barrier properties)
[0641] In the third embodiment, the optically effective film has excellent gas barrier properties.
[0642] The water vapor transmission rate of the optical film measured in accordance with JIS K7129-2:2019 at a temperature of 40°C and a humidity of 90% RH can be 20 g / (m 2 ·24hr) or less, can be 15g / (m 2 ·24hr) or less, or 10g / (m 2 The lower the water vapor permeability of the optical film, the better, and it can be 2 g / (m 2 ·24hr) or more, or 3g / (m 2 The water vapor transmission rate can be measured using a water vapor transmission rate measuring device ("PERMATRAN" manufactured by Modern Controls).
[0643] The oxygen permeability of the optical film measured in accordance with JIS K7126-2:2006 at a temperature of 25°C and a humidity of 50% RH may be 100 cc / (m 2 ·24hr·atm) or less, can be 80cc / (m 2 ·24hr·atm) or less, or 50cc / (m 2 The oxygen permeability of the optical film is preferably as low as possible, and may be 5cc / (m 2 ·24hr·atm) or more, or 7cc / (m 2 The oxygen permeability can be measured using an oxygen permeability measuring device ("OX-TRAN 10 / 50A") manufactured by Modern Controls.
[0644] <Adhesive layer>
[0645] The optically functional film of the third embodiment of the present disclosure may be an easily adhesive film having a polyester film and an easily adhesive layer provided on the polyester film. The easily adhesive layer may be provided on only one of the first and second surfaces of the polyester film, or may be provided on both the first and second surfaces.
[0646] The cross section of the highly adhesive film according to the third embodiment of the present disclosure is Figure 4The cross-section of the highly adhesive film 1 shown is the same. Figure 4 This diagram also corresponds to a cross-sectional view showing the easily adhesive film 1 according to the third embodiment of the present disclosure. Figure 4 The easily adhesive film 1 includes a polyester film 4 and an easily adhesive layer 6 in this order. The easily adhesive layer 6 is provided on the first surface 4a of the polyester film 4.
[0647] As the description of the easy adhesion layer in the third embodiment of the present disclosure, the description of the easy adhesion layer in the first embodiment of the present disclosure can be applied unless there is any contradiction.
[0648] The easy-adhesive layer containing a resin derived from a biomass material has a high environmental contribution, and has a high affinity with a polyester film containing a biomass polyester and a high ability to follow the shape of the film, so the optical film having such an easy-adhesive layer has excellent processability. The optical film having an easy-adhesive layer containing a resin derived from a fossil fuel has excellent adhesion durability in a high temperature and high humidity environment.
[0649] In the third embodiment, the biomass degree of the easy adhesion layer may be 10% or more, 12% or more, 15% or more, or 18% or more. In the third embodiment, the biomass degree of the easy adhesion layer may be 98% or less, 90% or less, 80% or less, 70% or less, 60% or less, or 50% or less. By determining the biomass degree of the resin constituting the easy adhesion layer and determining it as a raw material, the biomass degree of the easy adhesion layer can be determined in advance, and the quality of the optical effect film can also be controlled.
[0650] The easy-adhesion layer may further contain the above-mentioned bluing agent.
[0651] Based on the mass of the easy-adhesive layer, the content of the bluing agent in the easy-adhesive layer may be 10 wtppm or more, 50 wtppm or more, 100 wtppm or more, 200 wtppm or more, 300 wtppm or more, 400 wtppm or more, 500 wtppm or more, 1,000 wtppm or more, 2,000 wtppm or more, 3,000 wtppm or more, or 4,000 wtppm or more. The easy-adhesive film having such an easy-adhesive layer has a small yellow tint.
[0652] Based on the mass of the easy-adhesive layer, the content of the bluing agent in the easy-adhesive layer may be 20,000 wtppm or less, 18,000 wtppm or less, 15,000 wtppm or less, 13,000 wtppm or less, 10,000 wtppm or less, or 8,000 wtppm or less. The easy-adhesive film having such an easy-adhesive layer has a good color tone and shows a high total light transmittance and low haze.
[0653] <Functional layer>
[0654] The optically functional film of the third embodiment of the present disclosure may be an optical layered body having a polyester film and a functional layer disposed on the polyester film. The optical layered body may have an easy-adhesion layer between the polyester film and the functional layer. The functional layer may be disposed on one side of the polyester film or on both sides.
[0655] The cross section of the optical layered body according to the third embodiment of the present disclosure is Figure 5 The cross-section of the optical layered body 3 shown is the same. That is, Figure 5 This diagram also corresponds to a cross-sectional view showing the optical layered body 3 according to the third embodiment of the present disclosure. Figure 5 The optical layered body 3 includes a polyester film 4, an easily adhesive layer 6, and a functional layer 8 in this order. The easily adhesive layer 6 and the functional layer 8 are provided on the first surface 4a of the polyester film 4.
[0656] The total light transmittance of the optical layered body may be 50% or more, 60% or more, 70% or more, 80% or more, 85% or more, or 90% or more. The higher the total light transmittance of the optical layered body film, the more preferred it is, and it may be 99% or less, 98% or less, or 95% or less. The total light transmittance is measured in accordance with JIS K7361-1:1997.
[0657] The haze of the optical layered body may be 10.0% or less, 7.0% or less, 5.0% or less, 4.0% or less, or 3.0% or less. The haze of the optical layered body may be 0.1% or more, 0.2% or more, or 0.3% or more. The haze is measured in accordance with JIS K7136:2000.
[0658] In the case of an optical layered body including a polyester film, an optional easy-adhesion layer, and a functional layer in this order, the total light transmittance and the haze were measured with the light incident surface being the polyester film surface.
[0659] The optical layered body according to the third embodiment of the present disclosure may include one functional layer or two or more functional layers. That is, two or more functional layers may be laminated on the polyester film via an easily adhesive layer as needed.
[0660] As the description of the functional layer in the third embodiment of the present disclosure, the description of the functional layer in the first embodiment of the present disclosure can be applied unless there is any contradiction.
[0661] Examples of the functional layer include the following (1) to (12).
[0662] (1) Hard coating
[0663] (2) Anti-glare layer
[0664] (3) Antifouling layer
[0665] (4) Multilayer structure having a hard coating layer and an anti-reflection layer in sequence
[0666] (5) A multilayer structure having a hard coat layer and an anti-glare layer in sequence
[0667] (6) A multilayer structure having a hard coating layer and an antifouling layer in sequence
[0668] (7) A multilayer structure having an anti-glare layer and an anti-reflection layer in sequence
[0669] (8) A multilayer structure having an anti-glare layer and an anti-fouling layer in sequence
[0670] (9) A multilayer structure having a hard coat layer, an anti-glare layer and an anti-reflection layer in this order
[0671] (10) Antistatic layer
[0672] (11) Conductive layer
[0673] (12) Phase difference layer
[0674] In the above (4) to (11), the left side indicates the layer located on the polyester film side.
[0675] Among the one or more functional layers, the functional layer in contact with the polyester film or the easy bonding layer preferably contains a cured product of an ionizing radiation curable component. The functional layer in contact with the polyester film or the easy bonding layer is preferably a hard coating layer. By making the functional layer in contact with the polyester film or the easy bonding layer contain a cured product of an ionizing radiation curable component, the pencil hardness of the optical layered body can be easily increased.
[0676] The functional layer may further contain the above-mentioned bluing agent.
[0677] Based on the mass of the functional layer, the content of the bluing agent in the functional layer can be 50 wtppm or more, 80 wtppm or more, or 100 wtppm or more. The optical layered body with such a functional layer has a small yellow tint. Based on the mass of the functional layer, the content of the bluing agent in the functional layer can be 600 wtppm or less, 550 wtppm or less, or 500 wtppm or less. The optical layered body with such a functional layer shows high total light transmittance and low haze.
[0678] In the third embodiment, the conductive layer contains a translucent resin as the above-mentioned binder resin and a plurality of conductive fibers arranged in the translucent resin. The conductive fiber refers to a substance having conductivity and a shape having a length that is sufficiently large compared to the thickness (for example, diameter). For example, a substance having conductivity and a length that is approximately 5 times or more of the thickness is contained in the conductive fiber. The conductive layer refers to a layer that contains a translucent resin and a plurality of conductive fibers arranged in the translucent resin and can be conductive from the surface. The fiber diameter of the conductive fiber is, for example, more than 10nm and less than 200nm. The fiber length of the conductive fiber is, for example, more than 30μm, and the upper limit is not particularly limited. As conductive fibers, for example, conductive carbon fibers, metal fibers such as metal nanowires, metal-coated organic fibers, metal-coated inorganic fibers, and carbon nanotubes can be cited.
[0679] Most of the conductive fibers may be present on the side close to the optical film from the position of half the thickness of the conductive layer. In this case, other conductive fibers are deposited on the above-mentioned majority of conductive fibers, and thus are also present on the side close to the surface from the position of half the thickness of the conductive layer, and are also present on the surface of the conductive layer. Thus, the conductive layer can be electrically conductive from its surface, and the conductive fibers are in contact with each other in the thickness direction of the conductive layer.
[0680] The functional layer is formed, for example, as follows. A curable composition is applied to a polyester film or an easy-adhesive layer at a desired thickness. When an organic solvent is used, the organic solvent is dried to remove the organic solvent to form a coating (uncured resin layer). The drying conditions are, for example, 40°C to 120°C and 10 seconds to 10 minutes. Next, when the curable composition contains a thermosetting component, the coating is heated at a temperature required for curing to cure it. When the curable composition contains an ionizing radiation curable component, the coating is irradiated with ionizing radiation to cure it. In this way, a functional layer can be formed.
[0681] The optically functional film of the third embodiment of the present disclosure is suitable as a film used in an image display device, specifically, various functional films such as a hard coat film, an antiglare film, an antireflection film, an antifouling film, an antistatic film, and a polarizer protective film.
[0682] [Polyester film]
[0683] In one embodiment, the third embodiment of the present disclosure relates to a polyester film containing polyester and a bluing agent. In one embodiment, the biomass degree of the polyester film is 10% or more, the total light transmittance of the polyester film is 70% or more, and the yellowness (YI) of the polyester film is -1.0 or more and 2.5 or less. The details of each component and physical property are as described above.
[0684] [Highly adhesive film]
[0685] In one embodiment, the third embodiment of the present disclosure relates to an adhesive film, which comprises a polyester film and an adhesive layer containing a bluing agent disposed on the polyester film. In one embodiment, the biomass degree of the adhesive film is 10% or more, the total light transmittance of the adhesive film is 70% or more, and the yellowness (YI) of the adhesive film is -1.0 or more and 2.5 or less. The details of each component and physical property are as described above.
[0686] [Surface panel for image display device]
[0687] Hereinafter, the optically functional film of the third embodiment of the present disclosure (including the above-mentioned easy-adhesion film and the optical layered body) is also referred to as "the optical component of the third embodiment of the present disclosure". As an application example of the optical component of the third embodiment of the present disclosure, for example, a surface plate for an image display device having a resin plate or a glass plate and the optical component of the third embodiment of the present disclosure arranged on the plate can be cited. The optical layered body is preferably arranged in such a manner that the surface of the functional layer side of the optical layered body faces the side opposite to the resin plate or the glass plate.
[0688] As the description of the surface plate in the third embodiment of the present disclosure, the description of the surface plate in the first embodiment of the present disclosure can be applied unless there is any contradiction.
[0689] [Polarizing plate]
[0690] As an application example of the optical component of the third embodiment of the present disclosure, for example, a polarizer can be cited, which includes: a polarizing element; a first transparent protective plate arranged on one surface of the polarizing element; and a second transparent protective plate arranged on the other surface of the polarizing element, wherein at least one of the first transparent protective plate and the second transparent protective plate is the optical component of the third embodiment of the present disclosure. The optical layered body is preferably arranged so that the surface on the functional layer side faces the side opposite to the polarizing element.
[0691] As the description of the polarizing plate in the third embodiment of the present disclosure, the description of the polarizing plate in the first embodiment of the present disclosure can be applied unless there is any contradiction.
[0692] A first transparent protective plate is disposed on one surface of the polarizing element, and a second transparent protective plate is disposed on the other surface. At least one of the first transparent protective plate and the second transparent protective plate is the optical component of the third embodiment of the present disclosure.
[0693] As the first transparent protective plate and the second transparent protective plate other than the optical component of the third embodiment of the present disclosure, for example, plastic films and glass plates can be cited. As plastic films, for example, polyester films, polycarbonate films, triacetyl cellulose films, cycloolefin polymer films and acrylic films can be cited, and in order to improve the mechanical strength, stretched films thereof are preferred. As glass plates, for example, glass plates made of glass such as alkali glass, nitride glass, soda-lime glass, borosilicate glass and lead glass can be cited.
[0694] The third embodiment of the present disclosure relates to, for example, the following [1] to
[18] .
[0695] [1] An optical film comprising polyester, wherein the biomass degree of the optical film is 10% or more, the total light transmittance of the optical film is 70% or more, and the yellowness index (YI) of the optical film is -1.0 or more and 2.5 or less.
[0696] [2] The optical effect film according to [1] above, wherein the optical effect film contains a bluing agent.
[0697] [3] The optical effect film according to [2] above, wherein the optical effect film is a polyester film containing the polyester and the bluing agent.
[0698] [4] The optical effect film according to [2] above, wherein the optical effect film comprises a polyester film containing the polyester and a color tone adjusting layer containing the bluing agent.
[0699] [5] The optically functional film according to [4] above, wherein the color tone adjustment layer is an easily adhesive layer.
[0700] [6] The optically functional film according to [5] above, wherein the resin constituting the easily adhesive layer is a resin derived from a biomass material.
[0701] [7] The optically functional film according to [5] above, wherein the resin constituting the easily adhesive layer is a resin derived from fossil fuels.
[0702] [8] The optically functional film according to [5] above, wherein the resin constituting the easily adhesive layer is a mixed resin of a resin derived from a biomass material and a resin derived from a fossil fuel.
[0703] [9] The optically functional film according to any one of [4] to [8] above, wherein the thickness of the polyester film is from 10 μm to 200 μm, and the thickness of the color tone adjustment layer is from 10 nm to 1,000 nm.
[0704]
[10] The optical effect film according to any one of [1] to [9] above, wherein the optical effect film contains a polyester derived from a biomass material.
[0705]
[11] The optical effect film according to any one of [1] to
[10] above, wherein the optical effect film contains polyester derived from a recycled material.
[0706]
[12] The optically effective film according to any one of [1] to
[11] above, wherein the Martens hardness of at least one surface of the optically effective film is 110 N / mm 2 Above 170N / mm 2 the following.
[0707]
[13] The optically effective film according to any one of [1] to
[12] above, wherein the elastic deformation power of at least one surface of the optically effective film is 60% to 70%.
[0708]
[14] The optically functional film according to any one of [1] to
[13] above, further comprising a functional layer.
[0709]
[15] The optically functional film according to
[14] above, wherein the functional layer contains a bluing agent.
[0710]
[16] A surface plate for an image display device, comprising: a resin plate or a glass plate; and the optically functional film according to any one of [1] to
[15] above, disposed on the plate.
[0711]
[17] An image display device comprising: a display element; and the optically functional film according to any one of [1] to
[15] above, disposed on the display element.
[0712]
[18] A polarizer comprising: a polarizing element; a first transparent protective plate disposed on one surface of the polarizing element; and a second transparent protective plate disposed on the other surface of the polarizing element, wherein at least one of the first transparent protective plate and the second transparent protective plate is the optically effective film described in any one of [1] to
[15] above.
[0713] Fourth Embodiment
[0714] A fourth embodiment of the present disclosure relates to an easily adhesive film.
[0715] Hereinafter, a fourth embodiment of the present disclosure will be described. In particular, the fourth embodiment of the present disclosure will be described centering on the differences from the first embodiment described above.
[0716] First, the problem to be solved by the fourth embodiment is described. For the purpose of improving the visual recognition of the image and suppressing the damage of the device surface, etc., the image display device has various optical layered bodies. Such optical layered bodies usually have a plastic film as an optical film and a functional layer provided on the film (for example, refer to Japanese Patent Publication No. 2007-046031 and Japanese Patent Publication No. 2012-256014).
[0717] As the above-mentioned plastic film, a polyester film such as a polyethylene terephthalate film is proposed. In this case, in order to make the adhesion between the film and the functional layer good, an easy-adhesion layer is sometimes provided between the polyester film and the functional layer. However, the inventors have found that the adhesion between the film and the functional layer is still insufficient.
[0718] In recent years, there has been a growing trend toward building a sustainable recycling-oriented society. From the perspective of carbon neutrality, there is a desire to move away from fossil fuels in the material field as well as in the energy field.
[0719] An object of a fourth embodiment of the present disclosure is to provide an easily adhesive film that can improve the adhesion of an optical layered body including a polyester film, an easily adhesive layer, and a functional layer in this order and can reduce environmental burden.
[0720] According to the fourth embodiment of the present disclosure, an easy-adhesive film is provided that can improve the adhesion of an optical layered body having a polyester film, an easy-adhesive layer, and a functional layer in sequence and can reduce environmental burden. In addition, an easy-adhesive film can be provided that has the same degree of optical and mechanical properties as when using polyester from fossil fuels even when using polyester from biomass materials.
[0721] [Highly adhesive film]
[0722] The easily adhesive film according to the fourth embodiment of the present disclosure includes a polyester film and an easily adhesive layer.
[0723] The easy-adhesion layer is disposed on the polyester film.
[0724] The easily adhesive film is an optical film. In this specification, an optical film refers to a film that can transmit light.
[0725] In the description of the adhesive film as an optical film of the fourth embodiment of the present disclosure described below, for the parts that can be constructed in the same manner as the optical film described in the first embodiment, the same symbols as those used in the first embodiment are sometimes used, and repeated descriptions are sometimes omitted. In addition, regarding the optical layered body, surface plate, image display device, and polarizer having an adhesive film as an optical film of the fourth embodiment of the present disclosure described below, for the parts that can be constructed in the same manner as the optical layered body, surface plate, image display device, and polarizer having the optical film described in the first embodiment, the same symbols as those used in the first embodiment are sometimes used for description, and repeated descriptions are sometimes omitted. In the case where it is obvious that the effects obtained in the first embodiment can also be obtained in the fourth embodiment, the description thereof is sometimes omitted. The description of the optical film, optical layered body, surface plate, image display device, and polarizer as the fourth embodiment of the present disclosure can be applied to the description of the optical film, optical layered body, surface plate, image display device, and polarizer of the first embodiment of the present disclosure as long as there is no contradiction.
[0726] In the following description of the fourth embodiment, when described as an “optical film”, it means the easily adhesive film of the fourth embodiment of the present disclosure unless otherwise specified.
[0727] like Figure 4 As shown, the polyester film 4 has a first surface 4a and a second surface 4b facing the first surface 4a. In the case where the first surface and the second surface are not particularly distinguished, they are sometimes simply referred to as "surfaces". The polyester film has a first direction and a second direction orthogonal to the first direction in the surface. The first direction is the longitudinal direction, flow direction or machine direction (MD) of the polyester film in the fourth embodiment. The second direction is the transverse direction or width direction (TD) of the polyester film in the fourth embodiment.
[0728] The cross section of the highly adhesive film according to the fourth embodiment of the present disclosure is Figure 4 The cross-section of the optical film 1 (highly adhesive film 1) shown is the same. That is, Figure 4 This diagram also corresponds to a cross-sectional view showing the easily adhesive film 1 according to the fourth embodiment of the present disclosure. Figure 4 The easily adhesive film 1 includes a polyester film 4 and an easily adhesive layer 6 in this order. The easily adhesive layer 6 is provided on the first surface 4a of the polyester film 4. The easily adhesive layer 6 may be provided only on one of the first surface 4a and the second surface 4b of the polyester film, or may be provided on both the first surface 4a and the second surface 4b.
[0729] <Polyester>
[0730] The polyester film contains polyester.
[0731] Polyester refers to a copolymer of at least a diol component and a dicarboxylic acid component. The polyester film preferably contains at least a polyester derived from a biomass material (hereinafter also referred to as "biomass polyester") as the polyester. By measuring the biomass polyester as the raw material of the film and determining it as the raw material of the film, the biomass degree of the film can be predetermined, and the quality of the film can also be controlled.
[0732] As polyester, specifically, polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polytrimethylene terephthalate (PTT), polyethylene naphthalate (PEN), polybutylene naphthalate (PBN) and polyethylene 2,5-furandicarboxylate (PEF) can be cited. Among these, PET is preferred because a polyester film with excellent mechanical strength can be obtained. As biomass polyester, specifically, polyesters produced using monomers derived from biomass materials as part or all of the raw material monomers (diol components and dicarboxylic acid components) in these polyesters can be cited.
[0733] The polyester film may contain one or more polyesters.
[0734] The polyester film may contain polyester derived from fossil fuels in addition to the biomass polyester. By making the polyester film contain at least a part of the biomass polyester, the amount of polyester derived from fossil fuels can be reduced compared with the conventional method, thereby reducing the environmental burden.
[0735] The adhesive film may contain polyester from recycled materials. The polyester contained in the adhesive film may be polyester from recycled materials and biomass polyester. A part of the polyester contained in the adhesive film may be polyester from recycled materials. In this case, the other part of the polyester contained in the adhesive film that is not polyester from recycled materials may be biomass polyester. The polyester from recycled materials may be recycled PET. The polyester from recycled materials may be a polyester derived from a raw material produced by recycling. More specifically, as a raw material for the polyester from recycled materials, at least any one of ethylene glycol from recycled materials or a dicarboxylic acid component from recycled materials may be used.
[0736] The content of the polyester in the polyester film may exceed 50% by mass, may be 60% by mass or more, may be 70% by mass or more, may be 80% by mass or more, may be 90% by mass or more, or may be 95% by mass or more.
[0737] The polyester film may contain additives. Examples of additives include ultraviolet light absorbers, light stabilizers, antioxidants, heat stabilizers, antistatic agents, slippery particles, heat-resistant polymer particles, alkali metal compounds, alkaline earth metal compounds, phosphorus compounds, flame retardants, anti-gelling agents, and surfactants. The polyester film may contain one or more additives.
[0738] <Polyester film structure>
[0739] The polyester film may have a single-layer structure or a multi-layer structure. A film having a single-layer structure is easy to control stretching. A film having a multi-layer structure is easy to obtain the effect brought about by changing the composition of each layer.
[0740] Examples of the polyester film having a multilayer structure include:
[0741] (1A) A multilayer film comprising two or three or more layers containing a biomass polyester as a main component;
[0742] (2A) a multilayer film comprising a layer containing a biomass polyester as a main component and a layer containing a polyester derived from a fossil fuel as a main component;
[0743] (3A) a multilayer film comprising, in order, a layer containing a biomass polyester as a main component, a layer containing a polyester derived from a fossil fuel as a main component, and a layer containing a biomass polyester as a main component;
[0744] (4A) a multilayer film comprising, in order, a layer containing a biomass polyester as a main component, a layer containing a biomass polyester as a main component, and a layer containing a polyester derived from a fossil fuel as a main component;
[0745] (5A) A multilayer film comprising, in this order, a layer containing a polyester derived from fossil fuel as a main component, a layer containing a biomass polyester as a main component, and a layer containing a polyester derived from fossil fuel as a main component.
[0746] Examples of the polyester film having a multilayer structure include:
[0747] (1B) A multilayer film having two or three or more layers with a biomass degree of 10% or more;
[0748] (2B) A multilayer film comprising a layer having a biomass degree of 10% or more and a layer having a biomass degree of less than 10%;
[0749] (3B) a multilayer film comprising, in order, a layer having a biomass degree of 10% or more, a layer having a biomass degree of less than 10%, and a layer having a biomass degree of 10% or more;
[0750] (4B) a multilayer film comprising, in order, a layer having a biomass degree of 10% or more, a layer having a biomass degree of 10% or more, and a layer having a biomass degree of less than 10%;
[0751] (5B) A multilayer film having, in order, a layer having a biomass degree of less than 10%, a layer having a biomass degree of 10% or more, and a layer having a biomass degree of less than 10%. In the multilayer films of (1B) to (5B), the biomass degree of the film as a whole is 10% or more.
[0752] The multilayer films of (1A) and (1B) have high environmental contributions. The multilayer films of (2A) to (4A) and (2B) to (4B) have high environmental contributions and excellent stretchability. The multilayer films of (5A) and (5B) have high environmental contributions and excellent stretchability, and can also suppress the influence of impurities that can be precipitated from biomass polyester on the functional layer laminated on the adhesive film.
[0753] The thickness of the highly adhesive film may be 10 μm or more, 15 μm or more, 20 μm or more, 25 μm or more, or 30 μm or more. Such highly adhesive films have excellent mechanical strength. The thickness of the polyester film is also the same.
[0754] The thickness of the adhesive film may be 200 μm or less, 180 μm or less, 160 μm or less, 140 μm or less, 120 μm or less, or 100 μm or less. Such an adhesive film has excellent bending resistance. The thickness of the polyester film is also the same.
[0755] In this specification, the thickness of the adhesive film and each layer is calculated by selecting 20 arbitrary positions of the cross-sectional photograph of the adhesive film obtained by scanning electron microscope (SEM) and calculating the average value of the 20 positions. The 20 positions are selected so that the positions are not biased to one side. The acceleration voltage and magnification of SEM are preferably set in accordance with the layer to be measured, with the acceleration voltage being 1 kV to 10 kV and the magnification being 20 to 7,000 times.
[0756] When forming a functional layer on the highly adhesive film, the film may be subjected to physical treatment such as corona discharge treatment and oxidation treatment to improve adhesion, or a coating called an anchor agent or a primer may be applied in advance.
[0757] The easy-adhesive film and the optical layered body described later can be a single-piece form cut into a specified size, or a long strip film can be rolled into a roll-shaped form. The size of the single piece, for example, has a maximum diameter of about 2 inches or more and 500 inches or less. The maximum diameter refers to the maximum length when any two points in the surface of the easy-adhesive film or the optical layered body are connected. For example, when the easy-adhesive film or the optical layered body is a rectangle, the diagonal of the rectangle becomes the maximum diameter. When the easy-adhesive film or the optical layered body is a circle, the diameter of the circle becomes the maximum diameter.
[0758] The width of the roll-shaped form can be, for example, 500 mm to 8,000 mm. The length of the roll-shaped form can be, for example, 100 m to 10,000 m. The easily adhesive film and optical layered body in a roll-shaped form can be cut into a single sheet for use according to the size of the image display device, etc. When cutting, it is preferred to remove the end of the roll where the physical properties are unstable.
[0759] The shape of the single sheet may be, for example, a polygon such as a triangle, a quadrilateral, or a pentagon, or may be a circle, or may be a random amorphous shape. More specifically, when the adhesive film and the optical layered body are quadrilaterals, the aspect ratio is not particularly limited as long as it does not cause problems as a display screen. For example, aspect:vertical = 1:1, 4:3, 16:10, 16:9, 2:1, 5:4, 11:8 may be cited.
[0760] <Properties of Highly Adhesive Film>
[0761] Hereinafter, physical properties that the highly adhesive film (optical film) preferably has will be described.
[0762] (Biomass degree)
[0763] The biomass degree of the adhesive film is 10% or more, 15% or more, 20% or more, or 25% or more. Such an adhesive film can reduce the environmental burden. The higher the biomass degree of the adhesive film, the more preferred it is, for example, 98% or less, 90% or less, 80% or less, 70% or less, 60% or less, 50% or less, or 40% or less.
[0764] When measuring the biomass content of the entire easily adhesive film, a sample may be prepared from the easily adhesive film. When measuring the biomass content of each layer in the easily adhesive film, a target layer may be separated from the easily adhesive film to prepare a sample.
[0765] (δq / δa)
[0766] The average value of δq / δa on the surface of the easily adhesive layer is 3.10 or less.
[0767] <Calculation of average value of δq / δa>
[0768] The 10 μm×10 μm region on the surface of the easy-adhesion layer was measured using the phase mode of an atomic force microscope (AFM). The distribution of the phase signal on the surface of the easy-adhesion layer was obtained by this measurement. The unit of the phase signal is [deg].
[0769] The arithmetic mean of the phase signal represented by the following equation 1 is denoted by δa.
[0770] The root mean square of the phase signal represented by the following equation 2 is denoted by δq.
[0771] In the following equations 1 and 2, orthogonal coordinate axes X and Y are set on a reference surface representing the average value of the phase signal, an axis orthogonal to the reference surface is set as the Z axis, and a curved surface of the phase signal is set as f(x, y). In the following equations 1 and 2, the size of the area for calculating δa and δq is set as Lx and Ly. In the following equations 1 and 2, Ar = Lx × Ly.
[0772] Seven 2 μm × 2 μm areas were selected from the 10 μm × 10 μm measurement area. δa, δq, and δq / δa at the seven locations were calculated. The average δq / δa was calculated based on the δq / δa at the five locations after removing the maximum and minimum values from the seven δq / δa.
[0773] The seven measurement areas may overlap partially, but the overlap ratio between any measurement area and the other six measurement areas is preferably 25% or less, more preferably 12% or less, and even more preferably 5% or less, based on area.
[0774] [Number 1]
[0775]
[0776] When the average value of δq / δa on the surface of the easy adhesion layer is 3.10 or less, the optical layered body including the polyester film, the easy adhesion layer and the functional layer in this order has particularly good adhesion. The technical significance of the average value of δq / δa on the surface of the easy adhesion layer is described below.
[0777] δa and δq are parameters related to the phase signal when a predetermined area on the surface of the easy-adhesion layer is measured using the phase mode of an atomic force microscope. The unit of the phase signal is [deg]. The phase signal represents the viscoelasticity of the surface of the easy-adhesion layer.
[0778] δa is the arithmetic mean of the phase signal in the specified area. δq is the root mean square of the phase signal in the specified area. The root mean square emphasizes the value larger than the average value compared to the arithmetic mean value. Therefore, an easy-to-adhesive layer with a small average value of δq / δa indicates that the phase signal is concentrated near the average value in the specified area. The phase signal indicates the viscoelasticity of the surface of the easy-to-adhesive layer, so an easy-to-adhesive layer with a small average value of δq / δa indicates that the change in viscoelasticity in the specified area is small.
[0779] As described above, the easy-adhesive layer with a small average value of δq / δa indicates that the change of viscoelasticity in a specified area is small. In addition, the film with an easy-adhesive layer with a small average value of δq / δa can make the optical layered body having a functional layer formed on the easy-adhesive layer have good adhesion. It is believed that the adhesion of the optical layered body becomes good due to the following reasons.
[0780] If other components are contacted on the functional layer of the optical layered body, a prescribed stress is generated. The stress is transmitted to the interface between the polyester film and the easy-adhesion layer via the functional layer and the easy-adhesion layer. The transmission mode of the stress is different according to the value of the viscoelasticity of the easy-adhesion layer. Therefore, when the change of the viscoelasticity in the surface of the easy-adhesion layer is large, the magnitude of the stress transmitted to the interface between the polyester film and the easy-adhesion layer is different according to the position in the surface. Therefore, when the average value of δq / δa of the easy-adhesion layer is large, it is easy to apply a large stress to the prescribed position in the surface, and it is easy to produce the interface peeling of the optical layered body. On the other hand, when the average value of δq / δa of the easy-adhesion layer is small, it is believed that the stress is dispersed in the surface, so the interface peeling of the optical layered body can be suppressed, so that the adhesion is good. The reason why the viscoelasticity of the easy-adhesion layer is different according to the position can consider the compatibility of the components constituting the easy-adhesion layer.
[0781] When the functional layer in contact with the easy bonding layer includes a cured product of an ionizing radiation curable component, the adhesion of the optical layered body is easily reduced. However, in an optical layered body in which the average value of δq / δa on the surface of the easy bonding layer is below the above value, even if the functional layer in contact with the easy bonding layer includes a cured product of an ionizing radiation curable component, the adhesion of the optical layered body can be easily improved.
[0782] The average value of δq / δa may be 3.10 or less, 3.00 or less, 2.80 or less, 2.60 or less, 2.40 or less, 2.20 or less, or 2.00 or less.
[0783] The smaller the average value of δq / δa is, the closer the viscoelasticity of the surface of the easy-adhesion layer is to homogeneity. When the viscoelasticity of the surface of the easy-adhesion layer is too homogeneous, it is difficult for the components of the functional layer to penetrate into the easy-adhesion layer, and sometimes it is difficult to improve the adhesion between the easy-adhesion layer and the functional layer. Therefore, the average value of δq / δa can be 1.20 or more, 1.25 or more, 1.30 or more, 1.40 or more, or 1.50 or more.
[0784] The average value of δq / δa on the surface of the easy-adhesion layer is a value in a predetermined area of 10 μm×10 μm. The proportion of the area with an average value of δq / δa of 3.10 or less in the total area of the surface of the easy-adhesion layer may be 80% or more, 90% or more, 95% or more, 98% or more, or 100%.
[0785] In this specification, δa can be calculated by the above formula 1. Formula 1 uses the formula of the arithmetic mean height of ISO 25178-2: 2012. In other words, in the formula of the arithmetic mean height of ISO 25178-2: 2012, the height is used as the data of the Z axis, but in Formula 1, the phase signal [deg] is used as the data of the Z axis instead of the height.
[0786] In this specification, δq can be calculated by the above formula 2. Formula 2 uses the formula for the root mean square height of ISO 25178-2: 2012. In other words, in the formula for the root mean square height of ISO 25178-2: 2012, the height is used as the data of the Z axis, but in Formula 2, the phase signal [deg] is used as the data of the Z axis instead of the height.
[0787] The average value of δq / δa can be calculated according to the following steps A1 to A4.
[0788] (A1) A 10 μm×10 μm region on the surface of the easy-adhesion layer is measured using a phase mode atomic force microscope. As an atomic force microscope, a product name “SPM-9600” manufactured by Shimadzu Corporation can be used.
[0789] (A2) Seven 2μm×2μm areas are selected from a measurement area of 10μm×10μm. The selected 2μm×2μm area is selected from an area where the maximum height of the amplitude measured by an atomic force microscope is less than 90nm. The maximum height is the maximum height Sz of ISO 25178-2:2012. By selecting a 2μm×2μm area from an area where Sz is less than 90nm, the influence of foreign matter and defects can be easily eliminated. The 7 areas are preferably selected in a non-overlapping manner, but they can also overlap with each other. It should be noted that when the measurement areas are repeated, the repetition ratio of any measurement area to the other 6 measurement areas is preferably 25% or less, more preferably 12% or less, and further preferably 5% or less on an area basis. In order to more easily eliminate the influence of foreign matter and defects, the selected 2μm×2μm area is preferably selected from an area where the arithmetic mean height of the amplitude measured by an atomic force microscope is less than 10nm. The arithmetic mean height is the arithmetic mean height Sa of ISO 25178-2:2012.
[0790] (A3) Calculate δa, δq and δq / δa in the selected 7 regions.
[0791] (A4) Based on the δq / δa at five locations excluding the maximum and minimum values among the δq / δa at seven locations, the average value of δq / δa is calculated.
[0792] In the easy-adhesion layer, the coefficient of variation of δq / δa calculated based on the δq / δa at the above five locations may be 0.040 or less. By making the coefficient of variation of δq / δa 0.040 or less, stress is more easily dispersed within the surface, and it is easier to make the adhesion good. The coefficient of variation of δq / δa may be 0.037 or less, or 0.035 or less.
[0793] When the coefficient of variation of δq / δa is too small, it may be difficult for the components of the functional layer to penetrate into the easy-adhesion layer, and it may be difficult to improve the adhesion between the easy-adhesion layer and the functional layer. Therefore, the coefficient of variation of δq / δa may be 0.010 or more, or 0.015 or more.
[0794] The ratio of the area where the coefficient of variation of δq / δa is 0.040 or less in the total area of the surface of the easy-adhesion layer may be 80% or more, 90% or more, 95% or more, 98% or more, or 100%.
[0795] (Total Light Transmittance and Haze)
[0796] The total light transmittance of the easy-adhesive film may be 70% or more, 75% or more, 80% or more, 85% or more, or 90% or more. The higher the total light transmittance of the easy-adhesive film, the more preferred it is, and it may be 99% or less, 98% or less, or 95% or less. The total light transmittance is measured in accordance with JIS K7361-1:1997.
[0797] The haze of the adhesive film may be 3.0% or less, 2.5% or less, 2.0% or less, 1.5% or less, or 1.0% or less. The lower the haze of the adhesive film, the more preferred it is, and it may be 0.1% or more, 0.2% or more, or 0.3% or more. The haze is measured in accordance with JIS K7136:2000.
[0798] (In-plane phase difference (Re))
[0799] The in-plane phase difference (Re) of the optical film is not particularly limited and can be 30,000 nm or less. In this specification, the "in-plane phase difference" is calculated by the formula: In-plane phase difference (Re) = (nx-ny) × T [nm]. "In-plane phase difference" is also called delay, and the unit is the unit of length. T in the above formula refers to the thickness of the optical film [nm].
[0800] When polarized light passes through a film having birefringence, rainbow spots can be observed on the film. Rainbow spots are rainbow-colored spots that sometimes reduce the visual recognition of the film. Polarized light is, for example, image light emitted from a liquid crystal display element or an organic EL display element including a reflection suppression functional layer based on polarization control.
[0801] From the perspective of suppressing rainbow spots of the optical film and improving visibility, the in-plane retardation of the optical film may be 3,000 nm or more, 4,000 nm or more, or 5,000 nm or less, or 1,500 nm or less, 1,450 nm or less, or 1,200 nm or less.
[0802] If the in-plane phase difference of the optical film is 3,000nm or more, the rainbow spots can be effectively made less obvious. It is speculated that this is based on the following reasons. It is speculated that the reason for the rainbow spots is that the light in the polarization state passes through the film with a deviation in the in-plane phase difference, and then the polarization state changes. As a result, the larger the in-plane phase difference of the optical film, the greater the change in the visible light transmittance of each wavelength relative to the change in the in-plane phase difference. In addition, the larger the in-plane phase difference, the easier it is for light of multiple wavelengths to pass through, so the light that passes through is mixed and easier to be visually recognized. That is, even if there is a deviation in the in-plane phase difference, the visible light transmittance of each wavelength also changes greatly, so even if the transmittance of a certain wavelength becomes low, the transmittance of other wavelengths also becomes high. Therefore, the change in the mixed color of the transmitted light is difficult to be visually recognized in the visual view. If the in-plane phase difference of the optical film is 3,000nm or more, the change in the visible light transmittance of each wavelength corresponding to the in-plane phase difference becomes large, and even if the visible light transmittance changes due to the deviation in the in-plane phase difference, it will be mixed and visually recognized, and it is difficult to visually recognize the change in color. In other words, rainbow spots can be effectively made less noticeable. In order to suppress cracking and tearing during stretching, the in-plane retardation of the optical film may be 30,000 nm or less, 25,000 nm or less, 20,000 nm or less, or 15,000 nm or less.
[0803] In addition, if the in-plane phase difference of the optical film is less than 1,500nm, the rainbow spots can be effectively made inconspicuous. It is speculated that this is based on the following reasons. The smaller the in-plane phase difference of the optical film, the smaller the change in the visible light transmittance of each wavelength relative to the change in the in-plane phase difference. That is, even if there is a deviation in the in-plane phase difference, the visible light transmittance of each wavelength hardly changes. Therefore, if the deviation of the in-plane phase difference is small enough, rainbow spots that can be visually confirmed will not occur. Therefore, if the in-plane phase difference of the optical film is less than 1,500nm, the change in the visible light transmittance of each wavelength corresponding to the in-plane phase difference is sufficiently small, and the rainbow spots caused by the deviation of the in-plane phase difference can be effectively made inconspicuous. In addition, from the perspective of suppressing the so-called black screen, the in-plane phase difference of the optical film can be more than 50nm, more than 100nm, more than 150nm, more than 200nm, more than 250nm, or more than 300nm. Here, the black screen refers to the phenomenon that when a user wears polarized sunglasses to observe, for example, a liquid crystal display device, the display screen becomes darker depending on the angle.
[0804] In the fourth embodiment, the refractive index difference "nx-ny" (hereinafter also referred to as "Δn") may be 0.040 or more, or 0.050 or more. If Δn is 0.040 or more, the thickness of the optical film required to obtain the desired in-plane phase difference can be reduced. Δn may be 0.250 or less, or 0.200 or less. If Δn is 0.250 or less, there is no need to over-stretch the optical film, and the cracking and tearing of the optical film can be suppressed.
[0805] In the fourth embodiment, Δn may be less than 0.040. If Δn is less than 0.040, rainbow spots caused by in-plane phase difference can be easily suppressed. Δn may be greater than 0.005, greater than 0.008, or greater than 0.010. If Δn is greater than 0.005, black screens can be easily suppressed.
[0806] The refractive index (nx) in the slow axis direction may be 1.580 or more, or 1.630 or more. The refractive index (nx) in the slow axis direction may be 1.780 or less, or 1.730 or less. The refractive index (ny) in the fast axis direction may be 1.550 or more, or 1.580 or more. The refractive index (ny) in the fast axis direction may be 1.760 or less, or 1.710 or less.
[0807] The optical film or polyester film is preferably a stretched film. The stretched film may be a uniaxially stretched film or a biaxially stretched film. The biaxial stretching may be a stepwise biaxial stretching or a simultaneous biaxial stretching.
[0808] As an example, an optical film having an in-plane phase difference of 3,000 nm or more and 30,000 nm or less is obtained by stepwise biaxial stretching as follows: a resin composition containing polyester is melted and extruded into a sheet to obtain an unstretched film; the unstretched film is stretched in the flow direction and then stretched in the width direction of the film.
[0809] The stretching in the flow direction can be performed, for example, by utilizing the difference in the peripheral speed of the roller. The stretching ratio in the flow direction can be 1.1 times or more, or 1.2 times or more. The stretching ratio in the flow direction can be 2.5 times or less, or 2.0 times or less, or 1.8 times or less.
[0810] As an example, an optical film having an in-plane phase difference of less than 1,500 nm is obtained by changing the stretching ratio as follows in the above-mentioned stepwise biaxial stretching. The stretching ratio in the flow direction can be 2.5 times or more, or 3.0 times or more. The stretching ratio in the flow direction can be 6.0 times or less, or 5.5 times or less. From the perspective of adjusting the in-plane phase difference to less than 1,500 nm, the stretching ratio in the width direction can be 80% or more and 120% or less, or 90% or more and 110% or less relative to the stretching ratio in the flow direction.
[0811] Polyester is excellent in transparency, heat resistance, and mechanical properties, and its in-plane phase difference can be controlled within a desired range by stretching.
[0812] As a method for controlling the in-plane phase difference of the optical film to be less than 1,500 nm, there is a method of appropriately setting the stretch ratio ratio during biaxial stretching, the stretching temperature, and the thickness of the produced optical film. Specifically, the closer the stretch ratio ratio is to 1, the smaller the in-plane phase difference is. The higher the stretching temperature, the smaller the in-plane phase difference is. The smaller the thickness, the smaller the in-plane phase difference is. The larger the stretch ratio ratio, the larger the in-plane phase difference is. The lower the stretching temperature, the larger the in-plane phase difference is. The larger the thickness, the larger the in-plane phase difference is.
[0813] (Crystallinity)
[0814] The crystallinity of the optical film may be 90% or less, 88% or less, 86% or less, or 85% or less. Such an optical film has good interlayer adhesion when the functional layers are stacked. From the perspective of the mechanical strength of the optical film, the crystallinity of the optical film may be 60% or more, 65% or more, or 70% or more.
[0815] The crystallinity of the optical film is a value measured by an X-ray diffraction method.
[0816] The measurement conditions and calculation method of the crystallinity are as follows.
[0817] (Measurement conditions)
[0818] Determination method: 2θ / θ determination
[0819] Installation: Rigaku Manufacturing Smart Lab 9kW
[0820] X-ray source: Cu-Kα45kV-200mA
[0821] Measuring range: 10~50deg
[0822] Step size: 0.020deg
[0823] Measuring time: 4.0deg / min
[0824] (Calculation method)
[0825] The crystallinity was calculated based on the peak shape fitting method from the formula: crystallinity (%) = peak area of crystalline substance / (peak area of crystalline substance + peak area of amorphous substance) × 100.
[0826] (Gas barrier properties)
[0827] In the fourth embodiment, the easily adhesive film has excellent gas barrier properties.
[0828] The water vapor transmission rate of the adhesive film measured in accordance with JIS K7129-2:2019 at a temperature of 40°C and a humidity of 90% RH can be 20 g / (m 2 ·24hr) or less, can be 15g / (m 2 ·24hr) or less, or 10g / (m 2 The lower the water vapor permeability of the adhesive film, the better, and it can be 2 g / (m 2 ·24hr) or more, or 3g / (m 2 The water vapor transmission rate can be measured using a water vapor transmission rate measuring device ("PERMATRAN" manufactured by Modern Controls).
[0829] The oxygen permeability of the highly adhesive film measured in accordance with JIS K7126-2:2006 at a temperature of 25°C and a humidity of 50% RH may be 100 cc / (m 2 ·24hr·atm) or less, can be 80cc / (m 2 ·24hr·atm) or less, or 50cc / (m 2 The oxygen permeability of the adhesive film is preferably as low as possible, and may be 5cc / (m 2 ·24hr·atm) or more, or 7cc / (m 2The oxygen permeability can be measured using an oxygen permeability measuring device ("OX-TRAN 10 / 50A") manufactured by Modern Controls.
[0830] <Adhesive layer>
[0831] As the resin constituting the easy bonding layer, thermoplastic resins such as polyester, polyurethane and (meth) acrylic resin and thermosetting resins can be enumerated, preferably thermoplastic resins. Among thermoplastic resins, preferably polyester and polyurethane, more preferably resins comprising these two components of polyester component and polyurethane component. These resins easily reduce the refractive index difference between polyester film and easy bonding layer.
[0832] The above-mentioned polyurethane component is easy to make the adhesion good, but it is sometimes difficult to enhance the strength of the coating film. Therefore, the resin constituting the easy-adhesion layer preferably contains two components, a polyester component and a polyurethane component. However, when the polyurethane component is too much relative to the polyester component, phase separation is likely to occur, so the average value of δq / δa and the coefficient of variation of δq / δa are likely to become larger. In addition, since the polyurethane component is soft, when the polyurethane component is too much, due to the difference in the cross-linking density within the surface, the average value of δq / δa and the coefficient of variation of δq / δa are likely to become larger. Therefore, the mass ratio of the resin containing the two components of the polyester component and the polyurethane component (polyester component: polyurethane component) can be 95:5~60:40, or 90:10~60:40.
[0833] The easily adhesive layer containing the resin derived from biomass material has a high environmental contribution, and has a high affinity with the polyester film containing biomass polyester and a high ability to follow the shape of the film, so the easily adhesive film having such an easily adhesive layer has excellent processability. The easily adhesive film having the easily adhesive layer containing the resin derived from fossil fuel has excellent adhesion durability in a high temperature and high humidity environment.
[0834] In the fourth embodiment, the biomass degree of the easy adhesion layer may be 10% or more, 12% or more, 15% or more, or 18% or more. In the fourth embodiment, the biomass degree of the easy adhesion layer may be 98% or less, 90% or less, 80% or less, 70% or less, 60% or less, or 50% or less. By determining the biomass degree of the resin constituting the easy adhesion layer and determining it as a raw material, the biomass degree of the easy adhesion layer can be determined in advance, and the quality of the easy adhesion film can also be controlled.
[0835] The glass transition temperature of the resin constituting the easy-adhesion layer may be 30° C. or higher, 50° C. or higher, or 70° C. or higher. The glass transition temperature of the resin may be 120° C. or lower, 110° C. or lower, or 90° C. or lower. The glass transition temperature is a midpoint glass transition temperature obtained by differential scanning calorimetry (DSC) in accordance with JIS K7121:2012.
[0836] If the glass transition temperature of the resin constituting the easy-adhesive layer is above 30°C, it is easy to suppress the easy-adhesive layer from flowing due to the heat during the process to generate internal stress, so it is easy to make the average value of δq / δa and the coefficient of variation of δq / δa within the above range. As the heat during the process, for example, the heat in the drying process of the coating liquid for the functional layer, the heat generated by heating when the optical layered body is attached to the polarizing element, etc. can be cited. If the glass transition temperature of the resin constituting the easy-adhesive layer is below 120°C, it is easy to suppress the stress caused by the difference in thermal behavior between the easy-adhesive layer and the polyester film due to the heat during the process, so it is possible to suppress the generation of cracks in the easy-adhesive layer due to stress. Therefore, if the glass transition temperature of the resin constituting the easy-adhesive layer is below 120°C, it is easy to make the average value of δq / δa and the coefficient of variation of δq / δa within the above range.
[0837] The drying time of the coating liquid for easy bonding layer can be less than 120 seconds, or less than 90 seconds. The drying time can be more than 15 seconds, or more than 20 seconds. The drying time can be adjusted by drying temperature and drying wind speed. If the drying time is less than 120 seconds, the components constituting the easy bonding layer can be suppressed to separate, and the mean value of δq / δa and the coefficient of variation of δq / δa can be easily made to be the above range. If the drying time is too short, the coating surface is sometimes rough and the optical properties are reduced.
[0838] The highly adhesive film of the fourth embodiment of the present disclosure is suitable as a film used in an image display device, specifically, as a base material for various functional films such as a hard coat film, an antiglare film, an antireflection film, an antifouling film, an antistatic film, and a polarizer protective film.
[0839] [Optical layered body]
[0840] As an application example of the adhesive film of the fourth embodiment of the present disclosure, there can be mentioned an optical layered body including the adhesive film of the fourth embodiment of the present disclosure and a functional layer provided on the adhesive layer of the film. The functional layer can be provided on one side of the adhesive film or on both sides.
[0841] The cross section of the optical layered body according to the fourth embodiment of the present disclosure is Figure 5 The cross-section of the optical layered body 3 shown is the same. That is, Figure 5This diagram also corresponds to a cross-sectional view showing the optical layered body 3 according to the fourth embodiment of the present disclosure. Figure 5 The optical layered body 3 includes a polyester film 4, an easily adhesive layer 6, and a functional layer 8 in this order. The easily adhesive layer 6 and the functional layer 8 are provided on the first surface 4a of the polyester film 4.
[0842] In the case of an optical layered body including a polyester film, an easily adhesive layer, and a functional layer in this order, the total light transmittance and the haze of the optical layered body were measured with the light incident surface being the polyester film surface.
[0843] <Functional layer>
[0844] The optical layered body according to the fourth embodiment of the present disclosure may include one functional layer or two or more functional layers. That is, two or more functional layers may be laminated on the polyester film via an easily adhesive layer.
[0845] Examples of the functional layer include the following (1) to (12).
[0846] (1) Hard coating
[0847] (2) Anti-glare layer
[0848] (3) Antifouling layer
[0849] (4) Multilayer structure having a hard coating layer and an anti-reflection layer in sequence
[0850] (5) A multilayer structure having a hard coat layer and an anti-glare layer in sequence
[0851] (6) A multilayer structure having a hard coating layer and an antifouling layer in sequence
[0852] (7) A multilayer structure having an anti-glare layer and an anti-reflection layer in sequence
[0853] (8) A multilayer structure having an anti-glare layer and an anti-fouling layer in sequence
[0854] (9) A multilayer structure having a hard coat layer, an anti-glare layer and an anti-reflection layer in this order
[0855] (10) Antistatic layer
[0856] (11) Conductive layer
[0857] (12) Phase difference layer
[0858] In the above (4) to (11), the left side indicates the layer located on the side of the easily adhesive film.
[0859] Among the one or more functional layers, the functional layer in contact with the easy bonding layer preferably comprises a cured product of an ionizing radiation curable component. The functional layer in contact with the easy bonding layer is preferably a hard coat layer. By making the functional layer in contact with the easy bonding layer comprise a cured product of an ionizing radiation curable component, the pencil hardness of the optical layered body can be easily increased.
[0860] In the fourth embodiment, the conductive layer contains a translucent resin as the above-mentioned binder resin and a plurality of conductive fibers arranged in the translucent resin. The conductive fiber refers to a substance having conductivity and a shape having a length that is sufficiently large compared to the thickness (for example, diameter). For example, a substance having conductivity and a length that is approximately 5 times or more of the thickness is contained in the conductive fiber. The conductive layer refers to a layer that contains a translucent resin and a plurality of conductive fibers arranged in the translucent resin and can be conductive from the surface. The fiber diameter of the conductive fiber is, for example, greater than 10nm and less than 200nm. The fiber length of the conductive fiber is, for example, greater than 30μm, and the upper limit is not particularly limited. As conductive fibers, for example, conductive carbon fibers, metal fibers such as metal nanowires, metal-coated organic fibers, metal-coated inorganic fibers, and carbon nanotubes can be cited.
[0861] Most of the conductive fibers may be present on the side close to the adhesive film from the position of half the thickness of the conductive layer. In this case, other conductive fibers are deposited on the above-mentioned majority of conductive fibers, and thus also exist on the side close to the surface from the position of half the thickness of the conductive layer, and also exist on the surface of the conductive layer. Thus, the conductive layer can be electrically conductive from its surface, and the conductive fibers are in contact with each other in the thickness direction of the conductive layer.
[0862] The functional layer is formed, for example, as follows. A curable composition is applied to the easy-adhesion layer at a desired thickness. When an organic solvent is used, the organic solvent is dried to remove the organic solvent to form a coating (uncured resin layer). The drying conditions are, for example, 40°C to 120°C and 10 seconds to 10 minutes. Next, when the curable composition contains a thermosetting component, the coating is heated at a temperature required for curing to cure it. When the curable composition contains an ionizing radiation curable component, the coating is irradiated with ionizing radiation to cure it. In this way, a functional layer can be formed.
[0863] A fourth embodiment of the present disclosure relates to, for example, the following [1] to
[13] .
[0864] [1] An adhesive film comprising a polyester film and an adhesive layer, wherein the polyester film contains polyester, the biomass degree of the adhesive film is 10% or more, the total light transmittance of the adhesive film is 70% or more, the average value of δq / δa on the surface of the adhesive layer is 3.10 or less, and the adhesive film is used to provide a functional layer on the adhesive layer.
[0865] <Calculation of average value of δq / δa>
[0866] The 10 μm×10 μm region on the surface of the easy-adhesion layer was measured using the phase mode of an atomic force microscope. The distribution of the phase signal on the surface of the easy-adhesion layer was obtained by the above measurement. The unit of the phase signal is [deg].
[0867] The arithmetic mean of the phase signal represented by the following equation 1 is denoted by δa.
[0868] The root mean square of the phase signal represented by the following equation 2 is denoted by δq.
[0869] (In the following equations 1 and 2, orthogonal coordinate axes X and Y are set on a reference surface representing the average value of the phase signal, an axis orthogonal to the reference surface is set as the Z axis, and a curved surface of the phase signal is set as f(x, y). In the following equations 1 and 2, the size of the region for calculating δa and δq is set as Lx and Ly. In the following equations 1 and 2, Ar = Lx × Ly.)
[0870] Seven 2 μm × 2 μm areas were selected from the 10 μm × 10 μm measurement area. δa, δq, and δq / δa at the seven locations were calculated. The average δq / δa was calculated based on the δq / δa at the five locations after removing the maximum and minimum values from the seven δq / δa.
[0871] [Number 2]
[0872]
[0873] [2] The highly adhesive film according to [1] above, wherein the polyester film contains a polyester derived from a biomass material.
[0874] [3] The highly adhesive film according to [1] or [2] above, wherein the highly adhesive film contains polyester derived from a recycled material.
[0875] [4] The highly adhesive film according to any one of [1] to [3] above, wherein at least one surface of the highly adhesive film has a Martens hardness of 110 N / mm 2 Above 170N / mm 2 the following.
[0876] [5] The highly adhesive film according to any one of [1] to [4] above, wherein the elastic deformation power of at least one surface of the highly adhesive film is 60% to 70%.
[0877] [6] The highly adhesive film according to any one of [1] to [5] above, wherein the degree of crystallinity of the highly adhesive film is 90% or less.
[0878] [7] The easily adhesive film according to any one of [1] to [6] above, wherein the resin constituting the easily adhesive layer is a resin derived from a biomass material.
[0879] [8] The easily adhesive film according to any one of [1] to [6] above, wherein the resin constituting the easily adhesive layer is a resin derived from fossil fuels.
[0880] [9] The adhesive film according to any one of [1] to [6] above, wherein the resin constituting the adhesive layer is a mixed resin of a biomass-derived resin and a fossil fuel-derived resin.
[0881]
[10] An optical layered body comprising: the easily adhesive film according to any one of [1] to [9] above; and a functional layer provided on the easily adhesive layer of the easily adhesive film.
[0882]
[11] A surface plate for an image display device, comprising: a resin plate or a glass plate; and the adhesive film according to any one of [1] to [9] or the optical layered body according to
[10] disposed on the plate.
[0883]
[12] An image display device comprising: a display element; and the highly adhesive film according to any one of [1] to [9] or the optical layered body according to
[10] , which is disposed on the display element.
[0884]
[13] A polarizing plate comprising: a polarizing element; a first transparent protective plate arranged on one surface of the polarizing element; and a second transparent protective plate arranged on the other surface of the polarizing element, wherein at least one of the first transparent protective plate and the second transparent protective plate is the highly adhesive film described in any one of [1] to [9] or the optical layered body described in
[10] .
[0885] Fifth Embodiment
[0886] A fifth embodiment of the present disclosure relates to an optical layered body.
[0887] Hereinafter, a fifth embodiment of the present disclosure will be described. In particular, the fifth embodiment of the present disclosure will be described centering on the differences from the first embodiment described above.
[0888] First, the problem to be solved by the fifth embodiment is described. For the purpose of improving the visual recognition of the image and suppressing the damage of the device surface, etc., the image display device has various optical layered bodies. Such optical layered bodies usually have a plastic film as an optical film and a functional layer provided on the film (for example, refer to Japanese Patent Publication No. 2007-046031 and Japanese Patent Publication No. 2012-256014).
[0889] The present inventors have found that the pencil hardness of an optical layered body or the adhesion (light-resistant adhesion) between a resin substrate and a functional layer in the optical layered body after exposure to a light environment may be insufficient.
[0890] In recent years, there has been a growing trend toward building a sustainable recycling-oriented society. From the perspective of carbon neutrality, there is a desire to move away from fossil fuels in the material field as well as in the energy field.
[0891] An object of a fifth embodiment of the present disclosure is to provide an optical layered body that is excellent in pencil hardness and light-resistant adhesion between a resin substrate and a functional layer and that can reduce environmental burden.
[0892] According to the fifth embodiment of the present disclosure, an optical layered body having excellent pencil hardness and light resistance adhesion between the resin substrate and the functional layer and capable of reducing environmental burden is provided. In addition, an optical layered body having the same degree of optical and mechanical properties as when using a resin derived from fossil fuels even when using a resin derived from biomass materials can be provided.
[0893] [Optical layered body]
[0894] In the description of the optical layered body of the fifth embodiment of the present disclosure described below, for the parts that can be constructed in the same manner as the optical layered body described in the first embodiment, the same symbols as those used in the first embodiment are sometimes used, and repeated descriptions are omitted. In addition, with respect to the surface plate, image display device, and polarizer having an optical layered body of the fifth embodiment of the present disclosure described below, for the parts that can be constructed in the same manner as the surface plate, image display device, and polarizer having an optical layered body described in the first embodiment, the same symbols as those used in the first embodiment are sometimes used for description, and repeated descriptions are sometimes omitted. In the case where it is obvious that the effects obtained in the first embodiment can also be obtained in the fifth embodiment, the description thereof is sometimes omitted. As for the description of the optical layered body, surface plate, image display device, and polarizer of the fifth embodiment of the present disclosure, the description of the optical layered body, surface plate, image display device, and polarizer of the first embodiment of the present disclosure can be applied as long as there is no contradiction.
[0895] The description of the resin substrate included in the optical layered body of the fifth embodiment of the present disclosure can be applied to the description of the optical film of the first embodiment of the present disclosure as long as there is no contradiction. Regarding the resin substrate of the fifth embodiment of the present disclosure described below, for parts that can be configured similarly to the optical film described in the first embodiment, the same symbols as those used in the first embodiment are sometimes used for description, and duplicate descriptions are sometimes omitted.
[0896] The description of the resin film included in the optical layered body of the fifth embodiment of the present disclosure can be applied to the description of the polyester film of the first embodiment of the present disclosure as long as there is no contradiction. Regarding the resin film of the fifth embodiment of the present disclosure described below, for parts that can be constructed in the same manner as the polyester film described in the first embodiment, the same symbols as those used in the first embodiment are sometimes used for description, and repeated descriptions are sometimes omitted.
[0897] The optical layered body of the fifth embodiment of the present disclosure comprises a resin substrate and a functional layer disposed on the resin substrate. In this specification, an optical layered body refers to a layered body capable of transmitting light. When "optical layered body" is recorded in the description of the fifth embodiment below, unless otherwise specified, it refers to the optical layered body of the fifth embodiment of the present disclosure.
[0898] like Figure 7 As shown, the resin substrate 5 has a first surface 5a and a second surface 5b facing the first surface 5a. The resin film described below also has a first surface and a second surface facing the first surface. In the case where the first surface and the second surface are not particularly distinguished, it is sometimes simply referred to as a "surface". The resin substrate has a first direction and a second direction orthogonal to the first direction in the surface. The first direction is the longitudinal direction, flow direction or machine direction (MD) of the resin substrate in the fifth embodiment. The second direction is the transverse direction or width direction (TD) of the resin substrate in the fifth embodiment.
[0899] Figure 7 It is a cross-sectional view showing the optical layered body 3 according to the fifth embodiment of the present disclosure. Figure 7 The optical layered body 3 includes a resin substrate 5 and a functional layer 8 in this order. The functional layer 8 is provided on the first surface 5 a of the resin substrate 5 .
[0900] Figure 8 It is a cross-sectional view showing the optical layered body 3 according to the fifth embodiment of the present disclosure. Figure 8 The optical layered body 3 includes a resin film 7, an easy-adhesion layer 6, and a functional layer 8 in this order. The easy-adhesion layer 6 and the functional layer 8 are provided on a first surface 7a of the resin film 7. The resin substrate 5 is composed of the resin film 7 and the easy-adhesion layer 6. The resin film 7 has a first surface 7a and a second surface 7b facing the first surface 7a.
[0901] The total light transmittance of the optical layered body is 70% or more, 80% or more, 85% or more, 88% or more, or 90% or more. The higher the total light transmittance of the optical layered body, the more preferred it is, and it may be 99% or less, 98% or less, or 95% or less. The total light transmittance is measured in accordance with JIS K7361-1:1997.
[0902] The haze of the optical layered body may be 10.0% or less, 7.0% or less, 5.0% or less, 4.0% or less, or 3.0% or less. The haze of the optical layered body may be 0.1% or more, 0.2% or more, or 0.3% or more. The haze is measured in accordance with JIS K7136:2000.
[0903] In the case of an optical layered body including a resin film, an optional easy-adhesion layer, and a functional layer in this order, the total light transmittance and the haze were measured with the light incident surface being the resin film surface.
[0904] The biomass degree of the optical layered body is 10% or more, 11% or more, 12% or more, 15% or more, or 20% or more. Such an optical layered body can reduce the environmental burden. The higher the biomass degree of the optical layered body, the more preferred it is, for example, it can be 98% or less, 90% or less, 80% or less, 70% or less, 60% or less, 50% or less, 40% or less, 30% or less, or 25% or less.
[0905] When measuring the biomass content of the entire optical layered body, a sample may be prepared from the optical layered body. When measuring the biomass content of each layer in the optical layered body, a target layer may be separated from the optical layered body to prepare a sample.
[0906] <Resin base material>
[0907] In the fifth embodiment, the resin substrate includes at least a resin film.
[0908] In the fifth embodiment, the resin substrate is composed of a resin film.
[0909] In the fifth embodiment, the resin substrate includes a resin film and an easily adhesive layer provided on the resin film.
[0910] The resin film preferably has transparency, smoothness, heat resistance and excellent mechanical strength. As the resin forming the resin film, thermoplastic resins such as polyester, triacetyl cellulose, diacetyl cellulose, cellulose acetate butyrate, polyamide, polyimide, polyether sulfone, polysulfone, polyolefin (such as polyethylene, polypropylene and polymethylpentene), polyvinyl chloride, polyvinyl acetal, polyether ketone, polymethyl methacrylate, polycarbonate and polyurethane can be cited. Among these, polyester and triacetyl cellulose are preferred, and polyester is more preferred.
[0911] The resin substrate may contain a resin derived from a recycled material. In particular, the resin film of the resin substrate may contain a resin derived from a recycled material. When the resin substrate contains a resin derived from a recycled material, the environmental burden can be further reduced.
[0912] The resin substrate may contain a resin derived from a biomass material. The resin film may contain a resin derived from a biomass material. Examples of the resin derived from a biomass material include polyester derived from a biomass material, polyolefin derived from a biomass material, triacetyl cellulose, diacetyl cellulose, and cellulose acetate butyrate. By measuring the resin derived from a biomass material as a raw material for the resin substrate and the resin film and determining it as a raw material, the biomass degree of the resin substrate and the resin film can be predetermined, and the quality of the resin substrate and the resin film can also be controlled.
[0913] As the resin film, for example, polyester films such as polyethylene terephthalate film and polybutylene terephthalate, polyolefin films such as triacetyl cellulose film, polyethylene film and polypropylene film, polyamide films such as nylon film and nylon 6 / m-xylylenediamine nylon 6 coextruded costretched film, coextruded costretched film of polypropylene / ethylene-vinyl alcohol copolymer, and composite films formed by laminating two or more of these films can be cited. Among these, polyester film and triacetyl cellulose film are preferred, and polyethylene terephthalate film is more preferred.
[0914] Polyester will be described in more detail below.
[0915] Polyester refers to a copolymer of at least a diol component and a dicarboxylic acid component. The resin substrate may contain a polyester derived from a biomass material (hereinafter also referred to as "biomass polyester") as the polyester. The resin film may contain a biomass polyester as the polyester.
[0916] As polyester, specifically, polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polytrimethylene terephthalate (PTT), polyethylene naphthalate (PEN), polybutylene naphthalate (PBN) and polyethylene 2,5-furandicarboxylate (PEF) can be cited. Among these, PET is preferred because a resin film with excellent mechanical strength can be obtained. As biomass polyester, specifically, polyesters produced using monomers derived from biomass materials as part or all of the raw material monomers (diol components and dicarboxylic acid components) in these polyesters can be cited.
[0917] The resin base material may contain one or more polyesters.
[0918] The resin film may contain one or more polyesters.
[0919] The resin substrate and the resin film may contain polyester derived from fossil fuels, biomass polyester, or both. By making the resin substrate or the resin film contain at least a portion of biomass polyester, the amount of polyester derived from fossil fuels can be reduced compared to the past, thereby reducing the environmental burden.
[0920] The resin substrate and the resin film may contain polyester from recycled materials. The polyester contained in the resin substrate and the resin film may be polyester from recycled materials and biomass polyester. A part of the polyester contained in the resin substrate and the resin film may be polyester from recycled materials. In this case, the other part of the polyester contained in the resin substrate and the resin film that is not polyester from recycled materials may be biomass polyester. The polyester from recycled materials may be recycled PET. The polyester from recycled materials may be a polyester derived from a raw material manufactured by recycling. More specifically, as...
Claims
1. An optical film, which is an optical film for laminating a functional layer, wherein: The optical film contains polyester, The biomass degree of the optical film is more than 10%, The total light transmittance of the optical film is more than 70%, The in-plane retardation of the optical film is 3,000 nm or more and 30,000 nm or less.
2. The optical film according to claim 1, wherein: The optical film contains polyester derived from biomass materials.
3. The optical film according to claim 1, wherein: The in-plane phase difference is greater than or equal to 4,000 nm and less than or equal to 15,000 nm.
4. The optical film according to claim 1, wherein: The Martens hardness of at least one surface of the optical film is 110 N / mm 2 Above 170N / mm 2 the following.
5. The optical film according to claim 1, wherein: The elastic deformation power of at least one surface of the optical film is 60% to 70%. 6 . The optical film according to claim 1 , which is composed of a polyester film containing the polyester, or comprises a polyester film containing the polyester and an easy-adhesion layer provided on the polyester film.
7. The optical film according to claim 6, wherein: The resin constituting the easy-adhesion layer is a resin derived from a biomass material.
8. The optical film according to claim 6, wherein: The resin constituting the easy-adhesion layer is a resin derived from fossil fuels.
9. The optical film according to claim 6, wherein: The resin constituting the easy-adhesion layer is a mixed resin of a resin derived from a biomass material and a resin derived from a fossil fuel.
10. An optical layered body comprising: The optical film of claim 6; and The functional layer is disposed on the optical film.
11. An optical film, which is an optical film for laminating a functional layer, wherein: The optical film contains polyester, The biomass degree of the optical film is more than 10%, The total light transmittance of the optical film is more than 70%, The optical film has an in-plane retardation of 1,500 nm or less.
12. The optical film according to claim 11, wherein: The optical film contains polyester derived from biomass materials.
13. The optical film according to claim 11, wherein: The in-plane phase difference is greater than or equal to 300 nm and less than or equal to 1,450 nm.
14. The optical film according to claim 11, wherein The Martens hardness of at least one surface of the optical film is 110 N / mm 2 Above 170N / mm 2 the following.
15. The optical film according to claim 11, wherein The elastic deformation power of at least one surface of the optical film is 60% to 70%. 16 . The optical film according to claim 11 , which is composed of a polyester film containing the polyester, or comprises a polyester film containing the polyester and an easy-adhesion layer provided on the polyester film.
17. The optical film according to claim 16, wherein: The resin constituting the easy-adhesion layer is a resin derived from a biomass material.
18. The optical film according to claim 16, wherein: The resin constituting the easy-adhesion layer is a resin derived from fossil fuels.
19. The optical film according to claim 16, wherein: The resin constituting the easy-adhesion layer is a mixed resin of a resin derived from a biomass material and a resin derived from a fossil fuel.
20. An optical layered body comprising: The optical film of claim 16; and The functional layer is disposed on the optical film.
21. An optical effect film, which is an optical effect film containing polyester, wherein: The biomass degree of the optical effect film is 10% or more, The total light transmittance of the optical film is more than 70%. The yellowness index YI of the optical effect film is not less than -1.0 and not more than 2.
5.
22. The optically effective film according to claim 21, wherein: The optically effective film contains a bluing agent.
23. The optically effective film according to claim 22, wherein: The optically effective film is a polyester film containing the polyester and the bluing agent.
24. The optically effective film according to claim 22, wherein: The optical effect film includes a polyester film containing the polyester and a color tone adjustment layer containing the bluing agent.
25. The optically effective film according to claim 24, wherein: The color tone adjustment layer is an easy-adhesion layer.
26. The optically effective film according to claim 25, wherein: The resin constituting the easy-adhesion layer is a resin derived from a biomass material.
27. The optically effective film according to claim 25, wherein: The resin constituting the easy-adhesion layer is a resin derived from fossil fuels.
28. The optically effective film according to claim 25, wherein: The resin constituting the easy-adhesion layer is a mixed resin of a resin derived from a biomass material and a resin derived from a fossil fuel.
29. The optically effective film according to claim 24, wherein: The polyester film has a thickness of 10 μm to 200 μm, and the color tone adjustment layer has a thickness of 10 nm to 1,000 nm.
30. The optically effective film according to claim 21, wherein: The optically effective film contains polyester derived from biomass materials.
31. The optically effective film according to claim 21, wherein: The Martens hardness of at least one surface of the optically effective film is 110 N / mm 2 Above 170N / mm 2 the following.
32. The optically effective film according to claim 21, wherein: The elastic deformation power of at least one surface of the optically effective film is 60% to 70%.
33. The optically functional film according to claim 21, further comprising a functional layer.
34. The optically effective film according to claim 33, wherein: The functional layer contains a bluing agent.
35. An easily adhesive film comprising a polyester film and an easily adhesive layer, wherein: The polyester film contains polyester, The biomass content of the highly adhesive film is 10% or more. The total light transmittance of the highly adhesive film is 70% or more. The average value of δq / δa on the surface of the easy-adhesion layer is 3.10 or less, The easy-adhesion film is used to provide a functional layer on the easy-adhesion layer. <Calculation of average value of δq / δa> The 10 μm×10 μm area on the surface of the easy-adhesion layer is measured using a phase mode of an atomic force microscope; the distribution of the phase signal on the surface of the easy-adhesion layer is obtained by the measurement; the unit of the phase signal is [deg]; The arithmetic mean of the phase signal shown in the following equation 1 is set to δa; The root mean square of the phase signal shown in the following equation 2 is set to δq; In the following formula 1 and the following formula 2, orthogonal coordinate axes X and Y are set on the reference surface representing the average value of the phase signal, the axis orthogonal to the reference surface is set as the Z axis, and the curved surface of the phase signal is set as f(x, y); in the following formula 1 and the following formula 2, the size of the area for calculating δa and δq is set as Lx and Ly; in the following formula 1 and the following formula 2, Ar=Lx×Ly; Select 7 2μm×2μm areas from the 10μm×10μm measurement area; δa, δq and δq / δa at 7 locations are calculated; based on δq / δa at 5 locations after removing the maximum and minimum values from the δq / δa at 7 locations, an average value of δq / δa is calculated; [Number 1] 36. The adhesive film according to claim 35, wherein The polyester film contains polyester derived from biomass materials.
37. The adhesive film according to claim 35, wherein The Martens hardness of at least one surface of the highly adhesive film is 110 N / mm 2 Above 170N / mm 2 the following.
38. The easily adhesive film according to claim 35, wherein The elastic deformation power of at least one surface of the highly adhesive film is 60% to 70%.
39. The adhesive film according to claim 35, wherein The highly adhesive film has a crystallinity of 90% or less.
40. The easily adhesive film according to claim 35, wherein The resin constituting the easy-adhesion layer is a resin derived from a biomass material.
41. The adhesive film according to claim 35, wherein The resin constituting the easy-adhesion layer is a resin derived from fossil fuels.
42. The adhesive film according to claim 35, wherein The resin constituting the easy-adhesion layer is a mixed resin of a resin derived from a biomass material and a resin derived from a fossil fuel.
43. An optical layered body comprising: The highly adhesive film according to claim 35; and A functional layer provided on the easily adhesive layer of the easily adhesive film.
44. An optical layered body comprising a resin substrate and a functional layer provided on the resin substrate, wherein: The composite elastic modulus of the functional layer is set to E r B. The composite elastic modulus of the resin substrate is set to E r In case of A, E r B is 1.0 GPa or more and 10.0 GPa or less, E r B / E r A is 0.50 or more and 2.00 or less, The biomass degree of the optical layered body is 10% or more, The optical layered body has a total light transmittance of 70% or more.
45. The optical layered body according to claim 44, wherein: The functional layer contains a resin derived from a biomass material.
46. The optical layered body according to claim 44, wherein: The functional layer contains nanoparticles.
47. The optical layered body according to claim 44, wherein: The resin substrate contains a resin derived from a biomass material.
48. The optical layered body according to claim 44, wherein: The resin substrate is composed of a resin film, or includes a resin film and an easy-adhesion layer provided on the resin film.
49. The optical layered body according to claim 44, wherein: The functional layer is at least one layer selected from a hard coating layer, an anti-glare layer, an anti-reflection layer, a phase difference layer, an antifouling layer, an antistatic layer and a conductive layer.
50. The optical film according to any one of claims 1 to 9 and 11 to 19, comprising polyester derived from recycled materials.
51. The optically functional film according to any one of claims 21 to 34, comprising polyester derived from recycled materials.
52. The highly adhesive film according to any one of claims 35 to 42, comprising polyester derived from a recycled material.
53. The optical layered body according to any one of claims 44 to 49, wherein The resin substrate contains a resin derived from a recycled material.
54. A surface plate for an image display device, comprising: Resin sheet or glass sheet; and The optical film according to any one of claims 1 to 9 and 11 to 19, the optically functional film according to any one of claims 21 to 34, the easily adhesive film according to any one of claims 35 to 42, or the optical layered body according to any one of claims 10, 20, and 43 to 49 disposed on the plate.
55. An image display device comprising: display element; and The optical film according to any one of claims 1 to 9 and 11 to 19, the optically functional film according to any one of claims 21 to 34, the easily adhesive film according to any one of claims 35 to 42, or the optical layered body according to any one of claims 10, 20, and 43 to 49, which is disposed on the display element.
56. A polarizing plate comprising: a polarizing element; a first transparent protective plate disposed on one surface of the polarizing element; and a second transparent protective plate disposed on the other surface of the polarizing element, wherein: At least one of the first transparent protective plate and the second transparent protective plate is the optical film according to any one of claims 1 to 9 and 11 to 19, the optically functional film according to any one of claims 21 to 34, the easily adhesive film according to any one of claims 35 to 42, or the optical layered body according to any one of claims 10, 20, and 43 to 49.
Citation Information
Patent Citations
Hard coating film and method for producing the same
JP2007046031A
Liquid crystal display device, polarizing plate, and polarizer protective film
JP2012256014A
Biaxially oriented polyester film and method for producing the same
JP2016141058A